AI driven integrated approach of microalgae Chlorella vulgaris AK and amine functionalized multi-walled carbon nanotubes (AF-MWCNT) for sewage wastewater treatment with improved biodiesel and anti-fungal activity - Anwesha Dey; Juhi Saxena; Prince Jain; Jaivik Pathak; Unnati Joshi; Anand Joshi; Krishna Mohan Poluri; Shakeel Ahmad Khan (Biomass and Bioenergy, 2027)

Digital nudging toward sustainable healthy foods: Insights from a trial on a university-based dashboard for promoting sustainable eating habits - Mariana Moncada de la Fuente; Prince Agyemang; Ebenezer M. Kwofie; Marilyne Chicoine; Ghina El Haffar; Laurette Dube; Stan Kubow; Valerie Orsat (Appetite, 2027)

Strength and durability of unary and binary nano particle blended cement composites - Aiswarya Sukumaran; Hsein Kew; Sevket Can Bostanci; G. Prince Arulraj (European Journal of Environmental and Civil Engineering, 2026)

Assessment of antidiabetic activity (α-amylase, α-glucosidase and dipeptidyl peptidase-IV inhibitory activities) of collagen hydrolysate recovered from buffalo hide along with its characteristics and antioxidant properties - Veppalampatti Ramanathan Santhosh; Tanbir Ahmad; Prince Devadason Immanuel; Devendra Kumar; Suman Talukder; Ashim Kumar Biswas; Sanjod Kumar Mendiratta; Zunjar Baburao Dubal; Ajay Kumar; Yasotha Thirupathi; C. K. Faslu Rahman; Anand Thoppil Shaji; et al. (Food and Humanity, 2026)

Farm-to-fork genomic analysis of Campylobacter coli in poultry and pig systems: A one health challenge in Northeast India - Arockiasamy Arun Prince Milton; Kandhan Srinivas; Heiborkie Shilla; Vivekanandhan Rangaraju; Samir Das; G. Bhuvana Priya; Sandeep Ghatak (Food and Humanity, 2026)

Environmental modulation of cytotoxicity and virulence factor stability in psychrotolerant Bacillus cereus group isolates - Tyler Chandross-Cohen; Mackenna Yount; Erin Readinger; Cassidy Prince; Kayla Kimble; Brian Praul; Lydia Weidner; Jasna Kovac (Food Microbiology, 2026)

Effect of pre-treatment and direct contact on rare earth element bioleaching from former Pea Ridge mine tailings by phosphate-solubilizing microbes - Prince Oppong Amoh; Hunter W. Schroer (Bioresource Technology, 2026)

Increasingly diverse coral reef fishes are threatened by unsustainable fishing in Palau - Christina Muller Karanassos; Alyssa Marshell; Barrett Wolfe; Steve Lindfield; Jeremy Prince; Nils C. Krueck (Reviews in Fish Biology and Fisheries, 2026)
Reef fisheries underpin the economy, culture, and food security of Indo-Pacific island nations, yet many target species are depleted due to inadequate management. Despite its reputation as a regional leader in fisheries management, Palau has experienced declines among key reef fish species, necessitating a comprehensive stock status assessment amid ongoing discussions to lift the national export ban. Conventional stock assessments are not feasible for most species due to limited data. To address this, we compiled life history information and applied data-limited, length-based stock assessment methods across 32 parameter scenarios. Analyses were based on a decade of fishery-dependent landing data (2014–2024) for 45 key species, with comparisons to historical landings (1976–1991) to evaluate changes in catch composition. Using Length-Based Spawning Potential Ratio as the primary assessment method, we found most species are in poor condition: 24.4% classified as “Depleted”, 51.1% “Vulnerable”, and 17.8% “Depleting”. Only 6.7% met criteria for “Sustainable” status (spawning potential ratio > 40% of unfished levels and a fishing mortality below natural mortality). Landings data indicate a clear shift from historically dominant large-bodied species to smaller taxa, reflecting target species depletions and regulatory changes. Despite life history parameters uncertainty, results were robust across alternative length-based approaches and consistently indicated widespread stock depletion. These findings highlight an urgent need for stronger management, including effective size limits, the protection of spawning aggregations, and retention of the export ban. Lifting the ban would likely increase fishing pressure and further accelerate declines of Palau’s already depleted reef fish populations.

FOXO transcription factors in Alzheimer’s Disease: balancing neuroprotection and neuronal degeneration - Mukul Shyam; Aleen Veronica; Jyoti Wadhwa; Vidhi Sharma; Oveyaa B M; Prathap Srirangan; Rajendran Venkatesh; Sabina Evan Prince (Molecular Biology Reports, 2026)

Epigenetic insights into high-altitude-induced venous thromboembolism: methylation signatures in Indian population - Sunanda Arya; Babita Kumari; Rashi Khare; Iti Garg; Prince Pacherwal; Rajneesh Kumar Joshi; Rajiv Kumar; Swati Srivastava (Molecular Biology Reports, 2026)

From bench to bedside: stem cell therapy as a transformative approach against HIV - Ankit Kumar Bharti S; Anirban Goutam Mukherjee; Abilash Valsala Gopalakrishnan; Babu Gajendran; Rahul Vashishth; Sabina Evan Prince (Molecular Biology Reports, 2026)

Decoding BDNF in neurodevelopmental, neurodegenerative, and neurological disorders: mechanisms and therapeutic perspectives - S. P. Raswanthiya; Obert Peterpaul Fernandes; Martin Prince Mathew; Piyush Jagdish Balgote; Jayanthi Sivaraman (Molecular Biology Reports, 2026)

The use of artificial intelligence in advancing molecular biology in Africa: a narrative review - Daniel Awuah; Alphonse Hounkpe; Jesse Anane-Asamoah; William Kanmwaa Dakubo; Isaac Kofi Adu; Prince Amoah Barnie; Emmanuel Owusu Ansah; Kwadwo Fosu; Cara Obenewaa Aidoo; Victoria Essien; Yakubu Adam; Ernest Ninson; et al. (Molecular Genetics and Genomics, 2026)

Multiphysics simulations of the Advanced Test Reactor using Pronghorn and Griffin - Guillaume Gesmier; Peter German; Mauricio Tano Retamales; Guillaume Giudicelli; Joshua Hanophy; Namjae Choi; Zachary M. Prince (Annals of Nuclear Energy, 2026)

Nano/submicron lignin particles from oil palm empty fruit bunches: Synthesis, amination, performance of Pb2+ adsorption, and DFT insights - Prince Sayungki; Lya Sulistyioning Rahayu; Tasrikin Agustianto; Oktaviani Oktaviani; Erik Budi Santiko; Muryanto Muryanto; Mirza Ardella Saputra; Atanu Kumar Das; Gagus Ketut Sunnardianto; Roni Maryana (Biomass and Bioenergy, 2026)

Structurally controlled gold in the Beposo area, Ashanti Region, Ghana: testing a mineral-systems targeting model with random forest and decision tree classifiers - Eric Dominic Forson; Samuel Nunoo; Prince Ofori Amponsah; Ralph Dartey Osei; Patrick Asamoah Sakyi (Earth Science Informatics, 2026)

A comprehensive review on advancements in microgreen extraction and stabilization for food and functional food applications - Nallaswamy Vanitha; Gourikutty Kunjurayan Rajesh; Kizhakkeppurath Kumaran Ajeeshkumar; Manadan Varghese Prince (Trends in Food Science & Technology, 2026)

Responsible scaling for sustainable intensification: Dimensions of land rights and farmer realities in Northern Ghana - Prince Asiedu; Mirja Michalscheck; Bekele Hundie Kotu; Birhanu Zemadim Birhanu; Martina Padmanabhan; Charity Osei Amponsah (Land Use Policy, 2026)

Perceived injustice and resource exploitation as drivers of community apathy in REDD+ implementation in Ghana - Prince Owusu; Naamang Ezekiel Liiman; Derrick Werekoh Asaah; Kelvin Boakye; Emil Gasinu; Bright Kusi Appiah; Akosua Pokuaa Yeboah; Sandy Chereh (Forest Policy and Economics, 2026)

A multi-model machine learning approach for the prediction of the fluvial bed sediment load with uncertainty assessment - Numan Ijaz; Sajjad Haider; Ahsan Ullah Khan; Prince Mahmood; Zain Syed (Modeling Earth Systems and Environment, 2026)

Sodium Alginate Offers Neuroprotection via Mitigating Inflammatory and Oxidative Markers in Cadmium-exposed Experimental Albino Rats - Prince; Surbhi Gupta; Prabhat Singh; Sachin Tyagi; Bhupesh Sharma; Vikram Singh (Journal of Pharmaceutical Innovation, 2026)

Analysis of turbulence-induced crossflow and coolant mixing under various flow interventions in rod bundle geometries - Prince Amoah; Vincent Yao Agbodemegbe; Edward Shitsi; Emmanuel Ampomah-Amoako (Annals of Nuclear Energy, 2026)

Phenology constrains the predictability of soil respiration in cropping systems revealed through interpretable machine learning - Jing Yang; Jing Hu; Dana M. Miles; Frances A. Podrebarac; Daniel McCraine; Joby M. Prince Czarnecki; John P. Brooks (Agricultural and Forest Meteorology, 2026)

Impact of leeway and rudder angles on propulsive performance of a single screw wind-powered ship - Saeed Hosseinzadeh; Stephen R. Turnock; Joseph Banks; Dominic Hudson; Martyn Prince (Ocean Engineering, 2026)

Instrumental and normative perspectives on non-compliance with urban planning and development regulations in Ghana - Prince Aboagye Anokye; Stephen B. Liwur; Justice P. Tuffour; Frank Addo Kuffour (Land Use Policy, 2026)

Population exposure to nitrogen dioxide (NO2) pollution in West Africa - Prince Junior Asilevi; Alex Kwao Ablerdu; Lydia Korley; Felicia Dogbey; Emmanuel Quansah (Environmental Pollution, 2026)

Next generation risk assessment and new approach methodologies for sustainable management of heavy metal contaminated environments: A critical review - Prince Kumar Singh; Indrajeet Kumar; Umesh Kumar; Rahul Prasad Singh; Ram Sharan Singh; Rajesh Kumar Sharma (Environmental Pollution, 2026)

Mapping of microplastic toxicity: Uptake, trophic transfer, and ecotoxicological risks in marine ecosystems - Prince Kumar Singh; Nisha Singh; Indrajeet Kumar; Umesh Kumar; Akanksha Dwivedi; Priyanka Singh; Saumya Mishra; Khushboo Pal; Avanish Prajapati; Rajesh Kumar Sharma (Aquatic Toxicology, 2026)

Biological Insights and Demographic Characteristics of Thumbprint Monocle Bream, Scolopsis bimaculata from the Southern Coromandel Coast of Tamil Nadu, India - R. G. Sasikumar; S. Santhoshkumar; P. Pavinkumar; B. Paplin Prince; J. Joyson Paul; M. Sharumathi; V. Santhiya; V. Suryapraba (Thalassas: An International Journal of Marine Sciences, 2026)

Biocontrol potential of Trichoderma and Bacillus strains against Macrophomina phaseolina causing dry root rot in groundnut - Prince Jayasimha Pamala; R. Sarada Jayalakshmi; K. Vemana; G. Mohan Naidu; Rajeev K. Varshney; Hari Kishan Sudini (Journal of Plant Pathology, 2026)

Knowledge to action: assessing the impact of schistosomiasis education on community knowledge, attitudes and practices in Nelson Mandela Bay, South Africa - Prince S. Campbell; Janine B. Adams; Melusi Thwala; Opeoluwa Oyedele; Paula E. Melariri (Infectious Diseases, 2026)

Nitric oxide: A key player in plant defense against biotic stress - Devanshu Dev; Shraddha Bhaskar Sawant; Prince Kumar Gupta; Priya Bhargava; Prachi Singh; Sudha Nandni; Udit Nandan Mishra; Sankarganesh E.; Abhijeet Ghatak (Plant Science, 2026)

Thermodynamically guided design of high-entropy alloy electrocatalysts for efficient and durable overall water splitting: From scalable synthesis to atomic-scale understanding of enhanced reaction kinetics - M. Athira Chandran; Prince Sharma; Prashant Singh; Bhagavatula L.V. Prasad; Ashutosh K. Singh (Chemical Engineering Journal, 2026)

Landscape controls physicochemical properties and nutrient dynamics of a biotite-granite catena in the rainforest zone of Ghana - Johnny Kofi Awoonor; Dora Neina; Alexander Owusu Ansah; Jackson Kwame Gyamfi; Prince Addai; Collins Korbla Tay (CATENA, 2026)

Ethnopharmacological exploration of Indian medicinal plants: from traditional knowledge to modern medicine - Indrajeet Kumar; Sachin Kumar Vishwakarma; Prince Kumar Singh; Umesh Kumar; Rahul Prasad Singh; Parvati Madheshiya; Akanksha Dwivedi; Priyanka Singh; Rajesh Kumar Sharma (Phytochemistry Reviews, 2026)

Phytochemicals in mosquito management: advances in herbal repellents and their future potential - Mukul Shyam; B. M. Oveyaa; Reshmi Kumari; Jyoti Wadhwa; Prathap Srirangan; Sabina Evan Prince (Phytochemistry Reviews, 2026)

Bioinformatics-based B-cell epitope identification from Leptospira interrogans outer membrane proteins LIC11574 and LIC13411 for the rational development of a multi-epitope anti-Leptospira vaccine - Jason M. Porcalla; Princes Angela P. Podiotan; Sedrick Maru M. Gutierrez; Nedrick T. Distor (Archives of Microbiology, 2026)

Characterization and Evaluation of Justicia adhatoda L. and Its Green Synthesized Nanoparticles for Its Efficacy in Culex quinquefasciatus - Vikas Chandra Roy; Prince Leeban Johnwilmet; Rajalakshmi Anbalagan; Jayalakshmi Krishnan; Jefrillah Jebaseelan; Anand Setty Balakrishnan (Acta Parasitologica, 2026)

In vitro and in silico evaluation of Picralima nitida monoterpene indole alkaloids as antimicrobial resistance modifiers - Makafui Adzo Gbemu; Susana Dufie Boatey; Prince Dagadu Okyere; Yaw Duah Boakye; John Nii Addotey; Rita Akosua Dickson; Edmund Ekuadzi (Advances in Traditional Medicine, 2026)

Development of a novel rapid genome exponential amplification reaction (GEAR) assay for high-sensitivity detection of Campylobacter coli using simplified sample preparation for on-site detection - A. Arun Prince Milton; Zakir Hussain; Moon Moon Mech; Kandhan Srinivas; G. Bhuvana Priya; Heiborkie Shilla; Samir Das; Girish Patil Shivanagowda; Sandeep Ghatak (World Journal of Microbiology and Biotechnology, 2026)

Two Decades of Nutrient Management Improves Soil Microbial Processes Regulating Carbon and Nutrient Cycling in a Pearl Millet–Wheat System in Semi-Arid Alluvial Soils - Sharat Kothari; Vinod Kumar Sharma; K. M. Manjaiah; Indu Chopra; Debarup Das; C. M. Parihar; Kadooran Abshiba; Prince Kumar; Kapil A. Chobhe; Mandira Barman (Journal of Soil Science and Plant Nutrition, 2026)

Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Synthesis of Fe-doped carbon from expired iron supplement tablets coupled with PMS for tetracycline degradation: From a non-radical pathway to an animal survival study - Sabarison Pandiyarajan; Ho-Chiao Chuang; Madan Kumar Arumugam; Divya Rajendran; Nguyen Xuan Sang; Prince Makarios Paul S; Ramanathan Subramanian (Process Safety and Environmental Protection, 2026)

Ingredient-driven mitigation of warmed-over flavor by Chinese star anise in precooked Chinese stewed beef - Junmei Liu; Siyang Deng; Donghui Xu; Guangyang Liu; Prince Chisoro; Ping Yang; Chunhui Zhang; Christophe Blecker (Food Research International, 2026)

Forest protection, EKC and LCC dynamics in the world's largest forest nations - Ugur Korkut Pata; Selin Karlilar Pata; Solomon Prince Nathaniel (Forest Policy and Economics, 2026)

Interactive effects of genotype and ginger supplemented diets on Performance, serum biochemical parameters, renal markers and antioxidant status of broilers (II) - Victor Mela Obinna Okoro; Adeniyi Charles Adeola; Uduak Emmanuel Ogundu; Ogechi Evangeline Kadurumba; Ahmadu Yahaya; Chidera Stella-Maris Ojiugo; Esther Ifechukwu Iheanacho; Ezinne Chioma Onyeji; Princes Natachi Nwalozie; Ifeanyi Solomon Ahamba; Martins Chima Uchegbu (Tropical Animal Health and Production, 2026)

Gestational deltamethrin exposure exacerbates post-traumatic epileptiform activity and social deficits, diminishing the therapeutic efficacy of curcumin in rats - Kamendra Kumar; Prince Kumar; Pavan Kumar; Deepak Sharma (Metabolic Brain Disease, 2026)

Spatio‐Temporal Patterns in Relative Abundance and Distribution of Southern Right Whales in Southwestern Australia, 2021–2024 - Katy Fannei; Max Fabry; Joshua N. Smith; Paul Close; Bridgette O'Shannessy; Barbara Stewart; Jane Prince; Claire Charlton (Marine Mammal Science, 2026)
Southern right whales ( Eubalaena australis ) are listed as Endangered in Australia due to past commercial exploitation. Currently, they are experiencing contemporary declines in population growth rates. Knowledge of critical periods and habitats in whale occupancy and reproduction is crucial for conservation efforts. This study documented the inter‐ and intra‐annual relative abundance and distribution of southern right whales within a Biologically Important Area along 450 km of southern coastline in Western Australia, using data from 94 weekly aerial surveys conducted from May–November 2021–2024. A total of 5899 individual sightings were recorded, of which 72% were mother–calf pairs. Whales were present from late‐May to early‐November, and peak relative abundance occurred in mid–late August. Maximum relative abundance varied annually, ranging from 92 to 194 individuals. Peak relative abundance periods and counts generally agreed with annual census observations for mother–calf pairs. Whale counts in the study area accounted for approximately 22% of the overall western population. Mother–calf pairs and unaccompanied whales occupied four key aggregation areas: Cheynes Beach, Cheyne Bay, Wray Bay, and Doubtful Island Bay. These findings highlight the seasonal significance of reproductive areas for southern right whales in southwestern Australia and are imperative for informing national recovery planning for the species.

YOLO–geochemical integration for real-time aeolian dust monitoring: a critical review of signatures, health risks, and policy implications - Prince Jebedass Isaac Chandran; Oguz Yigiterhan; R. Lakshmipathy (Environmental Monitoring and Assessment, 2026)

Temporal trends and evolutionary patterns of marine fish diversity along the Gujarat coast - Tejas Gurjar; Prince Upadhyay; Vyomil Patel; Monisha Kottayi; Ankita Doshi; Parth Pandya (Regional Studies in Marine Science, 2026)

Genotype and environmental effects on grain yield, agronomic performance, and beta-carotene content of provitamin A maize in tropical savannah ecologies - Gloria B. Adu; Isaac K. Amegbor; Flora C. Amagloh; Charles Nelimor; Baffour Badu-Apraku; Prince M. Etwire; Desmond S. Adogoba; Benedicta Atosona; Paulina A. Aboyadana; Kulai A. Manigben; Rashid Seidu; Maryke Labuschagne (Journal of Cereal Science, 2026)

Crossbreeding effects and combining abilities among Namibian sheep breeds raised under arid conditions - Uaipo Ngorio; Clarice Princes Mudzengi; Soul Washaya (Ecological Genetics and Genomics, 2026)

How a nocturnal cold front amplified wildfire impacts on near-surface air quality downwind of the second largest US wildfire - Sandip Pal; Matthew Hamel; Hassanpreet Dhaliwal; Diya Das; Danielle Harr; Tyler Danzig; Temple R. Lee; Kiran Menon; Nicholas E. Prince; Matthew Asel; Wesley Burgett (Atmospheric Research, 2026)

Alteration in hippocampal mitochondria ultrastructure and cholesterol accumulation linked to mitochondrial dysfunction in the valproic acid rat model of autism spectrum disorders - Paula D. Prince; Martín G. Codagnone; Javier A. W. Opezzo; Juan S. Adán Areán; Christian Höcht; Nathalie Arnal; Silvia Alvarez; Sandra Zárate; Analía Reinés (Psychopharmacology, 2026)

Antimicrobial Armageddon: The Professional Guide to Conquering Antibiotic Resistance - Alissar AlJerf; Abdullah H. Maad; Prince O. Ukaogo; Loai Aljerf; Atem Bethel Ajong; Muaaz Alajlani (Probiotics and Antimicrobial Proteins, 2026)

Agro-waste amendments alleviate nickel stress: insights into growth, physiology, metabolites, bioaccumulation and health risk assessment in wheat under tropical ecosystems - Umesh Kumar; Prince Kumar Singh; Indrajeet Kumar; Rajesh Kumar Sharma (Physiology and Molecular Biology of Plants, 2026)

Long-term manuring influences boron availability in an Inceptisol under rice–wheat cropping system - Prince Kumar; Ruma Das; Dibyendu Sarkar; Mandira Barman; Abir Dey; Y. S. Shivay; Mayurakshi Chanda; Shrila Das; S. P. Datta (Nutrient Cycling in Agroecosystems, 2026)

Agro-Waste Biochar for Soil Restoration and Climate-resilient Crop Production: a Five-year Global Review - Mohamed Roshan Abu Firnass Mustaffa; Kannan Pandian; Shanmugam Vijayakumar; Sridevi Govindaraj; Manimaran Gajendiren; Surya Teja Varanasi; Abishek John Prince (Journal of Soil Science and Plant Nutrition, 2026)

Neuroprotective role of cyanidin in Alzheimer’s and Parkinson’s disease: current insights and the road ahead - Bushra Bashir; Nandani Andotra; Prince Sharma; Tripti Sharma; Smriti Chauhan; Ankit Awasthi; Shareen Singh; Thakur Gurjeet Singh; Sachin Kumar Singh; Sukriti Vishwas (Inflammopharmacology, 2026)

MLCK as a phosphorylation switch: from molecular structure to muscle function - Poushali Mitra; Rohit Singh; Prince Tiwari (Biophysical Reviews, 2026)

Hormonal Approaches for Enhancing Flowering Intensity and Fruit Set in Kola, Cola nitida (Vent.) Schott. & Endl. - Daniel Nyadanu; Samuel Tetteh Lowor; Prince Pobee; Wisdom Edem Anyomi; Jerome Agbesi Dogbatsey; Abraham Akpertey (Applied Fruit Science, 2026)

Groundwater quality assessment in Bihar's aquifers: a machine learning approach - Prince Kumar; Soumya Sucharita Singha; Sudhakar Singha (Environmental Science and Pollution Research, 2026)

Transglutaminase and its role in Alzheimer’s disease: focus on mitochondria, aging, defective mitophagy, synaptic degeneration, and metabolomics - Samson Prince Hiruthyaswamy; Dinesh Rao; Sreeja Balakrishna; Nazarene Marylene Nicky Macarius; Yukesh Kumar Sakthivel; Kanagavel Deepankumar; Murali Vijayan (GeroScience, 2026)

Nanotechnology in aflatoxin management: emerging tools for rapid detection and post-harvest control in grains - Sufail Parakkathodi; Prince Chawla; Mukul Kumar; Gulden Goksen; Deepika Kaushik; Aarti Bains (World Journal of Microbiology and Biotechnology, 2026)

Willingness to buy gene edited food in developing countries: Findings from India - Keshika Gajbhiye; Brainerd Prince; Abhishek Dureja; Navjot Kaur (Food and Humanity, 2026)

Exploring the Effect of Air Pollution on Corporate Social Responsibility: Insights from South Africa - Jean Baptiste Bernard Pea-Assounga; Hongxing Yao; Dalia Ayme Opoko Apendi; Prince Dorian Rivel Bambi (Water, Air, & Soil Pollution, 2026)

Modelling the impact of climate variability on rainfed Aus Rice (BR-26) using DSSAT in different agroecological zones of Bangladesh - Md Monirul Haque Prince; Sk. Thamidur Rhaman; Ferdouse Zaman Tanu; Rahatul Islam; Md. Saikat Hossen (Theoretical and Applied Climatology, 2026)

Cuminaldehyde, a natural monocyclic terpenoid, attenuates isoproterenol-induced myocardial infarction in rats via modulation of Bax/Bcl-2/Bcl-xL/Cyt.c/caspase- 9/caspase-3, and MMP-2/MMP-9 pathways - Shervin Prince Stanely; Reya Issac (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Occupational radiation exposure and cause-specific mortality in a cohort of Canadian medical workers - Mohammad Sazzad Hasan; Tim Prendergast; Philippe Prince; Minh T. Do; Paul A. Demers; Cheryl Peters; Lydia Zablotska; Paul J. Villeneuve (International Archives of Occupational and Environmental Health, 2026)

Evaluation of health risks associated with potentially toxic elements (PTEs) in urban public automobile parks soil dust in Northwest, Nigeria - Prince Onyedinma Ukaogo; Loai Aljerf; Ibrahim Imrana; Victoria Chinelo Onuorah; Oluebube Faith Ezenwafor; Victor C. Eze; Eziuche Amadike Ugbogu; Abiola Omotayo Oyebamiji; Chizoba Thelma Ukaogo (Environmental Geochemistry and Health, 2026)

Spatial analysis and hybrid machine learning prediction of forest fire susceptibility: a longitudinal appraisal synergy with physiographic division - Netrananda Sahu; Pritiranjan Das; Prince Gupta; Suraj Kumar Mallick; Rajiv Pandey; Xiaojun Wang; Manish Kumar; Ayush Varun; Ravi Kesharwani; Anil Kumar (Advances in Space Research, 2026)

Performance examination of anodic bioelectrochemical contributions in pyrite and graphite multi-anode–constructed wetland-microbial fuel cells under hydraulic and organic loads - Prince Atta Opoku; Huang Jingyu; Xu Shaowei (Environmental Science and Pollution Research, 2026)

Comparative life cycle assessment of dietary supplementation with protected organic acid and essential oils in swine production - Prince Agyemang; Ebenezer M. Kwofie; Ludovic Lahaye; Melissa Otis; Stephane Benaben; Glenmer Tactacan; Marcia de Souza Vieira; Olufemi Babatunde; Emilie Fontaine (Science of The Total Environment, 2026)

Transient hydrodynamic loading and cavity evolution during oblique water entry of a cylindrical body - Nishant Gupta; Prince Raj Lawrence Raj; Koustuv Debnath; Joydeep Bhowmik (Ocean Engineering, 2026)

Leveraging smart technologies to enhance safety in milk and milk-based products - Shubham Singh Patel; Aarti Bains; Ravinder Kaushik; Sanju Bhala Dhull; Rupak Nagraik; Mohammad Fareed; Sandeep Janghu; Prince Chawla (Food Control, 2026)

Exposure to low-dose ionizing radiation and dementia mortality in Canadian nuclear power plant workers - Brianna Frangione; Laura A. Rodriguez Villamizar; Ian Colman; Franco Momoli; Estelle Davesne; Lydia Zablotska; Cheryl E. Peters; Paul Demers; Minh Do; Tim Prendergast; Philippe Prince; Paul J. Villeneuve (Environmental Research, 2026)

Therapeutic potential of esculetin in attenuating kidney and heart damage caused by cyclophosphamide: insights into NRF2 activation and NLRP3 inhibition - Prathap Srirangan; Mukul Shyam; Vidya Radhakrishnan; Shankha Shubhra Ghosh; Sabina Evan Prince (Molecular & Cellular Toxicology, 2026)

Advances in the development of N-acylbenzo[d][1,2,3]diazaborinin-1(2H)-ols as antibacterial agents by synthesis, characterization, and antimicrobial assay - Chloe A. Woods; Betty Gutierrez; Naidine Aguinaldo; Prince Kanukwa; Yutong Li; Bethany Hubbard; Juan Daniel Avila; Anthony Jones; Fatime Sebok; Michael P. Groziak; Phattananawee Nalaoh; David M. Jenkins; et al. (Medicinal Chemistry Research, 2026)

Comparative evaluation of physio-hematological, antioxidant and hypoxia associated gene expression responses in cattle breeds adapted to hot semi-arid environment and cold Arid Trans-Himalayan region of Leh-Ladakh - Manish Tiwari; Monika Sodhi; Prince Vivek; Aman Jast; Saket K Niranjan; Ranjit S Kataria; Vijay K Bharti; Pawan Singh Dabbas; Amarjeet; Gayatri Gujar; Preeti Verma; Manishi Mukesh (International Journal of Biometeorology, 2026)

Evaluating MPA success for Caribbean reef fish: the role of design, habitat, and management - Christina Skinner; Kaylee R. F. Prince; Nicholas V. C. Polunin; Peter J. Mumby; Stacey M. Williams; Cristina Sánchez-Godínez; Charlie S. Dryden; Steven P. Newman (Coral Reefs, 2026)
Marine protected areas (MPAs) are essential tools for protecting marine ecosystems; yet, their effectiveness varies across regions. In the Caribbean, home to some of the world’s most degraded reefs, evaluating MPA performance requires consistent ecological data and information on management practices. To address this, we conducted standardised reef fish surveys of small (< 20 cm) and large (≥ 20 cm) fish across 83 sites in ten countries (32 MPA and 51 non-MPA sites) and interviewed MPA managers to assess compliance and enforcement. Across all sites, MPAs supported higher total biomass and species richness of small fish, but responses for herbivores, piscivores, and large fish groups were inconsistent. MPA sites in Jamaica and Saint Lucia showed significant biomass increases, while other sites showed minimal effects, highlighting the role of local ecological and socio-economic contexts. Both old and new MPAs had high total and herbivore biomass of large fish, suggesting that thoughtful site selection may enhance MPA effectiveness. Small to medium-sized MPAs (up to ~ 66 km 2 ) showed positive effects on total and herbivore biomass, while larger MPAs exhibited diminishing returns. For large fish, compliance and enforcement were critical drivers of higher biomass, outweighing MPA size, age, or benthic habitat characteristics, while increasing human population density negatively impacted biomass. For small fish, drivers of biomass were more variable, although MPA size emerged as a positive influence. These results emphasise the importance of enforcement, compliance, and careful MPA design in achieving ecological benefits; well-managed MPAs, regardless of size, can support coral reef fish communities.

Integrated biorefinery of Limnospira (Arthrospira) platensis: Recycling cultivation medium and biosorption of endocrine disruptors from water - Alenne Prince Junqueira de Moraes; Camylle Guimarães Scheliga; Yollanda Carolina da Silva Ferreira Vançato; Cláudia Maria Luz Lapa Teixeira; André Luís de Sá Salomão (Algal Research, 2026)

Evaluation of clinically approved neuroprotective drugs as adjunct therapies in experimental cerebral malaria - Prince Joshi; Salique Hassan Shaham; Rahul Shivahare; Kanchan Yadav; Anamika Sharma; Parul; Shubha Shukla; Renu Tripathi (Archives of Microbiology, 2026)

Response of Strawberry (Fragaria × ananassa Duch.) to Plant Density and Column Size in a Vertical Soilless Cultivation System - Vikas Kumar Sharma; A. K. Godara; Deepak Kaushik; Krishan Kant Meena; Sushil Sharma; Adesh Kumar; Arvind Malik; Prince (Applied Fruit Science, 2026)

Spatio-temporal analysis of Ghana’s ecological zones: integrating multispectral remote sensing and machine learning algorithms - Augustine O. K. N. Mensah; Bi Shuoben; Clement Kwang; Emmanuel Yeboah; Isaac Sarfo; Ebenezer Nikoi; Collins Oduro; Prince Martin Gyekye; Ishmeal Quist; Princella Ofori Darko; Clement Issaka Anaba; Asante Vincent Antwi (Environmental Monitoring and Assessment, 2026)

Views and experiences regarding workplace genetic testing: findings from a national survey of U.S. employees - Drew Blasco; Sarah McCain; Subhamoy Pal; Wendy R. Uhlmann; Rebecca Ferber; Kunal Sanghavi; Elizabeth Charnysh; Anya E.R. Prince; Charles Lee; J. Scott Roberts (Journal of Community Genetics, 2026)
The emergence of voluntary health-related genetic testing in workplace wellness programs indicates a need to understand employees’ views and experiences regarding workplace genetic testing (wGT). A large, diverse national sample of employed adults ( N =2000; median age=43 years; 51.1% female; 33% non-white) completed a web survey of their wGT views and experiences. Although 80% of participants indicated their employer did not offer wGT, 54.1% were interested in testing, especially (somewhat/very) for cancer (89.2%), heart disease (93.1%), and Alzheimer’s disease (85.3%). Characteristics associated with wGT interest included younger age (<55 years), Hispanic/Latino ethnicity, genetic testing experience or familiarity, and a positive family medical history (all p <0.05). Reasons for pursuing wGT (e.g., inform health behaviors) were endorsed more frequently than reasons for declining (e.g., insurance/employability concerns). Among participants offered wGT (20%), 60% indicated having undergone testing. Test uptake was associated with personal medical history, greater familiarity with genetic testing, and self-reported physical health (all p <0.05). A minority of employed adults surveyed reported being offered, or having had, wGT. Nevertheless, many employees are potentially interested in wGT, particularly for common diseases. Although employees have wGT concerns, many view it as beneficial to inform health behaviors and decisions.

Iron and Sulphur Cross Talk Regulates the Root System Architecture, Phytosiderophores Biosynthesis and Release and Expression of Fe-PS Transporter in Wheat - Vasundhara Sharma; Pradeep Kumar Jain; Prince Choyal; Pandurang Raghunath Divte; Vandna; Rakesh Kumar Prajapat; Bhupinder Singh (Agricultural Research, 2026)

The literature landscape on cities and climate change - Ayyoob Sharifi; Karen C. Seto; Prince Dacosta Aboagye (Urban Climate, 2026)

Investigating the use of dual-stage filtration system for E. coli removal in wastewater - Eric Eyram Kpodo; Prince Abeidu-Aidoo; Hosea Osabu; Benny Adu-Ampong; Evans Asenso; Peace Korshiwor Amoatey (Total Environment Advances, 2026)

A window into the early stages of aqueous alteration from mackinawite in samples of asteroid Bennu - M.C. Benner; T.J. Zega; B.S. Prince; Z.E. Wilbur; H.C. Connolly; D.S. Lauretta (Geochimica et Cosmochimica Acta, 2026)

Microwave-assisted production of underutilized moth bean (Vigna aconitifolia) protein concentrate: Influence of irradiation on protein extraction yield, physicochemical, functional, antioxidant, amino acid profile, and in-vitro digestibility - Nikhil Dnyaneshwar Patil; Ankur Kumar; Aarti Bains; Nazish Muzaffar; Prince Chawla; Nemat Ali (Food Bioscience, 2026)

Exploration of genetic diversity and population structure in North Indian Aegle marmelos accessions using ISSR markers - Prince Minhas; Rajvinder Minhas; Atul Chamyal; Rakesh Kumar; Kanika Aggarwal; Rahul Kumar; Maneet Rana; Vikas Sharma (Ecological Genetics and Genomics, 2026)

Correction to: Hydrothermal Synthesis and Photocatalytic Performance of CQDs/TiO₂ Nanocomposites for CIP Removal - Qurtulen Qurtulen; Asrar Ahmad; Mohammad Mujahid; Omar Al‑Hartomy; Prince Mufti Ziaul Hasan (Water, Air, & Soil Pollution, 2026)

Exploring the Length-Weight Relationships and Well-being of 15 Commercially Important Threadfin Breams (Family: Nemipteridae) From the Southeast Coromandel Coast, Tamil Nadu, India - Sasikumar. R.G; Santhoshkumar. S; Pavinkumar. P; Paplin Prince. B; Joyson Paul. J; Sharumathi. M; Nandhakumar. M (Thalassas: An International Journal of Marine Sciences, 2026)

Wave climate variability along the selected erosional hotspots of Kerala - Prince Arayakandy; P G Remya; Meenakshi Sreejith; Phiros Shah; Ratheesh Ramakrishnan; B Praveen Kumar; Alfred Johny; T M Balakrishnan Nair (Ocean Dynamics, 2026)

Gut microbiota at the crossroads of food additives, pollutants, and chronic disease risk - Esther Ugo Alum; Basil Uchechukwu Nwali; Ugonna Cassandra Aniokete; Akunna Perpetua Emeruwa; David Chukwu Obasi; Prince Nkemakolam Okoroh; Ada Ak. Akwari; Olisa Alfred Nwuruku; Edwin Nzubechukwu; Patrick Maduabuchi Aja (Toxicology and Environmental Health Sciences, 2026)

Seaweed as a functional feed additive in aquaculture: Efficacy, safety, and fish species-specific optimization - Sahr Lamin Sumana; Gnoumasse Sidibe; Ahmed E. Elshafey; Damien Habinshuti; Agnes Mattia; Jusu Massaquoi; Sheku Tarawallie; Mukhtar Muhammad Abdullateef; Abubakar Shuaibu; Prince Tongor Mabey; Amidu Mansaray; Yang Xiaofei; et al. (Algal Research, 2026)

Insights into the human metabolism and in silico receptor activity of gidazepam and desalkylgidazepam - Prince Sellase Gameli; Johannes Kutzler; Cristina Minnelli; Giuseppe Basile; Emiliano Laudadio; Francesco Paolo Busardò; Volker Auwärter; Jeremy Carlier (Archives of Toxicology, 2026)
Desalkylgidazepam, an active gidazepam metabolite, first appeared on the illicit drug market in 2022 and has been detected in polydrug intoxication cases. Since both benzodiazepines and their metabolites can result from gidazepam metabolism, it is important to identify markers that specifically indicate consumption of each compound. We therefore investigated the human metabolism of gidazepam and desalkylgidazepam by incubating them with human hepatocytes and analyzing the resulting samples, along with human blood from a confirmed desalkylgidazepam-positive case, using liquid chromatography-high-resolution mass spectrometry. To further assess their pharmacological profile, we examined the activity of gidazepam, desalkylgidazepam, and their potential (3 R )- and (3 S )-hydroxy metabolites at γ-aminobutyric acid A (GABA A R) and 18 kDa translocator protein (TSPO) receptors in silico, using AutoDock Tools and UCSF Chimera. Gidazepam was metabolized through N -desalkylation (yielding desalkylgidazepam), N -acetylation, and N -glucuronidation. Conversely, desalkylgidazepam was subjected to hydroxylation and subsequent O -glucuronidation reactions. Notably, gidazepam demonstrated a lower affinity at GABA A R’s prominent α 1 /γ 2 site compared to desalkylgidazepam and its (3 R )- and (3 S )-hydroxy metabolites. However, its interaction with the transmembrane domains of the α 1 β 2 subunit may account for its anxiolytic effects. For the TSPO receptor, gidazepam and 3-hydroxy desalkylgidazepam metabolites showed higher binding affinity, whereas desalkylgidazepam did not bind to TSPO. Our findings suggest blood markers specific to gidazepam, namely gidazepam- N -glucuronide and N -acetyl gidazepam, are essential for confirming gidazepam consumption. In addition, in silico modelling supports the hypothesis that gidazepam functions as a prodrug via GABA A R and as an agonist at TSPO. Further research is necessary to clarify designer benzodiazepine activity at TSPO.

Environmental policy stringency, renewable energy consumption, and load capacity factor in BRICS countries: a bootstrap rolling-window approach - Solomon Prince Nathaniel; Muhammad Saeed Meo; Olajide O. Oyadeyi; Chikaodili Josephine Solomon (Environment, Development and Sustainability, 2026)

Distinguishing social and medical traits: perspectives of scientists using polygenic scores - Margaret Waltz; Karen M. Meagher; Courtney Canter; Matthew Kucmanic; Kristine J. Kuczynski; Anya E. R. Prince; R. Jean Cadigan (Journal of Community Genetics, 2026)
Polygenic scores (PGS) have been developed for a wide variety of traits, such as cancer, risk tolerance, obesity, asthma, educational attainment, and cardiovascular disease. Prior research shows that the public tends to view the use of genetic information for medical traits more favorably than for social or other non-medical traits, and legal and policy discourse regularly treats medical and social traits as distinct categories. However, distinguishing between social and medical traits can be conceptually and practically challenging. Drawing on 47 semi-structured interviews with researchers who have developed or utilized PGS across a range of traits, this study examines how scientists discussed and conceptualized a dividing line between what is medical and what is social, as well as the perceived necessity of a medical/social divide. Overall, the scientists we interviewed broadly agreed that the line is ambiguous; they did not hold unequivocal views about what constitutes a social versus a medical trait, nor where a clear line might be drawn. Instead, they reasoned through any distinctions between social and medical traits in varied and sometimes conflicting ways, including attempting to draw the line, highlighting the role of social context in drawing the line, questioning the line’s relevance, and pointing to the line’s policy implications. We argue that this ambiguity has significant implications for how PGS research is conducted, interpreted, and regulated, calling for a reexamination of regulatory strategies that rely on this distinction.

Pollution and health risk assessment of drinking water sources within artisanal and small-scale gold mining areas: a case of Asankrangwa District in Ghana - Eric Danso-Boateng; Ebenezer Adom; Prince Appiah Owusu; Roland Songotu Kabange (Environmental Science and Pollution Research, 2026)
Artisanal and small-scale gold mining (ASGM) is common in many developing countries; while it contributes to their socio-economic development, it also causes environmental pollution. This study examined the impact of ASGM activities on the quality of drinking water sources in the Asankrangwa District in Ghana, in terms of water quality index, heavy metal pollution index models, and human health risks. The results of physicochemical parameters indicate that 40.0% of all water sources are unsuitable for consumption. Heavy metal pollution indices indicated that 45.0% of the water sources were extremely polluted, and 25.0% were moderately polluted. For instance, cadmium (Cd) concentrations across all water sources reached levels up to 23 times the WHO limit (3.0 × 10 –3 mg/L). Additionally, mercury (Hg) concentrations in 75.0% of the water sources (2.0 × 10 –3 –7.2 × 10 –1 mg/L) exceed the maximum contaminant limit (2.0 × 10 –3 mg/L) by approximately 361 times. Streams, in particular, exhibit higher Hg levels than groundwaters. Analysis revealed that 90% of the water sources pose a significant carcinogenic health risk upon consumption, with lifetime cancer risk values exceeding 1.0 × 10 −4 . The findings revealed that the pollution level is reduced and water quality improved 5 km from the ASGM sites; however, the water sources require treatment to render them suitable for consumption.

Non-cognitive skills and willingness to participate in drought index crop insurance in Ghana - Edward Martey; John K. M. Kuwornu; Francis H. Kemeze; Prince M. Etwire; Emmanuel K. Apiors; Mario J. Miranda (Climate and Development, 2026)

Identifying conflicts and sectoral dynamics prior to marine spatial planning: A case study of Bhola and Hatia, two coastal islands of Bangladesh - K M Azam Chowdhury; Alif Mohammad Khan; Shahriar Khosnoor Prince; Kawser Ahmed (Marine Policy, 2026)

Recent advances in cellulose-based aerogels for meat packaging: Fabrication, modifications, functionality, and preservation mechanisms - Mansuri M. Tosif; Oscar Zannou; Aleksandra Purkiewicz; Prince Chawla; Gulden Goksen (Trends in Food Science & Technology, 2026)

Toward urban wetland sustainability – a multivariate statistical analysis of encroachers' outlook - Akosua Baah Kwarteng Amaka-Otchere; Eric Oduro-Ofori; Otiwaa Boakye; Prince Boakye Frimpong; Kafui Ocloo; John Bosco Dramani (Science of The Total Environment, 2026)

Modeling growth for Gellapper sheep raised under arid extensive production system - Uaipo Ngorio; Clarice Princes Mudzengi; Tinotenda Nhovoro; Soul Washaya (Small Ruminant Research, 2026)

Soil–hydrology controls on groundwater microplastic contamination - S.B. Sumam; Sneha Gautam; Prince Arulraj (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Plant responses to sulfur nutrition and disease attack under climate change: Roles of sulfur and management strategies for wheat and barley - Simbo DIAKITE; Francess Sia SAQUEE; Nyasha John KAVHIZA; Elena Nikolaevna PAKINA; Prince Emmanuel NORMAN; Elena Mikhailovna CHUDINOVA; Archil Anzorovich TSINDELIANI; Inna Vladimirovna POTOTSKAYA (Pedosphere, 2026)

Entomopathogenic soil bacteria as biocontrol agents against Spodoptera litura (Fab): A sustainable approach - Pallvi Mehra; Arushi Mahajan; Prince Dhammi; Satish Koundal; Harvinder Singh Saini; Sanehdeep Kaur (Journal of Invertebrate Pathology, 2026)

Tetrabromobisphenol A (TBBPA) in e-waste and e-waste recycling/dismantling sites: Endocrine disruption, ecotoxicological and human health risks, remediation strategies, and policy recommendations - Emmanuel Sunday Okeke; Stephen Sunday Emmanuel; Timothy Prince Chidike Ezeorba; Adebisi Esther Enochoghene; Veronica Chisom Okeke; Chukwuebuka ThankGod Eze; Weiwei Feng; Guanghua Mao; Yao Chen; Xiangyang Wu (Journal of Environmental Chemical Engineering, 2026)

The impact of drying-induced gelatinization on texture and rehydration capacity of starchy foods; a critical consideration for attaining zero hunger - Yasmine Bouhile; Emeka Godwin Anaduaka; Timothy Prince Chidike Ezeorba; Stephen Sunday Emmanuel; Charles Ogugua Nwuche; Emmanuel Sunday Okeke; Chidiebele Emmanuel Ikechukwu Nwankwo (Food Research International, 2026)

Community water resource and energy poverty in Ghana - Edward Martey; Prince M. Etwire; Frank Adusah-Poku; Kwabena Krah; Mustapha M. Suraj (Energy Policy, 2026)

Electrochemical performance of titanium (Ti), antimony-doped tin oxide on titanium (NiATOTi) and platinum- antimony-doped tin oxide on titanium (NiATOTiPt) anodes in closed loop flow wastewater treatment - Navneet Yadav; Sina Younesi; Ibrahim Prince Tholley; Richard E. Palmer; Chedly Tizaoui (Chemical Engineering Journal, 2026)

Synergistic solvation and proton coupling reduce diffusion barriers in MoS2 cathodes for high-capacity Zn2+ proton hybrid batteries - Muruganandham Hariram; Prince Sharma; Vahid Attari; Prashant Singh; Debasish Sarkar (Chemical Engineering Journal, 2026)

Hydrothermal Synthesis and Photocatalytic Performance of CQDs/TiO₂ Nanocomposites for CIP Removal - Qurtulen Qurtulen; Asrar Ahmad; Mohammad Mujahid; Omar Al-Hartomy; Prince Mufti Ziaul Hasan (Water, Air, & Soil Pollution, 2026)

Residential indoor and outdoor exposure to VOCs and NO2: insights from a multi-city pilot study in India - Prince Vijay; Akshay Kumar; Shreya Dubey; Rajdeep Singh; Vinayak Sahota; Sonali Borse; Harish C. Phuleria (Environmental Geochemistry and Health, 2026)

Fluctuations in Ecosystem Services in Response to Land Conversion and Climate Extremes as an Index of Ecosystem Degradation and Restoration: A Comparison of the Lake Chad and Aral Sea Basins - Emeka Edwin Igboeli; Chukwuka Prince Ogbue; Friday Uchenna Ochege; Muhammad Afzal; Rafiq Hamdi; Albert Poponi Maniraho; Geping Luo (Ecosystems, 2026)

Unified Phenological Characterization of Fruit Crops Using the Extended BBCH Scale - Aman Kumar; Akshay Mehta; Vikas Kumar Sharma; Sushil Sharma; Pravin Kumar Sharma; Prince (Applied Fruit Science, 2026)

The aging gut–glia–immune axis in alzheimer’s disease: microbiome-derived mediators of neuroinflammation and therapeutic innovation - Prince Ahad Mir; Nishant Kumar; Gyamcho Tshering Bhutia; Preeti Chaudhary; Gurkiran Kaur; Sukesh Kumar Gupta (GeroScience, 2026)

Exploring synergistic contamination of heavy metals and microplastics in marine edible fishes and associated risk status in humans - Prince Upadhyay; Vyomil Patel; Tejas Gurjar; Rahul Ladumor; Monisha Kottayi; Ankita Doshi; Ankita Salunke; Parth Pandya (Marine Pollution Bulletin, 2026)

Reduced translational activity is associated with early-stage muscle growth retardation in big-eye mandarin fish (Siniperca kneri) - Xiaoli Yao; Jia Zheng; Xiaojun Yang; Prince Yeboah; Yan Zhao; Shoujie Tang; Jinliang Zhao (Aquaculture, 2026)

Effect of Reynolds number and wave frequency on particle trajectories and orbital patterns for wave-current interaction - Debayan Bera; Sourav Sarkar; Koustuv Debnath; Prince Raj Lawrence Raj (Ocean Engineering, 2026)

Green gains: the development of next-generation dairy feed additives through a multidimensional sustainability lens - Prince Agyemang; Ebenezer M. Kwofie; Ludovic Lahaye; Melissa Otis; Emilie Fontaine; Aubin Payne; Greg Thoma (Journal of Environmental Management, 2026)

Urban climate action planning case studies: A review of trends, approaches, and reported barriers and drivers - Prince Dacosta Aboagye; Ayyoob Sharifi (Journal of Environmental Management, 2026)

Synergistic green synthesis of rice husk-derived carbon quantum dots for dual function detection of micro plasticizer (dimethyl phthalate) and photocatalytic dye degradation: A sustainable approach - Sweezee Thakur; Glowi Alasiri; Aarti Bains; Rupak Nagraik; Ali M. Alaseem; Mohammad Fareed; Prince Chawla (Food Bioscience, 2026)

Development of a visual assay for Mithun (Bos frontalis) meat authentication using polymerase spiral reaction (PSR) - Moon Moon Mech; Hanumant Singh Rathore; Arockiasamy Arun Prince Milton; Nagappa Karabasanavar; Kandhan Srinivas; Sabia Khan; Zakir Hussain; Vikram Ramesh; Harshit Kumar; Samir Das; Sandeep Ghatak; Girish Patil Shivanagowda (Food Control, 2026)

Climate-smart agriculture: analysis of the determinants of adoption intensity of sustainable agronomic practices among mango farmers in the Yilo Krobo Municipality of Eastern Region of Ghana - Kwaku Adu; Kwame B. Bour; Adwoa Oforiwaa Antwi; Prince Pobee; Frank Gyimah Sackey (Climate and Development, 2026)

Chondrogenic Differentiation of Stem Cells for Cartilage Regeneration: Advances and Future Perspectives - Ahmed Abdal Dayem; Abdelbary Prince; Ahmed M. M. Gabr (Tissue Engineering and Regenerative Medicine, 2026)

Evaluation of the near-surface wind products from reanalyses over the North-Western Indian Ocean - Akhil Varghese; Phiros Shah; Akash S; Athuldev A V; Prince Arayakandy; Muhammad Shafeeque; Sruthi Thalayappil R S (Ocean Dynamics, 2026)

The Neuroimmune Duality of CD4⁺ T Cells: Drivers of Damage and Repair in the Brain - Nishant Kumar; Prince Ahad Mir; Gyamcho Tshering Bhutia; Jasreen Uppal; Anureet Kaur; Gurkiran Kaur; Sukesh Kumar Gupta (Molecular Neurobiology, 2026)

PIWI–piRNA Axis in Epilepsy: Bridging Epigenetic Regulation, Neuroinflammation, and Neuronal Excitability - Mukul Shyam; Rashmi Rashmi; Vidhi Sharma; Rajendran Venkatesh; Aditi Jain; Yaazhini G; Abilash Valsala Gopalakrishnan; Prathap Srirangan; Sabina Evan Prince (Molecular Neurobiology, 2026)

Reprogramming Neuroinflammation: Mitochondrial Targets and Immune Checkpoint Inhibitors in Alzheimer’s Disease - Nishant Kumar; Prince Ahad Mir; Gyamcho Tshering Bhutia; Preeti Chaudhary; Gurkiran Kaur; Qadir Alam; Sharad Daulatrao Pawar; Sukesh Kumar Gupta (Molecular Neurobiology, 2026)

Autologous Neural Stem Cell Encapsulation in CT04-Integrated Fibrin Hydrogel Enhances Tissue Regeneration After Spinal Cord Injury in Monkeys - Razieh Jaberi; Prince David Okoro; Mostafa Hajinasrollah; Masoumeh Zarei Kheirabadi; Sara Mirsadeghi; Saeid Rahmani; Zahra Nazemi; Firas Kobeissy; Sahar Kiani (Molecular Neurobiology, 2026)

Estimating transpiration dynamics of a low-density litchi orchard using crop coefficients derived from a variable leaf conductance model, canopy cover, and tree height in Northeastern South Africa - Prince Dangare; Paul J. R. Cronje; Zama E. Mashimbye; Tendai Sawunyama; Joseph Masanganise; Zanele Ntshidi; George P. Nel; Sebinasi Dzikiti (Irrigation Science, 2026)

In vivo and in vitro metabolism of the designer benzodiazepine, bretazenil: a comparison of pooled human hepatocytes and liver microsomes with postmortem urine and blood samples - Prince S. Gameli; Johannes Kutzler; Laura M. Huppertz; Diletta Berardinelli; Livio Tronconi; Giuseppe Basile; Jeremy Carlier; Francesco P. Busardò; Volker Auwärter (Archives of Toxicology, 2026)
Benzodiazepines are often used with other drugs like opioids, potentially leading to severe intoxications. Bretazenil, an imidazo-tetrahydropyrrolo-1,4-benzodiazepine, developed in the 1980s but never marketed as a medicine, has recently appeared on the illicit drug market. Given its high potency, short elimination half-life, and potential for rapid metabolism, it is essential to identify markers for bretazenil consumption for clinical and forensic purposes. Our study aimed to thoroughly explore bretazenil’s metabolism using web-based in silico prediction tools, in vitro incubation with pooled human liver microsomes and hepatocytes, and to compare these results with authentic postmortem blood and urine samples. The in silico prediction revealed 16 metabolites, mainly formed by hydroxylation (phase I) and further O -glucuronidation, sulfation, and methylation (phase II) reactions. High-resolution mass spectrometry and software-aided data processing of in vitro and in vivo samples identified a total of 26 metabolites. Eight metabolites were detected in vitro, 15 in postmortem urine, and 11 in postmortem blood. Hydroxylation on the pyrrolidine ring was predominant. Other phase I reactions, including combinations of dihydroxylation, hydroxylation, reduction, and carboxylation as well as phase II glucuronidation and sulfation on the pyrrolidine ring, imidazole ring, or the tert -butyl chain, were also identified. Additionally, we discovered a new benzodiazepine biotransformation pathway via hydroxylation and cysteine conjugation in both human hepatocytes and blood. Due to bretazenil’s extensive metabolism, we recommend hydroxy-bretazenil (B14), reduced hydroxy-bretazenil (B6), and reduced dihydroxy-bretazenil (B1) as significant markers for detecting bretazenil use.

Modelling the number of shade tree species needed to reach the optimal canopy target in cocoa agroforestry systems - George Ashiagbor; Isaac Stanisluv Essah; Prince Paa Kwesi Baiden; Abigail A. Adjetey Bisa; Ophelia Ahorlu; Gideon Enyinful-Andoh; Winston Adams Asante; Edward Yeboah; James Mutegi; Esther Mugi-Ngenga; Kokou Adambounou Amouzou; Thomas Oberthür (Agroforestry Systems, 2026)

Decadal dynamics of urban heat Islands in a coastal industrial region of india: remote sensing insights for sustainable urban planning - C Antony Zacharias Grace; John Prince Soundranayagam; Neelam Sidhu; Sahil Sharma; Ernest Amita Roy; V Stephen Pitchaimani; A Antony Alosanai Promilton (Environment, Development and Sustainability, 2025)

Energetics of intense substorms of solar cycle 23 - Devi R. Nair; P. R. Prince (Acta Geophysica, 2025)

Exploring the intricacies of indoor dust pollution from neonicotinoid insecticides and its human health impacts: An exemplar from eleven agricultural communities in Ghana, West Africa - Collins NIMAKO; Osei AKOTO; Nathaniel BOADI; Prince OFORI; Yared B. YOHANNES; Shouta M.M. NAKAYAMA; Yoshinori IKENAKA; Mayumi ISHIZUKA (Journal of Hazardous Materials, 2025)

The nexuses of micro(nano)plastics at environmental interfaces: Challenges in wastewater treatment and sustainable water management - Bienvenu Gael Fouda-Mbanga; Bothwell Nyoni; Jabulani I. Mnyango; Calvin Phiri; Shanganyane P. Hlangothi; Aliemeke Miracle; Ayeni Boluwatife; Olushuyi Celestina; Sonia Nadege Kenfack Voukeng; Chimaine Feudjio Tsague; Linda Dyorisse Nyamen; Petrus Pennie Mokolokolo; et al. (Journal of Environmental Chemical Engineering, 2025)

Microbial driven iron mineral transformation and its role in pollutant migration and transformation: A critical review - Varney Edwin Johnson; Bob Wisdom Jallawide; Richmond Anaman; Thomas Tmath Tarpeh; Kermue Vasco Jarnda; Blessing Sunday; Marklyn Weata Wingbah; James Prince Abeeku Tarley; Kejing Zhang; Yan Shi (Journal of Environmental Chemical Engineering, 2025)

Restoration of abandoned artisanal mining sites: Effects of biophilia and ecoguilt - Adams Osman; Addae Boateng Adu-Gyamfi; Benedict Arko; Prince Boateng; Ebenezer Oppong Osei; Henry Kwaku Gyambibi; Abdul Manan Kalifa (Journal for Nature Conservation, 2025)

Immobilized pigeon pea urease on chitosan-PEG biocomposite for concurrent urea sensing in milk and blood samples - Prince Kumar; Aditya Ghosal; Arvind M. Kayastha (Food Chemistry, 2025)

CMC-regulated multi-chamber formation contributes to the texture of deep-fried batter-coated meat strips: multiple visual evaluation collaborative water/oil migration analysis - Ying Xu; Ruishu Zhang; Ping Yang; Laiyu Zhao; Xiaojia Hu; Wenjing Mai; Prince Chisoro; Feng Huang; Chunhui Zhang (Food Hydrocolloids, 2025)

From grain to Gain: Bridging conventional methods with chemometric innovations in cereal quality analysis through near-infrared spectroscopy (NIRS) - Maharishi Tomar; Rakesh Bhardwaj; Prabha Singh; Simardeep Kaur; Sumer Pal Singh; Anil Dahuja; Veda Krishnan; Rekha Kansal; Vijay Kumar Yadav; Racheal John; Awnindra Kumar Singh; Pankaj Kaushal; et al. (Food Control, 2025)

Effect of NaCl pretreatment and frying conditions on the physico-chemical and sensory properties of potato peel chips - Md. Abdul Alim; Amartya Kumar Das; Md. Akib Al-Asad; Md Al Shahriar Prince; Md. Tarakul Islam; Rukaiya Zaman; Md. Momin Khan (Food and Humanity, 2025)

Spirogyra derived CuO-NPs with antibacterial, heavy metal adsorption, and photocatalytic dye degradation: A sustainable approach in environmental remediation - Samriti Guleria; Aparajita Bhasin; Prince Chawla; Vinay Kumar Dhiman; Prashant Anil Pawase; Halis Simsek (Environmental Nanotechnology, Monitoring & Management, 2025)

Ultrafast CO2 sorption in sol-gel lithium zincate: Rapid kinetics and sequential sorption dynamics - R. Achu; Devika Surendran; Prince George; Atly Pauly; A. Peer Mohamed; Balagopal N. Nair; U.S. Hareesh (Chemical Engineering Journal, 2025)

First report of lumpy skin disease and foot-and-mouth disease co-infection in India - Kandhan Srinivas; Samir Das; Sabia Khan; Pebam Chandrima Devi; Sandeep Ghatak; Arockiasamy Arun Prince Milton (Molecular Biology Reports, 2025)

Phytochemicals as modulators of ferroptosis: a novel therapeutic avenue in cancer and neurodegeneration - Esther Ugo Alum; Ada Ak. Akwari; Prince Nkemakolam Okoroh; Ugonna Cassandra Aniokete; Jacinta Nnennaya Abba; Daniel Ejim Uti (Molecular Biology Reports, 2025)

Diabetic retinopathy: a comprehensive review of pathophysiology and emerging treatments - Mukul Shyam; S. Sidharth; Aleen Veronica; Lakshmipriya Jagannathan; Prathap Srirangan; Vidya Radhakrishnan; Evan Prince Sabina (Molecular Biology Reports, 2025)

Targeted miRNA Delivery in Epilepsy: Mechanisms, Advances, and Therapeutic Potential - Mukul Shyam; Oveyaa BM; Prathap Srirangan; Nivedita N; Evan Prince Sabina (Molecular Biology Reports, 2025)

NLRP3 as a therapeutic target in cyclophosphamide-associated toxicities - Prathap Srirangan; Mukul Shyam; Vidya Radhakrishnan; Sabina Evan Prince (Molecular Biology Reports, 2025)

Emergence of virulent, multidrug-resistant, and genetically diverse Aeromonas hydrophila in foods of animal and aquatic origin from tribal regions of Northeastern India - Kandhan Srinivas; Arockiasamy Arun Prince Milton; G. Bhuvana Priya; Heiborkie Shilla; Lavinia Wahlang; Kasanchi M. Momin; Dadimi Bhargavi; Vanita Lyngdoh; John Pynhun Lamare; Zakir Hussain; Girish PS; Sandeep Ghatak; et al. (Brazilian Journal of Microbiology, 2025)

Nickel Contamination in Terrestrial Ecosystems: Insights into Impacts, Phytotoxicity Mechanisms, and Remediation Technologies - Umesh Kumar; Indrajeet Kumar; Prince Kumar Singh; Akanksha Dwivedi; Priyanka Singh; Saumya Mishra; Chandra Shekhar Seth; Rajesh Kumar Sharma (Reviews of Environmental Contamination and Toxicology, 2025)

Decoding India’s struggle for energy trilemma balance: a mixed-method approach using machine learning and AHP - Pratyush Kumar Patro; Enoch Quaye; Timileyin Aworinde; Prince Aduama; Adolf Acquaye (Environment, Development and Sustainability, 2025)

A novel size-based method for assessing the spawning potential ratio of data-poor octopus fisheries - Jeremy D. Prince; Indah Rufiati; Wahyu Dita Septiani; Duranta Diandria Kembaren; Charlotte Louise Anne Gough (Frontiers in Marine Science, 2025)
Cephalopod biology, which is characaterised by short lifespans, semelparous reproduction, rapid non-asymptotic growth, and seasonally fluctuating biomass, presents a particular challenge stock assessment. Small scale, data-poor artisanal octopus fisheries are an increasingly important source of food and income for coastal fishing communities but pose a particularly pernicious assessment challenge. We developed and tested a novel size-based data-poor assessment methodology, demonstrating its applicability with 17 Indonesian fisheries for Octopus cyanea . The Short-Lived Assessment Model (SLAM) is similar to Length-based Spawning Potential Ratio Assessment (LBSPR) and Length-based Integrated Mixed Effects (LIME) methodologies, in assuming that taxa share both growth curves and a relativity between maximum size and size of maturity. Incorporating a power curve form of growth typical of cephalopods and monthly time steps SLAM estimates selectivity at age schedules, monthly fishing mortality rates (F) and spawning potential ratio (SPR). A minimum of 12 monthly samples of catch at weight data (CAW) are required, but longer time series and additional indices of effort and/or catch will produce more reliable results. SLAM’s structure is flexible; with <24 months of CAW it parallels LBSPR in assuming equilibrium dynamics and constant monthly recruitment. With >24 months of CAW, a dynamic structure becomes possible similar to LIME, and seasonal recruitment patterns can be estimated.

Advances in oleogel technology for sustainable and intelligent food packaging strategies - Madhu Sharma; Aarti Bains; Rupak Nagraik; Mohammad Fareed; Prince Chawla (Trends in Food Science & Technology, 2025)

Morpho-cultural and phylogenomic characterization of Fusarium proliferatum causing strawberry wilt: First report from India - Adesh Kumar; Shubham Saini; Anil Kumar Saini; Roomi Rawal; Rakesh Kumar; K.C. Rajeshkumar; Sushil Sharma; Vikas Kumar Sharma; Yogesh Kumar; Raj Pal Singh Dalal; Prince; Indu Arora; et al. (Physiological and Molecular Plant Pathology, 2025)

Integrating life cycle assessment and systemic circularity indicators for circular economy decision making: A case study of a conventional commercial building in Nigeria - Benjamin I. Oluleye; Daniel W.M. Chan; Prince Antwi-Afari (Journal of Cleaner Production, 2025)

Exploring plant-based approaches: A review of protein extraction, characterization, food and pharmacological application from fruit pulps - Riya Phogat; Aarti Bains; Gulden Goksen; Sanju Bala Dhull; Nemat Ali; Rupak Nagraik; Mohammad Fareed; Prince Chawla (Food Chemistry, 2025)

Top ten super-adsorbents for removal of textile dyes from wastewater - M.A. Gabris; Aravin Prince Periyasamy; Ali Tehrani-Bagha (Environmental Research, 2025)

Theranostic covalent organic frameworks for biosensing and targeted drug delivery - Wilson Dumisani Gamuchirai Dube; Theophilus Ngong Gha ajem; Prince Nicholas Yarh; Wishes Tatenda Machoko; Yaoyao Wang; Dan Wang; Tatenda Chimbunde; Xue Tang; Zhao Linjie; Deli Xiao; Pierre Dramou (Chemical Engineering Journal, 2025)

Heavy Metal Analysis of Commercial Rice Grains from Varanasi City of India: Insight into Contamination Level, Daily Intake and Associated Health Risks - Priyanka Singh; Rajesh Kumar Sharma; Prince Kumar Singh (Biological Trace Element Research, 2025)

Global analysis of nutritional strategies to mitigate the environmental impacts of dairy production: the case of supplementing diets with microencapsulated B vitamins - Prince Agyemang; Ebenezer M. Kwofie; Ludovic Lahaye; Melissa Otis; Emilie Fontaine; Victoria Asselstine; Aubin Payne; Greg Thoma (Sustainable Production and Consumption, 2025)

Assessing the impact of small-scale mining activities on land use land cover and the sustainability of mining practices in Ghana: A case of the Atiwa East district - Samuel Kofi Mensah; Emmanuel Kwesi Nyantakyi; Gifty Serwaa Mensah; Ebenezer K. Siabi; Nana Osei Bonsu Ackerson; Prince Antwi-Agyei; Peter Donkor; Sarah Elikplim Siabi (Resources Policy, 2025)

Isolation and characterization of antimicrobial compounds from Picralima nitida (Apocynaceae) - Makafui Adzo Gbemu; Susana Dufie Boatey; Denick Amon; Prince Okyere Dagadu; Priscilla Kolibea Mante; Yaw Duah Boakye; Edmund Ekuadzi (Phytochemistry Letters, 2025)

Impact of Volunteer Support on an Inpatient Hospital Feeding Assistance Program: Trends, Challenges, and Resource Optimization - E. Muradyan; P. Hain; M. Prince; F. Ramezani; E. Burke; N. Maharaj (Journal of the Academy of Nutrition and Dietetics, 2025)

Potentially toxic elements in flooded-gold-mine fields: compost stabilises Cd, biochar and manure mobilize As and Pb - Albert Kobina Mensah; Ephraim Sekyi-Annan; Sadick Adams; Harry Okyere; Fuseini Issaka; Prince Charles Asante; Haruna Gado Yakubu; Collins Korbla Tay (Journal of Hazardous Materials, 2025)

Water–oil displacement in prefried potatoes during freezing–thawing and reheating: A simulation of the industrial prepared dishes supply chain - Hengxun Lin; Liye Cui; Meisui Tian; Wenqiang Guan; Prince Chisoro; Xia Li; Yiping Yang; Yong Chen; Xiangning Chen; Christophe Blecker; Chunhui Zhang (Food Chemistry, 2025)

Ambient environmental conditions and active outdoor play in the context of climate change: A systematic review and meta-synthesis - Eun-Young Lee; Seiyeong Park; Yeong-Bae Kim; Henry Liu; Priya Mistry; Kevin Nguyen; Yeonjae Oh; Maeghan E. James; Steven Lâm; Louise de Lannoy; Richard Larouche; Taru Manyanga; et al. (Environmental Research, 2025)

Energy-efficient multi-stage reverse osmosis modules: A viable competitor to centrifugal reverse osmosis? - Hasib Ahmed Prince; Mustafa Usta; Cosan Daskiran (Desalination, 2025)

Environmental Biomonitoring of Heavy Metal and Microplastic Contamination in Mahi River Unveils Increased Risk to Edible Fish and Humans - Prince Upadhyay; Rahul Ladumor; Vyomil Patel; Tejas Gurjar; Monisha Kottayi; Ankita Doshi; Parth Pandya (Water, Air, & Soil Pollution, 2025)

Salidroside and inflammation-linked disorders: integrative insights into the pharmacological effects and mechanistic targets - M. V. N. L. Chaitanya; Deepshikha Patle; Sachin Kumar Singh; Avijit Mazumder; Rakesh Kumar Sindhu; Kamal Dua; Navneet Khurana; Prince Arora (Inflammopharmacology, 2025)

A Review on Integrating the Circular Economy in Diabetic Appliances Manufacture and Management for Sustainable Healthcare - Shubham Singh Patel; Aarti Bains; Nemat Ali; Prince Chawla (Circular Economy and Sustainability, 2025)

Smart technologies in aquaculture: An integrated IoT, AI, and blockchain framework for sustainable growth - Prince Jebedass Isaac Chandran; Hana Ahmed Khalil; PK Hashir; Veerasingam S (Aquacultural Engineering, 2025)

Intra- and inter-urban variability in chemical characteristics of residential outdoor PM2.5 in Indian metropolitan cities - Prince Vijay; Harish C. Phuleria (Environmental Science and Pollution Research, 2025)

Optimization on the performance parameters of micro- and nanostructured mollusc gastropod seashell waste as reflector for bifacial photovoltaic module by central composite design-based response surface methodology - Suriya Kala Shakthivel; Prince Winston David; Gurukarthik babu Balachandran; Hariharasudhan Thangaraj (Environmental Science and Pollution Research, 2025)

Impact of below-freezing air temperatures on the formation and stability of seawater-crude oil emulsion - Jianyun Li; Wen Ji; Roger C. Prince; Kenneth Lee; W. Scott Pegau; Michel Boufadel (Marine Pollution Bulletin, 2025)

Upcycling spodumene tailings and waste glass in ceramic tiles production: Effect of particle size fractionation and sintering temperature on the properties - Adeolu Adediran; Nana Asaam; Prince Allah; Pekka Tanskanen; Priyadharshini Perumal (Process Safety and Environmental Protection, 2025)

A review on exploring the emerging role of novel transdermal gel drug delivery systems for skin diseases - Prince Nikhil Rathore; Anirban Pal; Sakshi Pandey; Sayani Maji; Alpana Ram (Next Research, 2025)

Impact of Volunteer Support on an Inpatient Hospital Feeding Assistance Program - E. Muradyan; P. Hain; M. Prince; F. Ramezani; E. Burke (Journal of the Academy of Nutrition and Dietetics, 2025)

Interleukin-6-taregeted dual-drug nanoparticles enhance glioblastoma chemotherapy by facilitating blood-brain barrier penetration and alleviating cardiotoxicity - Zesheng Sun; Jialiang Lin; Yue Huang; Qianqian Liu; Xucheng Zhu; Yu Yang; Ya Wen; Chunbin Shao; Weiquan Liao; Yan Song; Sharon Prince; Yi Wang; et al. (Chemical Engineering Journal, 2025)

Dating multiple fractionation trends in pegmatites – Implications for the genesis of a large lithium pegmatite province in West-Africa - Marieke Van Lichtervelde; Oscar Laurent; Prince Ofori Amponsah; Isaac Iwan E. Williams (Chemical Geology, 2025)

Textile Dyes in Wastewater and its Impact on Human and Environment: Focus on Bioremediation - Aravin Prince Periyasamy (Water, Air, & Soil Pollution, 2025)

Biological Parameters and Population Structure of Frigate Tuna (Auxis thazard) along Chennai coast, Southeast India - Paplin Prince. B; Santhoshkumar. S; Pavinkumar. P; Lloyd Crispin. C; John Chembian. A; Sudhan. C; Sasikumar. R.G (Thalassas: An International Journal of Marine Sciences, 2025)

Identifying suitable dam sites using geospatial data and machine learning: a case study of the katsina-ala river in Benue State, Nigeria - Ugochukwu Charles Akajiaku; Elijah Ige Ohimain; Ebikombo-ere B. Olodiama; Desmond Rowland Eteh; Ayebawanaemi G. Winston; Prince Chukwuemeka; Anslem O. Otutu; Becky Peremoboere Bamiekumo; Okes Imoni (Earth Science Informatics, 2025)

Influence of Supplementary Nickel on Minerals Balance, Hematobiochemical Parameters, Antioxidant Activity, Plasma Minerals and Hormones Status in Murrah Buffalo Calves - Thamizhan P; Chander Datt; Shambhvi; Prince Chauhan; Anupam Thakuria; Raman Malik (Agricultural Research, 2025)

Computational elucidation of Plasmodium falciparum enoyl-ACP reductase inhibition by Salacia debilis compounds: adaptive ligand binding drives antimalarial activity - Prince Manu; Muntawakilu Padiga Seidu; Alice Adomako; Caleb Kusi Asamoah; Ophelia Duodu; Akyana Britwum; Michael Konney Laryea; Godfred Darko; Lawrence Sheringham Borquaye (In Silico Pharmacology, 2025)

Erratum zu: Publishers Erratum zu mehreren Artikeln in BIOspektrum - Maria Felicia Basilicata; Anna Einsiedel; Olha Kurpa; Prince Saforo Amponsah; Martin Milanov; Markus Vögtle; Hans-Georg Koch; Gulustan Celik; Nadine Weinelt; Sjoerd J. L. van Wijk; Emma Fenech; J. Sofie Friedrich; et al. (BIOspektrum, 2025)

Characterising Long-Term Depressive Symptoms Post-brain Injury: A Systematic Review of Symptom Trajectory Groups and Their Predictors - Priscilla Prince; Kristin Naragon-Gainey; Rodrigo Becerra; Michael Weinborn; Carmela F. Pestell (Neuropsychology Review, 2025)
This systematic review investigates the long-term trajectories of depressive symptoms in individuals with acquired brain injury (ABI) and identifies factors predicting group membership in these trajectories. The review follows the PRISMA guidelines and is registered on the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY-2023–11-0013). A comprehensive search of MEDLINE, PSYCINFO, EMBASE, CINHALPlus, ScienceDirect, Scopus, and Web of Science identified peer-reviewed studies published in English on adults aged 16 and above with an ABI diagnosis. Studies were included if they used a validated depression measure, had at least three assessment points, and applied group-based trajectory modelling. Exclusion criteria included studies focusing on neurodegenerative or neurodevelopmental disorders, or solely on treatments. The methodological quality was assessed using Joanna Briggs’ critical appraisal tool. The review synthesised data from ten studies involving 13,205 participants (average age 51.38 years, 55.86% male). Four depressive symptom trajectory groups were identified with varying prevalence: stable low (68%), persistent high (13%), increasing (20%), and decreasing (11%). Several key predictors including sex, age, injury severity, and education emerged as significant predictors of group membership in the persistent high , increasing , and decreasing depressive groups. However, variability in study methodologies and sample compositions posed challenges to direct comparison. Nonetheless, the review underscores the importance of long-term monitoring and the development of tailored interventions, as depression can manifest or intensify years post-injury. Understanding depressive symptom trajectories could help create personalised interventions, improving quality of life for those with depression after ABI.

Mechanistic exploration of BPA-induced hepatotoxicity and the therapeutic potential of Kedrostis foetidissima: A network pharmacology and molecular docking study incorporating in silico and in vitro approach - Doveit Antony Charles; Sabina Evan Prince (South African Journal of Botany, 2025)

A blockchain-based supply chain framework for advancing circular economy in the construction industry - Lawrence Martin Mankata; Prince Antwi-Afari; S. Thomas Ng (Journal of Cleaner Production, 2025)

Binding mechanism of metal ions (Ca2+, Cu2+ and Mg2+) with tetrapeptide FFDR: A combined experimental and quantum chemistry approach - Chidimma Juliet Igbokwe; Feng Shao; Ziqi Yan; Janet Quaisie; Timothy Prince Chidike Ezeorba; Yuqing Duan; Kai Hu; Meihong Cai; Haihua Zhang (Food Chemistry, 2025)

Indoor air quality assessment of particulate matter levels in urban homes in India - Prince Vijay; Vinayak Sahota; Rajdeep Singh; Shreya Dubey; Sonali Borse; Harish C. Phuleria (Atmospheric Pollution Research, 2025)

Life cycle methodology for determining the effect of reformulating swine diets with an enzyme technology to mitigate environmental impact and optimize production performance in Canada - Prince Agyemang; Ebenezer M. Kwofie; Ludovic Lahaye; Melissa Otis; Emilie Fontaine; Glenmer Tactacan; Marcia de Souza Vieira (The International Journal of Life Cycle Assessment, 2025)

Characteristics of mesoscale convective systems during monsoon extreme rainfall events: case studies from the southwest coast of India - D. S. Silpamol; Ajil Kottayil; Viju O. John; Prince Xavier (Natural Hazards, 2025)

Sustainability analysis and exergy return on investment of a dual-chamber solar PV-powered evaporative cooling system based on conventional and extended exergy approach - M. C. Ndukwu; Leonard Akuwueke; Godwin Akpan; Godwin A. Usoh; Inemesit Ekop; Linus Oriaku; Augustine Edet Ben; Prince Omenyi; Emeka Oleka; Merlin Simo-Tagne; Fidelis Abam (Clean Technologies and Environmental Policy, 2025)

Exploring the Antibacterial, Antioxidant and Larvicidal Effects against Culex quinquefasciatus of Nigella sativa Seeds and its Silver Nanoparticles - Jefrillah Jebaseelan; Umamaheswari Kopula Ganesh; Prince Leeban Johnwilmet; Rajalakshmi Anbalagan; Jayalakshmi Krishnan; Anand Setty Balakrishnan (Acta Parasitologica, 2025)

Numerical investigation of negative skin friction in battered piles group Based on pile position: a consolidation study - Ghislain Franck Emani; Weiya Xu; Prince Kas-Avortri; Firdawus Ssemuga Nattabi; Zeeshan Khursheed; Erika Chantal Etine (European Journal of Environmental and Civil Engineering, 2025)

Mercury in the environment: Biogeochemical transformation, ecological impacts, human risks, and remediation strategies - Suryapratap Ray; Rahul Vashishth; Anirban Goutam Mukherjee; Abilash Valsala Gopalakrishnan; Evan Prince Sabina (Chemosphere, 2025)

Exploring the off-flavour removal mechanism of d-limonene, geraniol and acetophenone in perilla leaves from the perspective of molecular structure and kinetic properties - Ke Bi; Yue Liu; Kangyu Wang; Ping Yang; Dong Han; Chunhui Zhang; Yanlu Luan; Lijuan Dong; Prince Chisoro; Marie-laure Fauconnier (Food Chemistry, 2025)

Optimizing starch-free arabinogalactan-rich taro nanomucilage: Green experimental design, structural elucidation, amino acid profiling, and biological properties - Mansuri M. Tosif; Aarti Bains; Prince Chawla; Surinder Paul; Poonam Kumari; Sanju Bala Dhull; Nemat Ali; Gulden Goksen (Food Chemistry, 2025)

Green roof as flood mitigation in Ghana - Kevin Kerry Yankey; Emmanuel Kwesi Nyantakyi; Amos T. Kabo-bah; Martin Kyereh Domfeh; Prince Antwi-Agyei; Robert Andoh; Nana Osei Bonsu Ackerson; Saeed Ibn Idris Kofi Yeboah; Anna Minkah-Amankwah; Thomas Atta-Darkwa (Natural Hazards, 2025)

The foraging distribution and habitat use of chick-rearing snow petrels from two colonies in Dronning Maud Land, Antarctica - Eleanor Maedhbh Honan; Ewan D. Wakefield; Richard A. Phillips; W. James Grecian; Stephanie Prince; Henri Robert; Sébastien Descamps; Anna Rix; A. Rus Hoelzel; Erin L. McClymont (Marine Biology, 2025)
The polar sea-ice zones are highly productive and seasonal habitats that support large populations of vertebrate predators. In the Antarctic, snow petrels ( Pagodroma nivea ) are regarded as highly ice-dependant, yet knowledge of their habitat use and foraging distribution during the breeding period comes largely from ship-based observations. Snow petrels show sexual size dimorphism, and previous studies have demonstrated a degree of sexual segregation in habitat use in East Antarctica during the incubation period. Here, we characterise the movements, behaviour and habitat use of foraging snow petrels using bird movement and remotely sensed environmental data. We tracked snow petrels from two colonies in Dronning Maud Land, East Antarctica during early chick rearing in January to February 2022, a period of unusually rapid sea-ice retreat in the region. During the chick-rearing period, mean foraging range was c. 395 km and did not differ between the sexes. However, we found some evidence of differing habitat use between the sexes: males foraged more in areas of higher sea-ice concentration and over the continental shelf, while females utilized deeper waters and lower sea-ice concentrations. Sexes also diverged in their behavioural responses to both sea ice and depths, with males more likely to switch to foraging in areas of higher sea-ice concentrations than females and females more likely to switch to foraging in deeper waters than males. Although both sexes were more likely to forage at higher sea-ice concentrations, they also used areas with little or no sea ice. This contrasts with previous studies and may have been due to the unusual paucity of sea-ice cover during our tracking period.

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Examining light absorbing characteristics of fine particulate matter during winter 2019–20 in residential areas of metropolitan cities in India - Prince Vijay; Harish C. Phuleria (Urban Climate, 2025)

Mapping and topic modeling of over 133,000 studies on climate change and cities: Trends, geographical disparities, and future research needs - Ayyoob Sharifi; Yukai Jin; Prince Dacosta Aboagye (Urban Climate, 2025)

Exploring the effect of early-life climate anomalies on child growth in Sub-Saharan African context: Insight from the demographic & health survey - Prince M. Amegbor; Kaira Lapurga; Elizabeth Carr; Marisa Guerrero; Oyinkansola Babayode; Sarah E. Crisci; Xin Y. Fang; Ayesa Siddeky; Reginald Quansah (Science of The Total Environment, 2025)

Review of Paleoproterozoic tectonics in the southern West African Craton: Insights from multi-disciplinary data integration - Julien Perret; Mark W. Jessell; Quentin Masurel; Patrick C. Hayman; Nicolas Thébaud; Lenka Baratoux; Alain Kouamélan; Aurélien Eglinger; Anne-Sylvie André-Mayer; Augustin Y. Koffi; Ibrahima Dia; Jacques Koné; et al. (Precambrian Research, 2025)

Quality decline of prepared dishes stored at 4 °C: Microbial regulation of nitrite and biogenic amine formation - Jiaxin Liu; Yin Wang; Ping Yang; Hongbo Li; Haizhen Mo; Prince Chisoro; Dong Han; Chunhui Zhang (Food Microbiology, 2025)

Significance of Planet SuperDove and refined Sentinel-2 imagery fusion for enhanced soil organic carbon prediction in croplands - James Kobina Mensah Biney; Jakub Houška; Olha Kachalova; Jiří Volánek; Prince Chapman Agyeman; David Kwesi Abebrese; Ehsan Chatraei Azizabadi; Nasem Badreldin (CATENA, 2025)

Mitigation of cadmium-induced hepatotoxicity by orally administered Xylopia aethiopica synthesized silver nanoparticles in rats - Emmanuel Nnaemeka Uhuo; Chiemeziem Adnma Obike; Parker Elijah Joshua; Prince Ogochukwu Alaebo; Rhonick Chukwuemeka Anyanwu (Journal of Molecular Histology, 2025)

A global systematic review and meta-analysis of innovative technologies for 1,2,4-trichlorobenzene remediation in soil and water - Olive Mekontchou Yemele; Zhenhua Zhao; Mbezele Junior Yannick Ngaba; Ervice Ymele; Liling Xia; Wang Xiaorou; Prince Atta Opoku (Environmental Geochemistry and Health, 2025)

Enhancing Environmental Quality through Board Dynamics: The Role of Environmental Regulations in Advancing Circular Economy in the SSA Region - Prince Brefo Boakye; John Yaw Akparep; Andrews Salakpi (Circular Economy and Sustainability, 2025)

Average Biomechanical Responses of the Human Brain Grouped by Age and Sex - Ahmed Alshareef; Aaron Carass; Yuan-Chiao Lu; Joy Mojumder; Alexa M. Diano; Olivia M. Bailey; Ruth J. Okamoto; Dzung L. Pham; Jerry L. Prince; Philip V. Bayly; Curtis L. Johnson (Annals of Biomedical Engineering, 2025)
Traumatic brain injuries (TBIs) occur from rapid head motion that results in brain deformation. Computational models are typically used to estimate brain deformation to predict risk of injury and evaluate the effectiveness of safety countermeasures. The accuracy of these models relies on validation to experimental brain deformation data. In this study, we create the first group-average biomechanical responses of the brain, including structure, material properties, and deformation response, by age and sex from 157 subjects. Subjects were sorted intro three age groups—young, mid-age, and older—and by sex to create group-average neuroanatomy, material properties, and brain deformation response to non-injurious loading using structural and specialized magnetic resonance imaging data. Computational models were also built using the group-average geometry and material properties for each of the six groups. The material properties did not depend on sex, but showed a decrease in shear stiffness in the older adult group. The brain deformation response also showed differences in the distribution of strain and a decrease in the magnitude of maximum strain in the older adult group. The computational models were simulated using the same non-injurious loading conditions as the subject data. While the models’ strain response showed differences among the models, there were no clear relationships with age. Further studies, both modeling and experimental, with more data from subjects in each age group, are needed to clarify the mechanisms underlying the observed changes in strain response with age, and for computational models to better match the trends observed across the group-average responses.

Potentially toxic elements in artisanal gold mine soils: contamination assessment, spatial distribution and associated risks in Ghana - Alex Amerh Agbeshie; Richard Awuah; Daniel Adusu; Rechiatu Asei; Prince Kwabena Agyapong; Vicentia Amoako; Precious Baryeh; Adisa Zibilila (Environmental Monitoring and Assessment, 2025)

Tunable quantum dots-modified metal–organic frameworks for photocatalytic conversion of CO2 to fuels and chemicals: a review - Suverna Trivedi; Balaji P. Selvaraj; Prince Ochonma; Greeshma Gadikota (Environmental Science and Pollution Research, 2025)

Understanding farmers’ challenges in maintaining maize quality for industrial use in Ghana: Barriers and strategies - Mensah Amos; Faizal Adams; Prince Asiedu; Vashti Owusu-Nkwantabisah; Samuel Owusu Afriyie (Journal of Stored Products Research, 2025)

Microbiota, mitochondria, and epigenetics in health and disease: converging pathways to solve the puzzle - Natalia Lucia Rukavina Mikusic; Paula Denise Prince; Marcelo Roberto Choi; Luiz Gustavo A. Chuffa; Vinícius Augusto Simão; Claudia Castro; Walter Manucha; Isabel Quesada (Pflügers Archiv - European Journal of Physiology, 2025)

Prediction of lead in agricultural soils: An integrated approach using machine learning, terrain attributes and reflectance spectra - Prince Chapman AGYEMAN; Kingsley JOHN; Ndiye Michael KEBONYE; Vahid KHOSRAVI; Luboš BORŮVKA; Radim VAŠÁT; Charles Mario BOATENG (Pedosphere, 2025)

Application of mucilage-based functional and clean-label food ingredients as vegan fat replacers in different food products - Mansuri M. Tosif; Aarti Bains; Gulden Goksen; Ravinder Kaushik; Prince Chawla (Current Opinion in Food Science, 2025)

Deciphering the Relationship Between Moisture Flux and Monsoon Extreme Rainfall Over the West Coast of India - Tesna Maria; Ajil Kottayil; Prince Xavier; Viju O. John (International Journal of Climatology, 2025)
The west coast of India has recently been experiencing torrential monsoon rains, a trend that studies indicate is likely to continue under future warming scenarios. This study investigates the link between moisture flux and extreme rainfall over the west coast, using observational and reanalysis datasets for the monsoon seasons (June to September) from 1990 to 2023. The analysis shows that, over the Indian subcontinent, rainfall along the west coast is primarily influenced by large‐scale moisture flux from the Arabian Sea. By decomposing the vertically integrated moisture flux into dynamic and thermodynamic components, this study observes that the thermodynamic component of moisture flux exhibits an increasing trend over the southwest coast, while this increasing trend is more prominent for the dynamic component over the northwest coast. Extreme rainfall over the southwest coast is increasing at a rate of 0.23 mm per season, attributed primarily to the increase in the thermodynamic component of moisture flux. It is observed that the rate of sea surface temperature (SST) increase over the Arabian Sea is faster than over the Bay of Bengal, with the average SST over the southeast Arabian Sea exceeding 28°C in recent years. Observations indicate that warming over the southeast Arabian Sea is strongly coupled with moisture accumulation observed over the southwest coast. This study provides strong evidence of a link between moisture transport, extreme rainfall and SST, identifying the southwest coast as a region vulnerable to climate change. Over the northwest coast, the incidence of extreme rainfall is associated with the strengthening of dynamic processes, and the mean monsoon rainfall in this region is increasing in alignment with the rising dynamic component of moisture flux.

Paying attention to proprioception: age affects ankle proprioception and the attentional demand of proprioceptive processing in sedentary adults - Marie Julie Vermette; Emmeline Paré; François Prince; Julie Messier (GeroScience, 2025)

Agricultural commercialization and sustainable land management practices in Ghana - Edward Martey; Prince M. Etwire; Tahirou Abdoulaye (Environment, Development and Sustainability, 2025)

A flavone C-glycoside, the major component of Gnetum africanum leaf extract, displayed strong immunomodulatory activity - Ngozi Madubogwu; Daniel L. Ajaghaku; Nkeoma Nkasi Okoye; Prince C Unekwe; Peter Proksch; Festus Basden C. Okoye (South African Journal of Botany, 2025)

Bayesian spatio-temporal modeling of African CO2 emissions (1990–2020): A hierarchical approach to identify determinants, regional trends, and local dynamics - Ebenezer Afrifa-Yamoah; Prince Mensah Osei (Science of The Total Environment, 2025)

Phytoplankton dynamics in the Antarctic marginal ice zone: Trends and drivers - Prince Prakash; Rahul Mohan; Ravidas K. Naik; Alvarinho J. Luis (Journal of Marine Systems, 2025)

Unique hot stage modification technique to enhance cementitious properties of electric arc furnace steel slag - Sheshang Singh Chandel; Avala Lavakumar; Navneet Singh Randhawa; Prince Kumar Singh (Journal of Environmental Management, 2025)

Microstructural analysis of phosphorus (P)-bearing assemblages in type 3 chondrites: Implications for P condensation and processing in the early solar nebula - M.C. Benner; V.R. Manga; B.S. Prince; L.M. Ziurys; T.J. Zega (Geochimica et Cosmochimica Acta, 2025)

Extraction and characterization of biopolymers from rice bran oil cake: Development of antimicrobial edible coating for extending shelf-life of strawberry fruit - Aashima Salaria; Shubham Singh Patel; Kandi Sridhar; Prince Chawla; Minaxi Sharma (Food Bioscience, 2025)

Biological Traits and Population Characteristics of Japanese Threadfin Bream, Nemipterus japonicus from the Coromandel Coast of Tamil Nadu, India - R. G. Sasikumar; S. Santhoshkumar; P. Pavinkumar; R. Velmurugan; R. Kumaran; B. Paplin Prince (Thalassas: An International Journal of Marine Sciences, 2025)

Insights into Cadmium Uptake and Changes in Morphophysiological and Biochemical Characteristics of Eclipta alba L., Plants Exposed to Elevated Cadmium in Soil - Akanksha Dwivedi; Prince Kumar Singh; Umesh Kumar; Indrajeet Kumar; Priyanka Singh; Rajesh Kumar Sharma (Journal of Soil Science and Plant Nutrition, 2025)

A comprehensive review of cadmium-induced toxicity, signalling pathways, and potential mitigation strategies - Naveen Vijiyakumar; Sabina Evan Prince (Toxicology and Environmental Health Sciences, 2025)

Modelling present and future distribution of intertidal macroalgae to evaluate the efficacy of Western Australia’s marine protected areas - Hadiyanto Hadiyanto; Jane Prince; Renae K. Hovey (Biodiversity and Conservation, 2025)
Distribution patterns of intertidal macroalgae are often investigated to evaluate the efficacy of designated marine protected areas (MPAs), yet those assemblages are threatened by high sea surface temperatures, making them vulnerable to ocean warming. Here, we model the present distribution patterns of macroalgae on rocky intertidal shores of Western Australia and project those patterns onto different future climate scenarios to assess the effect of ocean warming. Present and future distribution patterns of those assemblages were then used to evaluate the efficacy of presently designated MPAs. We developed distribution models using hierarchical modelling of species communities based on species occurrence and biomass data of 36 species from 38 sites (18°S to 34°S). The efficacy of MPAs was evaluated by overlaying marine park boundaries with the map of species distributions. Macroalgae were projected to show decreases in species richness by 49%, reduction in total biomass by 20%, changes in species composition by 43%, increases in spatial homogenisation, poleward shift by 0.80°, and loss in distribution area by 70% by 2100 based on RCP8.5 scenario. Nevertheless, half of the remaining distribution area of macroalgae was still inside existing MPAs. The current macroalgal bioregions all contained at least one MPA, but it is projected that a bioregion from 25°S to 31°S will be separated into two distinct bioregions (25°S to 29°S and 30°S to 31°S) by 2100 based on RCP8.5 scenario. Unfortunately, there is no MPA within the northernmost bioregion, and all studied species inside the MPA within the southernmost bioregion will go extinct under that scenario. Thus, the current system of MPAs will be inadequate in the future, based on our modelling.

Shellogy: reading abalone shells to empower reef‐scale management - Jeremy D. Prince (New Zealand Journal of Marine and Freshwater Research, 2025)
Developing spatially explicit assessment and management techniques that engage stakeholder behaviour has been an enduring priority for fisheries targeting benthic marine invertebrates like abalone. This study describes the basis of ‘Shellogy’; a concept with the potential to empower reef‐scaled management by using shell morphology to qualitatively evaluate abalone populations and their variability. The premise of shellogy is that a range of shell characteristics, previously established as distinguishing between populations with differing life history parameters, are also indicative of relative age and stage of maturation. Using the analysis of existing data, literature synthesis and illustrations, together with simulation of length frequency histograms, this study establishes from first principles that the morphometric ratios of abalone shells, along with superficial internal and external shell characteristics, change predictably with age and maturation. This study explains how recognising the connection between shell shape, and relative age and maturity, enables the appearance of shells in populations and catches, to be used to inform qualitative reef‐scale assessment and facilitate stakeholder engagement with reef‐scale management initiatives.

Exploring the Therapeutic Potential of Esculetin in Mitigating Cyclophosphamide-Induced Hepato-Toxicity - Prathap Srirangan; Sabina Evan Prince (Indian Journal of Clinical Biochemistry, 2025)

Environmental risk assessment of heavy metals and microplastics in marine biota along Gujarat coastline, India - Prince Upadhyay; Rahul Ladumor; Tejas Gurjar; Monisha Kottayi; Ankita Doshi; Parth Pandya (Marine Pollution Bulletin, 2025)

A silent killer in the word: Review on Aspergillus flavus strains - Yann Christie Sissinto Adjovi; Joli Prince Mintognissè Fossou; Ulrich Hilarion Ahehehinnou (Toxicon, 2025)

Unveiling the potential of freshwater edible algae: Innovative extractions and functional food applications - VP Aswathy; Sayani Mavai; Aarti Bains; Kandi Sridhar; Baskaran Stephen Inbaraj; Prince Chawla; Minaxi Sharma (South African Journal of Botany, 2025)

Changes in freezing parameters and temperature distribution of beef induced by AC electric field: Alleviation on freezing damage and myowater loss - Hengxun Lin; Jing Wang; Prince Chisoro; Guangyu Wu; Songsong Zhao; Xiaojia Hu; Chuan Yang; Yunhe Liu; Wei Jia; Qingqing Li; Chunhui Zhang; Christophe Blecker; et al. (Journal of Food Engineering, 2025)

Design of ternary metal oxides for photoelectrochemical water splitting using machine learning techniques - Snehangshu Mishra; Prince Kumar; Sutapa Dey; Prasanta Pattanayak; Trilok Singh (Journal of Environmental Chemical Engineering, 2025)

Petrology and geochemistry of the Suhum Basin granitoid complex, Ghana: Implications for crustal growth during the Rhyacian orogeny of the West African Craton - Daniel Kwayisi; Prince Ofori Amponsah; Emmanuel Kwaku Awunyo; Marian Selorm Sapah; Patrick Asamoah Sakyi; Ben-Xun Su; Prosper M. Nude; Abigail Enyonam Ayikwei; Eric Dominic Forson (Journal of African Earth Sciences, 2025)

Characterizing metabolome signature of colostrum, transition and mature milk of indigenous cows (Bos indicus) adapted to high altitude environment of Leh-Ladakh - Amarjeet; Umesh Kumar; Monika Sodhi; Dinesh Kumar; Prince Vivek; Saket K. Niranjan; Ranjit Singh Kataria; Sudarshan Kumar; Manish Sharma; Manish Tiwari; Rajeev A.K. Aggarwal; Vijay K. Bharti; et al. (Food Chemistry, 2025)

Interfacial composition on the mechanical properties, microstructure and digestion of emulsion-filled whey protein gels: Effect of soy and whey protein ratios - Georgina Benewaa Yeboah; Sen Wang; Wei Wu; Haowei Zhang; Prince Ofori Donkor; Juan Wu; Yu Cheng (Food Bioscience, 2025)

Environmental-Health Convergence: A deep learning-oriented decision support system for catalyzing sustainable healthy food systems - Prince Agyemang; Ebenezer M. Kwofie; Jamie I. Baum; Dongyi Wang; Emmanuel A. Kwofie (Environmental Modelling & Software, 2025)

Does participation in on-farm demonstrations improve aspirations formation and food security? Evidence from Ghana - Edward Martey; John K. M. Kuwornu; Prince M. Etwire; Emmanuel K. Apiors; Samuel Kwabena Chaa Kyire; Patrick Maanikuu Muotono Izideen; Francis H. Kemeze (Food Security, 2025)

How do genome abnormalities impact mitochondrial homeostasis? - Olha Kurpa; Prince Saforo Amponsah (BIOspektrum, 2025)
The genome of eukaryotes encodes thousands of proteins needed to ensure cell health. Hence, an imbalance in the genome has profound consequences for protein homeostasis (proteostasis). The genome and proteome are interlocked in a mutual relationship, which impacts the functions of cellular organelles like mitochondria. However, the underlying mechanisms remain an enigma. Here, we highlight this relationship and outline some open questions to be addressed.

Griffin: A MOOSE-based reactor physics application for multiphysics simulation of advanced nuclear reactors - Yaqi Wang; Zachary M. Prince; Hansol Park; Olin W. Calvin; Namjae Choi; Yeon Sang Jung; Sebastian Schunert; Shikhar Kumar; Joshua T. Hanophy; Vincent M. Labouré; Changho Lee; Javier Ortensi; et al. (Annals of Nuclear Energy, 2025)

Aerosol transport and associated boundary layer thermodynamics under contrasting synoptic conditions over a semiarid site - Sandip Pal; Nicholas E. Prince; Michael Anand; Matthew Hamel (Science of The Total Environment, 2025)

TracMyAir smartphone application for modeling exposures to PM2.5 and ozone – Integration with air quality networks and location-activity sensors - Michael Breen; Vlad Isakov; Catherine Seppanen; Saravanan Arunachalam; Miyuki Breen; Steven Prince; Thomas Long; David Heist; Parikshit Deshmukh; K. Wyat Appel; Christian Hogrefe; Benjamin Murphy; et al. (Science of The Total Environment, 2025)

Post-tornado roadway debris detection from satellite images: An integrated GIS and image processing approach - Richard Boadu Antwi; Prince Lartey Lawson; Eren Erman Ozguven; Ren Moses (Remote Sensing Applications: Society and Environment, 2025)

Bioenergy generation, organic matter, and simultaneous nitrogen and phosphorus removal in comparative pyrite and graphite-based constructed wetland-microbial fuel cells at different anode scales - Prince Atta Opoku; Xu Shaowei; Huang Jingyu (Journal of Water Process Engineering, 2025)

Antibiotic residues and antibiotic resistance genes in African water systems: Implications for safe drinking water, aquatic ecosystems, and Sustainable Development Goals - Emmanuel Sunday Okeke; Chidiebele Emmanuel Ikechukwu Nwankwo; Timothy Prince Chidike Ezeorba; Martins Obinna Ogugofor; Charles Ogugua Nwuche (Journal of Water Process Engineering, 2025)

Examining the risk mitigation strategies of farm households in Ghana: The role of community water resources - Edward Martey; Prince M. Etwire; Collins Asante-Addo; Francis Addeah Darko; Mustapha M. Suraj (Journal of Environmental Management, 2025)

How thawing and salting affects the post-cooked quality of frozen beef: New insights into the mechanism of fiber morphology evolution and water migration - Hengxun Lin; Yong Chen; Yiping Yang; Liye Cui; Guangyu Wu; Prince Chisoro; Xiangning Chen; Xia Li; Chunhui Zhang; Christophe Blecker (Food Research International, 2025)

Recent advances in the analytical methods for quantitative determination of antioxidants in food matrices - Nikhil Dnyaneshwar Patil; Aarti Bains; Kandi Sridhar; Minaxi Sharma; Sanju Bala Dhull; Gulden Goksen; Prince Chawla; Baskaran Stephen Inbaraj (Food Chemistry, 2025)

Emerging deep eutectic solvents for food waste valorization to achieve sustainable development goals: Bioactive extractions and food applications - Sayani Mavai; Aarti Bains; Kandi Sridhar; Prince Chawla; Minaxi Sharma (Food Chemistry, 2025)

Utilizing plant-derived mucilage as palm oil substitute in chocolate cream: A comparative study of Colocasia esculenta, Cordia dichotoma, and Psyllium husk mucilage - Mansuri M. Tosif; Aarti Bains; Gulden Goksen; Mohd Ziaur Rehman; Nemat Ali; Prince Chawla (Food Bioscience, 2025)

Earth Observation Based Characterization of Environmental Conditions for Forest Fire Risk in Western Himalayan Ecosystems Using Machine Learning Approach - Shanti Kumari; Shailja Mamgain; Arijit Roy; H. C. Prince; Aditi Ahlawat (Journal of the Indian Society of Remote Sensing, 2025)

Timing analysis of Be/X-ray transient 4U 0115 + 63 during Type II outburst of 2023 using NuSTARobservations - Chetana Jain; Prince Sharma; Anjan Dutta (Advances in Space Research, 2025)

Evaluating the sensitivity of a chronic plant bioassay relative to an independently derived predicted no-effect thresholds to support risk assessment of very hydrophobic organic chemicals - Aaron D. Redman; Miriam Leon Paumen; Daniel J. Letinski; Barbara A. Kelley; Cary Sutherland; Bryan M. Hedgpeth; Josh D. Butler; Roger Prince; Gail E. Bragin; Abraham J. Smith (Archives of Environmental Contamination and Toxicology, 2025)

In silico design and assessment of a multi-epitope peptide vaccine against multidrug-resistant Acinetobacter baumannii - Shiv Nandan Sah; Sumit Gupta; Neha Bhardwaj; Lalit Kumar Gautam; Neena Capalash; Prince Sharma (In Silico Pharmacology, 2024)

Spatial model of groundwater contamination risks from pit-latrines in a low-income country - Rebekah G.K. Hinton; Robert M. Kalin; Modesta B. Kanjaye; Prince Mleta; Christopher J.A. Macleod; Mads Troldborg (Water Research, 2024)

Cortisol concentrations in substance use disorder patients undergoing short-term psychotherapy incorporating equine interaction compared to cognitive behavioral therapy: A preliminary study - E. Farnlacher; M.M. Friend; K. Holtcamp; M.C. Nicodemus; R. Swanson; C. Lemley; C. Cavinder; P. Prince (Journal of Equine Veterinary Science, 2024)

Micro-level welfare effects of integrated soil fertility management in Northern Ghana - Edward Martey; Prince M. Etwire; John K.M. Kuwornu; Mustapha M. Suraj (Journal of Cleaner Production, 2024)

Green growth in Africa: The role of renewable energy, biocapacity, government policies, and R&D on CO2 emissions reductions - Kyei Emmanuel Yeboah; Junwen Feng; Seidu Abdulai Jamatutu; Prince Yaw Owusu Amoako; Felicia Esi Nyarko; Nabila Amin (Journal of Environmental Management, 2024)

Integrating multiple microstructure and water distribution visual analysis to reveal the moisture release and quality deterioration of precooked beef during freezing-thawing-reheating processes - Hengxun Lin; Liye Cui; Yong Chen; Yiping Yang; Xiangning Chen; Prince Chisoro; Xia Li; Christophe Blecker; Chunhui Zhang (Food Chemistry, 2024)

Exploration of Calocybe indica mushroom phenolic acid-kidney bean protein complex: Functional properties, amino acid profiles, in-vitro digestibility, and application in vegan product development - Nikhil Dnyaneshwar Patil; Sweezee Thakur; Aarti Bains; Sawinder Kaur; Nemat Ali; Rahul Arora; Mohammad Khalid Parvez; Gulden Goksen; Sandeep Janghu; Prince Chawla (Food Chemistry, 2024)

Biomass-derived carbon quantum dots from Chlorella vulgaris: Photocatalytic reduction of malachite green dye coupled with anti-quorum sensing and antimicrobial activity against food pathogens - Sweezee Thakur; Aarti Bains; Anil Kumar; Gulden Goksen; Sanju Bala Dhull; Nemat Ali; Mohammad Rashid Khan; Prince Chawla (Food Bioscience, 2024)

Analysis of urban households’ perception and factors that influence participation in urban agriculture in Kumasi, Ghana - Fred Nimoh; Enoch Kwame Tham-Agyekum; Prince Donkor; Latif Issaka; Linda Asare; Stephen Prah (Food and Humanity, 2024)

Advancing antimicrobial efficacy of Cucumis momordica seeds: Nanoemulsion application in Eurotium cristatum-mediated solid-state fermentation - Madhu Sharma; Gulden Goksen; Nemat Ali; Sandeep Janghu; Mohammad Khalid Parvez; Mohammed S. Al-Dosari; Maharshi Bhaswant; Prince Chawla (Food and Bioproducts Processing, 2024)

Economic parameter estimates of spring wheat varieties grown under different cultivation technologies - Francess Sia Saquee; Elena Pakina; Meisam Zargar; Prince Emmanuel Norman; Kalabashkina Elena Vladimirovna; Tsymbalova Vitaliya Alexandrovna (Biocatalysis and Agricultural Biotechnology, 2024)

Sustainable management of rice by-products: Environmental challenges, industrial applications, and circular bio-economy innovations - Ajay Kamboj; Pardeep Kumar Sadh; Prince Chawla; Baljeet Singh Saharan; Chandra Shekhar Seth; Kandi Sridhar; Joginder Singh Duhan; Minaxi Sharma (Biocatalysis and Agricultural Biotechnology, 2024)

Drought Priming Enhanced Grain Yield of Wheat Against Salinity Stress - Ashutus Singha; Jahidul Karim; Asif Adnan Prince; Nargis Akter; khalada Akter Runa; Muhammad Naqib; A. K. Mohibul Islam; Setu Roy; Jouadul Hasan (Water Conservation Science and Engineering, 2024)

The association of FSCN1 (rs852479, rs1640233) and HOTAIR (rs920778) polymorphisms with the risk of breast cancer in Egyptian women - Eman Reda Galal; Dina A. Abdelhakam; Lamiaa Khalaf Ahmed; Yasmine Elhusseny; Sherif El Prince Sayed; Noha H. Eltaweel (Molecular Biology Reports, 2024)
Background Breast cancer (BC) is one of the most prevalent cancers that contribute to mortality among women worldwide. Despite contradictory findings, considerable evidence suggests that single nucleotide polymorphisms (SNPs) in the FSCN1 and HOTAIR genes may have a causative impact on the development of BC. This case–control study was conducted to evaluate the association of genotype frequency in FSCN1 rs852479, rs1640233, and HOTAIR rs920778 with susceptibility and prognosis of BC, as well as the impact of clinical stages and hormonal features. Methods and results FSCN1 (rs852479, rs1640233) and HOTAIR (rs920778) were genotyped using TaqMan real-time PCR assay in 200 BC patients and 200 cancer-free controls, all representing Egyptian women. Genotypic analyses in association with clinicopathological factors and disease risk were assessed. As a result, a significant association with BC risk was observed for CC genotype frequency of FSCN1 rs852479 A > C (OR = 0.395, 95% CI 0.204–0.76, p - value = 0.005). However, no significant correlation was detected between the FSCN1 rs1640233 C > T and HOTAIR rs920778 C > T polymorphic variants and susceptibility to BC. Interestingly, CC genotype of FSCN1 rs1640233 was more likely to progress tumor size and lymph node invasion in BC cases ( p - value = 0.04 and 0.02, respectively). Moreover, it was revealed that there was a non-significant correlation between the haplotype distributions of FSCN1 rs852479 and rs1640233 and the probability of BC. Conclusions Based on the sample size and genetic characteristics of the subjects involved in the present study, our findings indicated that FSCN1 rs852479 may contribute to BC susceptibility in a sample of the Egyptian population.

A perspective on varied fungal virulence factors causing infection in host plants - Prince Kumar; Rajani Sharma; Kunal Kumar (Molecular Biology Reports, 2024)

Temporal insights into deep chlorophyll maxima dynamics in the Indian sector of the Southern Ocean: a Bio-Argo float study - Prince Prakash; T. V. S. Uday Bhaskar (Journal of Oceanography, 2024)

Effect of shade management practice on cocoa seedling mortality: micro evidence from the Amansie-West district of Ghana - Amos Mensah; Faizal Adams; Bright Owusu Asante; Stephen Prah; Badu Yaw Tweneboa; Prince Asiedu (Agroforestry Systems, 2024)

Mesopredator release moderates trophic control of plant biomass in a Georgia salt marsh - Joseph P. Morton; Marc J. S. Hensel; David S. DeLaMater; Christine Angelini; Rebecca L. Atkins; Kimberly D. Prince; Sydney L. Williams; Anjali D. Boyd; Jennifer Parsons; Emlyn J. Resetarits; Carter S. Smith; Stephanie Valdez; et al. (Ecology, 2024)
Predators regulate communities through top‐down control in many ecosystems. Because most studies of top‐down control last less than a year and focus on only a subset of the community, they may miss predator effects that manifest at longer timescales or across whole food webs. In southeastern US salt marshes, short‐term and small‐scale experiments indicate that nektonic predators (e.g., blue crab, fish, terrapins) facilitate the foundational grass, Spartina alterniflora , by consuming herbivorous snails and crabs. To test both how nekton affect marsh processes when the entire animal community is present, and how prior results scale over time, we conducted a 3‐year nekton exclusion experiment in a Georgia salt marsh using replicated 19.6 m 2 plots. Our nekton exclusions increased densities of plant‐grazing snails and juvenile deposit‐feeding fiddler crab and, in Year 2, reduced predation on tethered juvenile snails, indicating that nektonic predators control these key macroinvertebrates. However, in Year 3, densities of mesopredatory benthic mud crabs increased threefold in nekton exclusions, erasing the tethered snails' predation refuge. Nekton exclusion had no effect on Spartina biomass, likely because the observed mesopredator release suppressed grazing snail densities and elevated densities of fiddler crabs, whose burrowing alleviates soil stresses. Structural equation modeling supported the hypotheses that nektonic predators and mesopredators control invertebrate communities, with nektonic predators having stronger total effects on Spartina than mud crabs by controlling densities of species that both suppress (grazers) and facilitate (fiddler crabs) plant growth. These findings highlight that salt marshes can be resilient to multiyear reductions in nektonic predators if mesopredators are present and that multiple pathways of trophic control manifest in different ways over time to mediate community dynamics. These results highlight that larger scale and longer‐term experiments can illuminate community dynamics not previously understood, even in well‐studied ecosystems such as salt marshes.

Major overlap in plant and soil organic carbon hotspots across Africa - Ndiye Michael Kebonye; Kingsley John; Manuel Delgado-Baquerizo; Yong Zhou; Prince Chapman Agyeman; Zibanani Seletlo; Brandon Heung; Thomas Scholten (Science of The Total Environment, 2024)

Assessing the influence of land use, agricultural, industrialization, CO2 emissions, and energy intensity on cereal production - Prince Dorian Rivel Bambi; Jean Baptiste Bernard Pea-Assounga (Journal of Environmental Management, 2024)

Exploring the role of static magnetic field in supercooling storage from the viewpoint of meat quality and microbial community - Yong Chen; Hengxun Lin; Yiping Yang; Liye Cui; Prince Chisoro; Chuan Yang; Guangyu Wu; Qingqing Li; Jingjun Li; Chunhui Zhang; Xia Li (Food Research International, 2024)

Environmental impact and source-controlled approaches for emerging micropollutants: Current status and future prospects - Madhu Sharma; Aarti Bains; Kandi Sridhar; Prince Chawla; Minaxi Sharma (Food and Chemical Toxicology, 2024)

Enabling modern bioenergy deployment in Nigeria to support industry and local communities - Prince Anthony Okoro; Katie Chong; Mirjam Röder (Biomass and Bioenergy, 2024)

Computational insights into NIMA-related kinase 6: unraveling mutational effects on structure and function - Nagesh Kishan Panchal; Shruti Mohanty; Sabina Evan Prince (Molecular and Cellular Biochemistry, 2024)

Correction: A new insight into monsoon intraseasonal variability as revealed from distinct wind-precipitation regimes over the southwest coast of India - K. Prajwal; Ajil Kottayil; Prince Xavier; Bernard Legras (Climate Dynamics, 2024)

A new insight into monsoon intraseasonal variability as revealed from distinct wind-precipitation regimes over the southwest coast of India - K. Prajwal; Ajil Kottayil; Prince Xavier; Bernard Legras (Climate Dynamics, 2024)

A widespread, consistent, and perplexing biphasic pattern in log catch‐at‐age data from a widely harvested family of tropical reef fishes - Brett M. Taylor; Jeremy Prince; Stephanie Mutz; Cassandra Pardee; John Wiley; D. Ross Robertson; J. Howard Choat (Fish and Fisheries, 2024)
Patterns of cohort decline are key demographic traits that provide a unique temporal perspective vital to understanding population dynamics. The discovery of multidecadal lifespans in tropical surgeonfishes in the 1990s created a paradigm shift to the notion that they are highly vulnerable species with low population recovery rates; however, research into the mortality patterns of surgeonfishes (Acanthuridae) has been sparse until recently. Recent studies on this family have demonstrated an unusual (possibly unique), two‐phase pattern of adult catch‐at‐age, whereby there is a population‐level shift from higher‐than‐expected rates of decline early in life to lower‐than‐expected decline rates for the remainder of the lifespan. To examine the geographic and phylogenetic ubiquity of this pattern, we compiled age‐based information from demographic samples of 70 populations of 25 tropical species spanning the Indo‐Central Pacific and Central‐Western Atlantic. Overall, we found that 79% of populations exhibited strong biphasic patterns, including 88% of populations across the Indo‐Central Pacific. By accounting for empirical relationships instead of using linear catch curves or classical assumptions of natural population decay based on lifespan, we demonstrate that surgeonfishes have turnover times that are two to four times faster than previously believed. Faster turnover times may suggest a higher level of sustainability for surgeonfish fisheries throughout the global tropics than previously estimated.

Phytochemical composition, antioxidant and antibacterial properties of methanol stem and leaf extracts of Croton bonplandianus Baill - Indrajeet Kumar; Umesh Kumar; Prince Kumar Singh; Jay Shankar Yadav; Akanksha Dwivedi; Priyanka Singh; Ashutosh Tripathi; Rajesh Kumar Sharma (Vegetos, 2024)

Modeling the fate and transport of E. coli pathogens in the Tano River Basin of Ghana under climate change and socioeconomic scenarios - Saeed Ibn Idris Kofi Yeboah; Prince Antwi-Agyei; Amos Tiereyangn Kabo-Bah; Nana Osei Bonsu Ackerson (Environmental Science and Pollution Research, 2024)

Utilization of quarry dust and periwinkle shell ash in concrete production - Chioma Emmanuella Njoku; Anthony Chibuzo Ekeleme; Benjamin Nnamdi Ekwueme; Chukwudike Onuoha; Ebube Prince Onuzulike; Wisdom Chibundu; Kooffreh Okon; Chibuike Christopher Ozoh (Environmental Science and Pollution Research, 2024)
The usage of plentiful raw discarded resources in the manufacturing of concrete has proven to be a sustainable and environmentally beneficial method of making concrete for a variety of purposes. In this study, the physical and mechanical properties of concrete made by partially and fully substituting fine aggregates and ordinary Portland cement with periwinkle shell ash and quarry dust (5%, 10%, 15%, 20%, and 100%), respectively, were examined. The ratio of water to cement utilized for the concrete mixture, 1:2:4, was 0.60. Fresh concrete underwent a slump test, and then 150-mm cubes of cured concrete were subjected to density, compressive strength tests, and morphological and structural property characterizations. The concrete without the waste materials gave an optimum compressive strength of 22.9 N/mm 2 as opposed to those that were partially replaced, having 18.8–15.1 N/mm 2 . The concrete samples with full replacements of periwinkle shell ash and quarry dust have compressive strengths lower than 13.8 N/mm 2 . All the concrete samples produced with partial and full replacements are in the class of normal concrete, but only those with partial replacements of up to 20% can be utilized for load-bearing and non-load-bearing applications. Opting for these alternative waste materials implies taking steps towards creating a cleaner and healthier planet for now and the future.

Bioaccumulation dynamics, noncarcinogenic and carcinogenic risks of heavy metals in commercially valuable shellfish and finfish species from the world largest floating slum, Makoko, Nigeria - Toheeb Lekan Jolaosho; Isa Olalekan Elegbede; Shehu Latunji Akintola; Abayomi Abdulazeez Jimoh; Prince Emeka Ndimele; Adejuwon Ayomide Mustapha; Joshua Damilola Adukonu (Marine Pollution Bulletin, 2024)

COP28 roadmap: Do ICT, education, and renewable energy consumption matter for environmental quality? Quantile evidence for emerging economies - Perekunah Bright Eregha; Solomon Prince Nathaniel; Xuan Vinh Vo (Journal of Cleaner Production, 2024)

Electric fields as effective strategies for enhancing quality attributes of meat in cold chain logistics: A review - Hengxun Lin; Guangyu Wu; Xiaojia Hu; Prince Chisoro; Chuan Yang; Qingqing Li; Christophe Blecker; Xia Li; Chunhui Zhang (Food Research International, 2024)

Cordia dichotoma fruit mucilage and flaxseed oil nanoemulsion loaded bioactive film: Synergistic approach to enhance antimicrobial properties and bread shelf-life - Mansuri M. Tosif; Sanju Bala Dhull; Nemat Ali; Muzaffar Iqbal; Abdullah F. AlAsmari; Prince Chawla (Food Bioscience, 2024)

We used to ‘chase the rains’ away in the past: the role of cultural values and beliefs in shaping farmers’ perceptions of climate variability and change in North-west Ghana - George Dakurah; Prince Osei-wusu Adjei; Henny Osbahr (Climate and Development, 2024)

Critical review on toxic contaminants in surface water ecosystem: sources, monitoring, and its impact on human health - Prince Kumar Singh; Umesh Kumar; Indrajeet Kumar; Akanksha Dwivedi; Priyanka Singh; Saumya Mishra; Chandra Shekhar Seth; Rajesh Kumar Sharma (Environmental Science and Pollution Research, 2024)

Navigating sustainable development: exploring the nexus of board attributes and environmental accounting information disclosure in China’s construction industry - Guanghui Chang; Ishmael Wiredu; Prince Kofi Boadu; Andrew Osei Agyemang (Environment, Development and Sustainability, 2024)

Emerging eco-friendly technologies for remediation of Per- and poly-fluoroalkyl substances (PFAS) in water and wastewater: A pathway to environmental sustainability - Timothy Prince Chidike Ezeorba; Emmanuel Sunday Okeke; Chidiebele Emmanuel Nwankwo; Stephen Chijioke Emencheta; Adebisi Esther Enochoghene; Veronica Chisom Okeke; Vincent E.O. Ozougwu (Chemosphere, 2024)

On the impact of soil texture on local scale organic carbon quantification: From airborne to spaceborne sensing domains - Vahid Khosravi; Asa Gholizadeh; Daniel Žížala; Radka Kodešová; Mohammadmehdi Saberioon; Prince Chapman Agyeman; Petra Vokurková; Anna Juřicová; Marko Spasić; Luboš Borůvka (Soil and Tillage Research, 2024)

Enhancing milk quality assessment with watermelon (Citrullus lanatus) urease immobilized on VS2-chitosan nanocomposite beads using response surface methodology - Prince Kumar; Divya; Amit Kumar Patel; Anchal Srivastava; Arvind M. Kayastha (Food Chemistry, 2024)

Enhancing functional attributes of rice protein concentrate through Aspergillus awamori MTCC 6652 assisted solid-state fermentation: Development of value-added vegan smoothie - Nikhil Dnyaneshwar Patil; Ankur Kumar; Kandi Sridhar; Prince Chawla; Minaxi Sharma (Food and Bioproducts Processing, 2024)

Effects of foliar selenium, biochar, and pig manure on cadmium accumulation in rice grains and assessment of health risk - Ofori Prince Danso; Zhangmin Wang; Zezhou Zhang; Shanshan Niu; Yuanqi Wang; Gege Wu; Xiaohu Wang; Li Zheng; Jun Dai; Xuebin Yin; Renbin Zhu (Environmental Research, 2024)

Ecological shock and time poverty: Evidence from northern Ghana - Edward Martey; Prince M. Etwire; Kwabena Krah (Environmental Development, 2024)

Application of seed mucilage as functional biopolymer in meat product processing and preservation - Xueqin Gao; Madhu Sharma; Aarti Bains; Prince Chawla; Gulden Goksen; Jian Zou; Wanli Zhang (Carbohydrate Polymers, 2024)

Green Synthesis, characterization, antimicrobial and anticancer properties of iron oxide nanoparticles mediated by Annona muricata (sour sop) leaf extract - Elias E. Elemike; Prince Joe Nna; Sophia C. Nzete; Damian C. Onwudiwe; Edjere Oghenekohwiroro; Moganavelli Singh; Ismail Hossain (Nanotechnology for Environmental Engineering, 2024)

Vulnerability of highways to landslide using landslide susceptibility zonation in GIS: Mandi district, India - Prince Tailey Jallayu; Abhishek Sharma; Kanwarpreet Singh (Innovative Infrastructure Solutions, 2024)

Mapping of on-field soil nutrient variabilities as a guiding force for smart farming: a case study from FarmerZone sentinel-1 from three potato agroecological zones of India - Portia D Singh; Jagdev Sharma; Prince Kumar; Srikant Srinivasan; Shyam Kumar Masakapalli (Environmental Monitoring and Assessment, 2024)

Clinical and Genomic Perspective of SARS CoV-2 Infection in Liver Disease Patients: A Single-Centre Retrospective Study - Reshu Agarwal; Arjun Bhugra; Pramod Gautam; Varun Suroliya; Ruchita Chhabra; Amit Pandey; Prince Garg; Pooja Rao; Rosmy Babu; Guresh Kumar; Chhagan Bihari; Debajyoti Bhattacharyya; et al. (Current Microbiology, 2024)

Salvia africana-lutea L.: a review of ethnobotany, phytochemistry, pharmacology applications and future prospects - Chinonso Anthony Ezema; Rita Ngozi Aguchem; Emmanuel Chigozie Aham; Wisdom Favour Chinedu Ezeorba; Innocent Uzochukwu Okagu; Timothy Prince Chidike Ezeorba (Advances in Traditional Medicine, 2024)
Plants are nature’s reserve for vitality and health-boosting agents. Despite ever-rising interest and research on plant medicinal chemistry, many stones are still being left unturned. Moreover, many traditional medicinal plants are yet to be discovered or functionally characterized. This study presented an up-to-date review of a poorly explored member of the Salvia genus indigenous to Africa— Salvia africana-lutea L. (synonymous with Salvia aurea L.) with details on its geographical distribution, ethnobotany, and pharmacological applications. We reviewed all literature published on Salvia africana-lutea up to January 2023, retrieved from PubMed, Scopus, and ScienceDirect as primary databases and google scholar as the secondary source. From our literature search, we found 38 documents published on S. africana-lutea , despite the popularity of the Salvia genus as a medicinal plant (having over 15,000 articles published to date). From the retrieved literature, only a few studies focused on exploiting the ethnobotanical features of the plants, such as the morphology, flowering and existence, and nature of its trichomes. Some studies have reported S. africana-lutea as an excellent source of essential oils trapped within their leaf trichomes with numerous phytochemicals and bioactivities. Other studies have reported some interesting pharmacological activities of plant extracts and isolated phytochemicals, such as their antimicrobial, anti-oxidative, analgesic, antipyretic, anticancer, cytotoxic, and other bioactivities. We identified some limitations of the few published studies, highlighting future research needs that should draw more scientific interest to foster more study on this under-explored and valuable plant species of Salvia , to harness its medicinal and industrial potential fully.

Removal and risk assessment of emerging contaminants and heavy metals in a wastewater reuse process producing drinkable water for human consumption - Prince Manyepa; Khalid Muzamil Gani; Mahomed Seyam; Ismail Banoo; Bettina Genthe; Sheena Kumari; Faizal Bux (Chemosphere, 2024)

Occurrence and ecotoxicological impacts of polybrominated diphenyl ethers (PBDEs) in electronic waste (e-waste) in Africa: Options for sustainable and eco-friendly management strategies - Emmanuel Sunday Okeke; Chidiebele Emmanuel Nwankwo; Timothy Prince Chidike Ezeorba; Veronica Chisom Iloh; Adebisi Esther Enochoghene (Toxicology, 2024)

Dolomite occurrence within drift deposits, Maldives archipelago - Kieron Prince; Juan Carlos Laya; David Budd; Cameron Joseph Manche; Carl Jacquemyn (Sedimentary Geology, 2024)

Natural dye-based sensor for monitoring temperature variation in storage for chicken patties - Suman Talukder; Sanjod Kumar Mendiratta; Ashim Kumar Biswas; Arup Ratan Sen; Immanuel Prince Devadason; Sagar Chand; Tanbir Ahmad; Devendra Kumar; Ravikant Agrawal; Ayon Tarafdar (Food Bioscience, 2024)

Incidental mortality of seabirds in trawl fisheries: A global review - Richard A. Phillips; Emma Fox; Rory Crawford; Stephanie Prince; Oliver Yates (Biological Conservation, 2024)

Circular bioeconomy in carbon footprint components of nonthermal processing technologies towards sustainable food system: A review - Aarti Bains; Kandi Sridhar; Sanju Bala Dhull; Prince Chawla; Minaxi Sharma; Prakash Kumar Sarangi; Vijai Kumar Gupta (Trends in Food Science & Technology, 2024)

Transportation bridge infrastructure asset condition monitoring using uncrewed aerial vehicles (UAVs) - Surya Sarat Chandra Congress; Anand J. Puppala; Jesse Escamilla; Raja Jaladurgam; Prince Kumar (Transportation Geotechnics, 2024)

Influence of dual succinylation and ultrasonication modification on the amino acid content, structural and functional properties of Chickpea (Cicer arietinum L.) protein concentrate - Nikhil Dnyaneshwar Patil; Aarti Bains; Sawinder Kaur; Rahul Yadav; Nemat Ali; Sandip Patil; Gulden Goksen; Prince Chawla (Food Chemistry, 2024)

The mollifying effect of Sambucus nigra extract on StAR gene expression, oxidative stress, and apoptosis induced by fenpropathrin in male rats - Marsail S. Nashed; Eman I. Hassanen; Marwa Y. Issa; Adel F. Tohamy; Abdelbary M. Prince; Ahmed M. Hussien; Maher M. Soliman (Food and Chemical Toxicology, 2024)

Localizing an underwater sensor node using sonar and establishing underwater wireless optical communication for data transfer applications - Jinka Venkata Aravind; Shanthi Prince (Marine Georesources & Geotechnology, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

The design and development of a dashboard for improving sustainable healthy food choices - Prince Agyemang; Ebenezer M. Kwofie; Jamie I. Baum; Dongyi Wang (Science of The Total Environment, 2024)

Association of tetrabromobisphenol A (TBBPA) with micro/nano-plastics: A review of recent findings on ecotoxicological and health impacts - Emmanuel Sunday Okeke; Timothy Prince Chidike Ezeorba; Yao Chen; Guanghua Mao; Weiwei Feng; Xiangyang Wu (Science of The Total Environment, 2024)

Technological advancement in the production of biohydrogen from lignocellulosic biomass: A review - Emisha L.; Prince D.; S.J. Vijay; Jebasingh Bhagavathsingh; Prathap Somu; Nagaraj Basavegowda; Dibyajyoti Haldar (Journal of Environmental Chemical Engineering, 2024)

Effect of dual modifications with ultrasonication and succinylation on Cicer arietinum protein-iron complexes: Characterization, digestibility, in-vitro cellular mineral uptake and preparation of fortified smoothie - Nikhil Dnyaneshwar Patil; Aarti Bains; Sawinder Kaur; Rahul Yadav; Gulden Goksen; Nemat Ali; Abdullah F. AlAsmari; Prince Chawla (Food Research International, 2024)

Preferential formation of uniform spherical vaterite by harnessing vortex flows and integrated CO2 capture and mineralization - Peilong Lu; Prince Ochonma; Rajashekhar Marthi; Shardul Dinesh Prabhu; Hassnain Asgar; Yong Lak Joo; Greeshma Gadikota (Chemical Engineering Journal, 2024)

Recent advances in biotechnological valorization of agro-food wastes (AFW): Optimizing integrated approaches for sustainable biorefinery and circular bioeconomy - Timothy Prince Chidike Ezeorba; Emmanuel Sunday Okeke; Mida Habila Mayel; Charles Ogugua Nwuche; Tobechukwu Christian Ezike (Bioresource Technology Reports, 2024)

Influence of the Keystone Grazer, Sesarma reticulatum, on the Hydrology and Organic Matter Cycling in Salt Marshes of the Southeastern USA - Elise S. Morrison; Thomas S. Bianchi; William F. Kenney; Mark Brenner; Kimberly Prince; Sydney Williams; Collin Ortals; Orlando Cordero; Sinéad M. Crotty; Christine Angelini (Estuaries and Coasts, 2024)
In salt marshes of the Southeastern USA, purple marsh crabs ( Sesarma reticulatum ), hereafter Sesarma , aggregate in grazing and burrowing fronts at the heads of tidal creeks, accelerating creek incision into marsh platforms. We explored the effects of this keystone grazer and sediment engineer on salt marsh sediment accumulation, hydrology, and carbon (C) and nitrogen (N) turnover using radionuclides ( 210 Pb and 7 Be), total hydrolyzable amino acids (THAA), and C and N stable isotopes (δ 13 C and δ 15 N) in sediment from paired Sesarma -grazed and un-grazed creeks. Sesarma -grazed-creek sediments exhibited greater bioturbation and tidal inundation compared to sediments in un-grazed creeks, as indicated by larger 210 Pb and 7 Be inventories. Total organic carbon (TOC) to total nitrogen (TN) weight ratios (C:N) were higher and δ 15 N values were lower in grazed-creek sediments than in un-grazed-creek sediments, suggesting Sesarma remove and assimilate N in their tissues, and excrete N with lower δ 15 N values into sediments. In support of this inference, the percent total carbon (TC) and percent TOC declined by nearly half, percent TN decreased by ~ 80%, and the C:N ratio exhibited a ~ threefold increase between Sesarma fore-gut and hind-gut contents. An estimated 91% of Sesarma ’s diet was derived from Spartina alterniflora, the region’s dominant salt marsh plant. We found that, as Sesarma grazing fronts progress across marsh landscapes, they enhance the decay of Spartina- derived organic matter and prolong marsh tidal inundation. These findings highlight the need to better account for the effects of keystone grazers and sediment engineers, like Sesarma , in estimates of the stability and size of blue C stores in coastal wetlands.

Groundwater potential modeling over the eastern part of Ghana’s Northern Region using evidence belief functions and weight of evidence - Eric Dominic Forson; Elikplim Abla Dzikunoo; Prince Ofori Amponsah; Aboagye Menyeh; Samuel Nunoo; Theophilus Yaw Amponsah (Earth Science Informatics, 2024)

Rapid and visual detection of Shiga-toxigenic Escherichia coli (STEC) in carabeef meat harnessing loop-mediated isothermal amplification (LAMP) - Govindarajan Bhuvana Priya; Ravi Kant Agrawal; Arockiasamy Arun Prince Milton; Madhu Mishra; Sanjod Kumar Mendiratta; Bhoj Raj Singh; Deepak Kumar; Ravi Kumar Gandham; Zunjar Baburao Dubal; Swaraj Rajkhowa; Ashish Luke; Girish Patil (Brazilian Journal of Microbiology, 2024)

Neutron transport methods for multiphysics heterogeneous reactor core simulation in Griffin - Zachary M. Prince; Joshua T. Hanophy; Vincent M. Labouré; Yaqi Wang; Logan H. Harbour; Namjae Choi (Annals of Nuclear Energy, 2024)

Methotrexate-induced intestine and nephrotoxicity attenuated by Andrographis paniculata via ameliorating oxidative stress, inflammation and apoptosis - Manisha Parthasarathy; Sabina Evan Prince (Advances in Traditional Medicine, 2024)

Missing phosphorus legacy of the Anthropocene: Quantifying residual phosphorus in the biosphere - Andrew J. Margenot; Shengnan Zhou; Suwei Xu; Leo M. Condron; Geneviève S. Metson; Philip M. Haygarth; Jordon Wade; Prince C. Agyeman (Global Change Biology, 2024)
A defining feature of the Anthropocene is the distortion of the biosphere phosphorus (P) cycle. A relatively sudden acceleration of input fluxes without a concomitant increase in output fluxes has led to net accumulation of P in the terrestrial‐aquatic continuum. Over the past century, P has been mined from geological deposits to produce crop fertilizers. When P inputs are not fully removed with harvest of crop biomass, the remaining P accumulates in soils. This residual P is a uniquely anthropogenic pool of P, and its management is critical for agronomic and environmental sustainability. Managing residual P first requires its quantification—but measuring residual P is challenging. In this review, we synthesize approaches to quantifying residual P, with emphasis on advantages, disadvantages, and complementarity. Common approaches to estimate residual P are mass balances, long‐term experiments, soil test P trends and chronosequences, with varying suitability or even limitations to distinct spatiotemporal scales. We demonstrate that individual quantification approaches are (i) constrained, (ii) often complementary, and (iii) may be feasible at only certain time–space scales. While some of these challenges are inherent to the quantification approach, in many cases there are surmountable challenges that can be addressed by unifying existing P pool and flux datasets, standardizing and synchronizing data collection on pools and fluxes, and quantifying uncertainty. Though defined as a magnitude, the distribution and speciation of residual P is relatively less understood but shapes its utilization and environmental impacts. The form of residual P will vary by agroecosystem context due to edaphoclimatic‐specific transformation of the accumulated P, which has implications for management (e.g., crop usage) and future policies (e.g., lag times in P loading from non‐point sources). Quantifying the uncertainty in measuring residual P holds value beyond scientific understanding, as it supports prioritization of monitoring and management resources and inform policy.

Biosynthesized silver nanoparticles prevent bacterial infection in chicken egg model and mitigate biofilm formation on medical catheters - Lipi Pradhan; Prince Sah; Malay Nayak; Anjali Upadhyay; Pragya Pragya; Shikha Tripathi; Gurmeet Singh; B. Mounika; Pradip Paik; Sudip Mukherjee (JBIC Journal of Biological Inorganic Chemistry, 2024)

Challenges and strategies for waste food anaerobic digestion: insights and future directions - Asma Musfira Shabbirahmed; Prathap Somu; Hsi-Hsien Yang; Samson Prince Hiruthyaswamy; Chetan Shekhar Karua; Akhilesh Kumar Yadav (Environment, Development and Sustainability, 2024)

Green synthesis of rice straw-derived silica nanoparticles by hydrothermal process for antimicrobial properties and effective degradation of dyes - Renu Kamboj; Aarti Bains; Minaxi Sharma; Ankit Kumar; Nemat Ali; Mohammad Khalid Parvez; Prince Chawla; Kandi Sridhar (Process Safety and Environmental Protection, 2024)

An explicit review and proposal of an integrated framework system to mitigate the baffling complexities induced by road dust-associated contaminants - Yuxiao Zhang; Alex Justice Frimpong; Jingning Tang; Isaac Oyeyemi Olayode; Sampson Kofi Kyei; Prince Owusu-Ansah; Philip Kwabena Agyeman; Jamshid Valiev Fayzullayevich; Gangfeng Tan (Environmental Pollution, 2024)

Development of a novel sensitive single-tube nested PCR assay for the detection of African swine fever virus - A. Arun Prince Milton; Samir Das; Kasanchi M. Momin; M. C.B. Prasad; Sabia Khan; G. Bhuvana Priya; Sandeep Ghatak; Arnab Sen; K. K. Baruah (Archives of Virology, 2024)

The impact of warming on food consumption - Prince Maxwell Etwire (Climate and Development, 2024)

Impacts of illegal Artisanal and small-scale gold mining on livelihoods in cocoa farming communities: A case of Amansie West District, Ghana - Peter Donkor; Ebenezer Kwadwo Siabi; Kwasi Frimpong; Prince Twum Frimpong; Samuel Kofi Mensah; Christopher Vuu; Elikplim Sarah Siabi; Emmanuel Kwasi Nyantakyi; Felix Agariga; Thomas Atta-Darkwa; Jacob Kofi Mensah (Resources Policy, 2024)

Synthesis of carbon quantum dots from waste Phaseolus vulgaris for the development of a fluorescence sensing probe to detect plasticizer in cookies - Sweezee Thakur; Aarti Bains; Baskaran Stephen Inbaraj; Kandi Sridhar; Anil Kumar; Mudasir Yaqoob; Nemat Ali; Mohammad Khalid Parvez; Prince Chawla; Minaxi Sharma (Process Safety and Environmental Protection, 2024)

Organic geochemical heterogeneity of cretaceous mudrocks and reassessment of oil sources in the Tano Basin, Ghana - Kojo Amoako; Ningning Zhong; Shengbao Shi; N'Guessan Francois De Sales Konan; Nancy Pearl Osei-Boakye; Gordon Foli; Prince Opoku Appau; Clifford Fenyi; Ebenezer Apesegah (Marine and Petroleum Geology, 2024)

Surface modification of toner-based recyclable iron oxide self-doped graphite nanocomposite to enhance methylene blue and tetracycline adsorption - Prince Oppong Amoh; Mahmoud Samy; Marwa Elkady; Hassan Shokry; Kenneth Mensah (Journal of Environmental Management, 2024)

Biomass valorization of liquid whey into carbon quantum dots via hydrothermal process for food pathogenic bactericidal activity and photocatalytic degradation of brilliant red dye - Sweezee Thakur; Aarti Bains; Anil Kumar; Gulden Goksen; Mudasir Yaqoob; Mohammad Khalid Parvez; Mohammed S. Al-Dosari; Prince Chawla (Food Bioscience, 2024)

Modelling the relationship between circular economy barriers and drivers for sustainable construction industry - Sulemana Fatoama Abdulai; Gabriel Nani; Ridwan Taiwo; Prince Antwi-Afari; Tarek Zayed; Adebayo Olatunbosun Sojobi (Building and Environment, 2024)

Recent variability and trends and projected changes in precipitation in the southeastern United States: a focus on the Apalachicola-Chattahoochee-Flint River Basin - Jeremy E. Diem; Prince Osei Bonsu (Theoretical and Applied Climatology, 2024)

Using geostatistics and machine learning models to analyze the influence of soil nutrients and terrain attributes on lead prediction in forest soils - Samuel Kudjo Ahado; Prince Chapman Agyeman; Luboš Borůvka; Radoslava Kanianska; Chukwudi Nwaogu (Modeling Earth Systems and Environment, 2024)

An effective underwater image enhancement based on the fusion of CLAHE and image constancy sharpening technique - Hena Prince; Binesh T (Earth Science Informatics, 2024)

Geochemical fingerprints and hydrocarbon potential of Paleocene mudrocks in the Tano Basin, Ghana: insights from biomarkers and stable carbon isotopes - Kojo Amoako; Nancy Pearl Osei-Boakye; Ningning Zhong; N’Guessan Francois De Sales Konan; Gordon Foli; Prince Opoku Appau; Clifford Fenyi; Ebenezer Apesegah (Acta Geochimica, 2024)

Latitudinal biodiversity gradients of rocky intertidal assemblages: Spatial scales and complex associations with environmental factors - Hadiyanto Hadiyanto; Jane Prince; Renae K. Hovey (Marine Ecology, 2024)
Latitudinal biodiversity gradients vary across taxonomic groups and spatial scales, and various environmental factors have been associated with those patterns. However, it remains unknown whether taxonomic groups with strong ecological associations have similar or different latitudinal patterns. Macroalgae are foundation assemblages on rocky intertidal shores and are often inhabited by invertebrates, predominantly polychaetes. This study analysed latitudinal patterns of macroalgae and their associated polychaetes at different spatial scales and determined how environmental factors influenced those patterns. Macroalgae and polychaetes were collected from transects within 38 rocky intertidal shores of Western Australia at 14 latitudes between 18° S and 34° S. Latitudinal gradients in species richness, diversity (Simpson's diversity index) and abundance were evaluated at transect, site and latitudinal scales. Relationships between environmental factors and rocky intertidal assemblages were analysed using piecewise structural equation modelling based on direct, indirect and complex models. Macroalgae showed increases in species richness, diversity and abundance at transect and site scales towards high latitudes, but species richness and diversity patterns were unclear at the latitudinal scale where transect and site data were pooled. In contrast, polychaete diversity decreased towards high latitudes, although this pattern was unclear at the transect scale. Polychaete richness and abundance tended to follow parabolic patterns that peaked at 27° S. Relationships between environmental factors and rocky intertidal assemblages were best described by a complex model, with significant relationships more often at transect and site scales. Sea surface temperatures showed the strongest relationship with macroalgal and polychaete distributions.

Mononuclear η6-arene ruthenium(II) complexes with pyrazolyl–pyridazine ligands: synthesis, CT-DNA binding, reactivity towards glutathione, and cytotoxicity - Amos K. Kanyora; Reinner O. Omondi; Peter Ongoma; Josiah O. Omolo; Athi Welsh; Sharon Prince; Joel Gichumbi; Allen Mambanda; Gregory S. Smith (JBIC Journal of Biological Inorganic Chemistry, 2024)

Improvement of qualitative and quantitative traits in cotton under normal and stressed environments using genomics and biotechnological tools: A review - Aarti Gupta; Manoj Kumar; Baohong Zhang; Maharishi Tomar; Amandeep Kaur Walia; Prince Choyal; Ravi Prakash Saini; Jayashree Potkule; David J. Burritt; Vijay Sheri; Pooja Verma; Deepak Chandran; et al. (Plant Science, 2024)

Soil-mustard revitalization via rice husk ash, a promising soil amendment material for sustainable management of heavy metal contamination in tropical ecosystem - Prince Kumar Singh; Indrajeet Kumar; Umesh Kumar; Rajesh Kumar Sharma (Journal of Environmental Management, 2024)

Exploring the effects of thermal and non-thermal modification methods on morphological, functional, and pasting properties of mung bean starch - Sanju Bala Dhull; Meenu Tanwar; Sunil Kumar Khatkar; Ankita Chandak; Prince Chawla; Gulden Goksen (Innovative Food Science & Emerging Technologies, 2024)

Corrigendum to “Development of a novel single-tube SYBR Green real-time PCR assay for simultaneous detection of Brucella spp. and Listeria monocytogenes by melt curve analysis” [International Dairy Journal 145 (2023) 105737] - A. Arun Prince Milton; M.C.B. Prasad; Kasanchi M. Momin; G. Bhuvana Priya; Zakir Hussain; Samir Das; Sandeep Ghatak; Arnab Sen (International Dairy Journal, 2024)

Health-promoting properties of bioactive proteins and peptides of garlic (Allium sativum) - Timothy Prince Chidike Ezeorba; Arinze Linus Ezugwu; Ifeoma Felicia Chukwuma; Emeka Godwin Anaduaka; Chibuike C. Udenigwe (Food Chemistry, 2024)

Reviving the absorbent chemistry of electrochemically mediated amine regeneration for improved point source carbon capture - Ahmad Hassan; Abdelrahman Refaie; Prince Aleta; Mohsen Afshari; Elmira Kalantari; Yuanyuan Fang; M. Mim Rahimi (Chemical Engineering Journal, 2024)

Rapid Drawdown Analysis Using Pore Pressures from BBM - Prince Turkson; Daniel R. VandenBerge (Geotechnical and Geological Engineering, 2024)

Screening of mustard cultivars for phytoremediation of heavy metals contamination in wastewater irrigated soil systems - Prince Kumar Singh; Jay Shankar Yadav; Indrajeet Kumar; Umesh Kumar; Rajesh Kumar Sharma (Environmental Monitoring and Assessment, 2024)

An integrated deep-learning model for smart waste classification - Shivendu Mishra; Ritika Yaduvanshi; Prince Rajpoot; Sharad Verma; Amit Kumar Pandey; Digvijay Pandey (Environmental Monitoring and Assessment, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Are unmanned aerial vehicle-based hyperspectral imaging and machine learning advancing crop science? - Alessandro Matese; Joby M. Prince Czarnecki; Sathishkumar Samiappan; Robert Moorhead (Trends in Plant Science, 2024)

Sustainable design and characterization of Aegle marmelos fruit nanomucilage-flaxseed oil nanoemulsion: Shelf-life of coated fresh-cut papaya - Madhu Sharma; Aarti Bains; Kandi Sridhar; Prakash Kumar Nayak; Prakash Kumar Sarangi; Nemat Ali; Sandip Patil; Prince Chawla; Minaxi Sharma (Sustainable Chemistry and Pharmacy, 2024)

Antibacterial and photocatalytic potential of bioactive compounds extracted from freshwater microalgae species (Spirogyra and Ocillatoria): A comparative analysis - Samriti Guleria; Prince Chawla; Ankush Relhan; Ashwani Kumar; Aparajita Bhasin; John L. Zhou (Science of The Total Environment, 2024)

Treatment of 2-naphthalene sulfonate by free and immobilized cells of indigenous isolate Comamonas sp. C2 and toxicity evaluation of biotransformed sample - Prince Dhammi; Satish Koundal; Sukanya Mehra; Pooja Chadha; Harvinder Singh Saini (International Biodeterioration & Biodegradation, 2024)

Examining the spatial and temporal variations in the indoor gaseous, PM2.5, BC concentrations in urban homes in India - Prince Vijay; Abhay Anand; Nidhi Singh; Tamara Schikowski; Harish C. Phuleria (Atmospheric Environment, 2024)

Occurrence, distribution, source apportionment, ecological and health risk assessment of heavy metals in water, sediment, fish and prawn from Ojo River in Lagos, Nigeria - Toheeb Lekan Jolaosho; Isa Olalekan Elegbede; Prince Emeka Ndimele; Taiwo Elijah Falebita; Opeyemi Yusuf Abolaji; Ibrahim Olawale Oladipupo; Faruq Enitan Ademuyiwa; Adejuwon Ayomide Mustapha; Zechariah Oluwapelumi Oresanya; Ogunkoya Oluwatobi Isaac (Environmental Monitoring and Assessment, 2024)

The puzzling etiologies of transient black discoloration in Nile Tilapia (Oreochromis niloticus) intensively cultured under RAS system - Alaa Eldin Eissa; Marwa M. Attia; Rabia A. El Zlitne; Ayad A. Magdy; Asmaa Edrees; Mahmoud S. Sharaf; Abeer E. Mahmoud; Awad A. Abdelbaky; Rehab R. Abd ElMaged; Elshaimaa Ismael; Rehab A. Qorany; Doaa F. El Moghazi; et al. (Aquaculture International, 2024)
The aim of this study is to identify the hidden etiologies of the black chromo-shifting transient phenomenon affecting Nile tilapia, Oreochromis niloticus , farmed in RAS-controlled ponds together with the assessment of the immunological reaction against the chronic irritating effects of the invasive agent. A total of 100 Nile Tilapia were collected from a private farm at Kafrelsheikh Province, located on the northern side of the Egyptian Nile Delta. The clinical history of the affected fish farm showed an unknown chromo-shifting phenomenon where tilapias were exhibiting severe black skin coloration, which gradually disappeared after removal from the tank’s water. A comprehensive gross examination of the collected fish; including parasitological examination of skin and gill scraps, was performed. Blood biochemical testing was performed on the infested blackish O. niloticus and control non-infested fish. The current study showed that the monogenean parasite, Gyrodactylus cichlidarum , was the abundant parasite detected in the infested fish leading to abnormal black discoloration of skin and disruption of the immune system represented by significant increase of cortisol levels, lysozyme activity and different liver enzymes compared to the control. Treatment trials have been applied with moderate degrees of success, where the monogenean count was sharply decreased, and the normal skin color was remarkably restored, at the end of day 14 post-treatment. A triple treatment plan was initiated through 7 days’ application of 0.7 g/m 3 copper sulfates pentahydrate preceded by 1.5 ml/m 3 hydrogen peroxide 40% solution for the same period. One day after the end of the initial treatment, a maintenance dosage of 0.095 ml/m 3 of glutaraldehyde (15%)/quaternary ammonium compounds (QACs) mixture was administered for 3 days. As a supportive/immune-stimulant regimen, a weekly dosage of vitamin C (0.45 g g/m 3 ) and Saccharomyces cerevisiae (0.45 g/m 3 ) was added into the tank’s water to improve the general fish health.

Valorization of food industrial waste: Green synthesis of carbon quantum dots and novel applications - Sweezee Thakur; Aarti Bains; Kandi Sridhar; Ravinder Kaushik; Prince Chawla; Minaxi Sharma (Chemosphere, 2024)

Co-location of fisheries and offshore wind farms: Current practices and enabling conditions in the North Sea - Prince Owusu Bonsu; Jonas Letschert; Katherine L. Yates; Jon C. Svendsen; Jörg Berkenhagen; Marcel J.C. Rozemeijer; Thomas R.H. Kerkhove; Jennifer Rehren; Vanessa Stelzenmüller (Marine Policy, 2024)

A preliminary predictive model for selenium nutritional status in residents based on three selenium biomarkers - Shanshan Niu; Zhangmin Wang; Xuebin Yin; Xiaodong Liu; Liqiang Qin; Muhammad Raza Farooq; Ofori Prince Danso; Zezhou Zhang; Qin Luo; Chenlu Sun; Jiaping Song (Journal of Trace Elements in Medicine and Biology, 2024)

Evaluation of Cladophora and Chlamydomonas microalgae for environmental sustainability: A comparative study of antimicrobial and photocatalytic dye degradation - Samriti Guleria; Halis Simsek; Prince Chawla; Ankush Relhan; Aparajita Bhasin (Environmental Pollution, 2024)

Novel helix loop-mediated isothermal amplification (HAMP) assay for colorimetric detection of Staphylococcus aureus in milk - A. Arun Prince Milton; M.C.B. Prasad; G. Bhuvana Priya; K.M. Momin; Vanita Lyngdoh; K. Srinivas; Samir Das; Sandeep Ghatak (World Journal of Microbiology and Biotechnology, 2024)

Entropy-Based Modelling for Flash Flood Hazard Mapping in Uttarakhand Himalaya - Harshith Clifford Prince; C. M. Bhatt; Arijit Roy; Shanti Kumari; Akhilesh Singh Raghubanshi; Raghavendra Pratap Singh (Journal of the Indian Society of Remote Sensing, 2024)

Soil health implications of some d-block metals in selected agricultural soils in Southeast Nigeria - Kokei Ikpi Ofem; Patrick Katan Kefas; Prince Okori Abam; Victoria Francis Ediene; Kingsley John; Mark Pawlett (Environmental Monitoring and Assessment, 2024)

Influence of monsoon extreme rainfall on the distribution of upper tropospheric humidity - M. V. Devika; Ajil Kottayil; Prajwal Koovekkallu; Prince Xavier; Viju John (International Journal of Climatology, 2023)
This study focuses on the changes in the upper tropospheric humidity (UTH) associated with two different extreme precipitation conditions for the period 2000–2019 over the Indian summer monsoon region. The analysis embodies UTH datasets derived from microwave sounders on‐board NOAA and MetOp‐A polar‐orbiting satellites. The circulation characteristics in the upper troposphere are studied using the high‐resolution ERA5 reanalysis data. The analysis of UTH variability over the Indian region shows a unique positive (negative) UTH anomaly patch extending from northwestern regions of India to the northern Arabian Sea for the enhanced (deficient) rainfall days over central India during the southwest monsoon period. The investigation reveals that deep convection alone does not impact the UTH variability. Rather the circulation in the upper troposphere also plays a crucial role in UTH distribution. The dynamics in the upper troposphere cause large‐scale dispersal of both wet and dry air in the upper troposphere, which is linked to the strengthening/weakening of Asian monsoon anticyclone. The study indicates that monsoon extremes exhibit a distinct moisture distribution pattern in the upper troposphere, influenced by upper‐level dynamics, which are associated with the intensity of the Asian monsoon anticyclone.

Performance evaluation of natural Olea europaea (olive oil)-based blended esters with butylated hydroxyanisole and butylated hydroxytoluene: optimization using response surface methodology - Hariharasudhan Thangaraj; Prince Winston David; Gurukarthik Babu Balachandran; Gowthama Kannan Sivasekar (Environmental Science and Pollution Research, 2023)

Valorization of onion peel waste: From trash to treasure - Aarti Bains; Kandi Sridhar; Brahma Nand Singh; Ramesh Chander Kuhad; Prince Chawla; Minaxi Sharma (Chemosphere, 2023)

Synergetic effects in the co-pyrolysis of lignocellulosic biomass and plastic waste for renewable fuels and chemicals - Wenfei Cai; Xiaofang Wang; Zhi Zhu; Reeti Kumar; Prince Nana Amaniampong; Jun Zhao; Zhong-Ting Hu (Fuel, 2023)

Estimation of the economic impacts and operational limitations imposed on unmanned aerial systems by poor sky conditions - Joby M. Prince Czarnecki; Jordan M. Shockley; Louis Wasson; Xiaofei Li (Precision Agriculture, 2023)

Tuber Yield and Incidence of Virus-Vectors in Late-Planted Seed Potato Crops in North-Western Plains of India - Prince Kumar; Raj Kumar; Mohd Abas Shah; Rajesh Kumar Singh; Ashwani Kumar Sharma; Raj Kumar; Vijay Kumar Dua (Potato Research, 2023)

Fertility implication of clay minerals in soils of three limestone geologic formations in southeastern Nigeria - Kokei Ikpi Ofem; Prince Okori Abam; Victoria Francis Ediene; Ene Emmanuel Aki; Sunday Marcus Afu; Egondu Charles Umeobi (Arabian Journal of Geosciences, 2023)

Silicon-based nanoparticles for mitigating the effect of potentially toxic elements and plant stress in agroecosystems: A sustainable pathway towards food security - Emmanuel Sunday Okeke; Ekene John Nweze; Tobechukwu Christian Ezike; Charles Ogugua Nwuche; Timothy Prince Chidike Ezeorba; Chidiebele Emmanuel Ikechukwu Nwankwo (Science of The Total Environment, 2023)

Impact of carbon footprint of bank loans and fossil fuel subsidies on ecological footprint in Tunisia: A contingency and asymmetric analysis - Maureen Ifeoma Iyke-Ofoedu; Nnenna G. Nwonye; Ishaku Prince Abner; Hillary Chijindu Ezeaku; Obinna Ubani (Journal of Cleaner Production, 2023)

Characterisation and rare-metal potential of the Winneba-Mankoadze pegmatites, Southern Ghana: Evidence of two pegmatite fields - Salaam Jansbaka Adams; Marieke Van Lichtervelde; Prince Ofori Amponsah; Prosper Mackenzie Nude; Daniel Kwadwo Asiedu; Samuel Boakye Dampare (Journal of African Earth Sciences, 2023)

Distribution and isotopic compositions of phenanthrene and methylphenanthrenes in crude oils: Implications for source input delineation and grouping oil families - N'Guessan Francois De Sales Konan; Meijun Li; Shengbao Shi; Abdulkareem Toyin; Andre Hyacinth Latyr Tine; Kojo Amoako; Prince Opoku Appau (Applied Geochemistry, 2023)

Air‐breathing behavior in Heterotis niloticus fingerlings: Response to changes in oxygen, temperature, and exercise regimes - Henry Owusu Adjei; Robert Yadama Laar; Prince Ofori‐Darkwah; Emmanuel Xorla Xatse; Jedida Osei Bediako; Peter Vilhelm Skov; Kwasi Adu Obirikorang (Journal of Fish Biology, 2023)
Air‐breathing in fish is believed to have arisen as an adaptation to aquatic hypoxia. Although air‐breathing has been widely studied in numerous fish species, little is known about the obligate air‐breathing African bonytongue, Heterotis niloticus . We evaluated if abiotic factors and physical activity affect air‐breathing patterns in fingerlings. The air‐breathing frequency ( f AB ) and behavioral responses of H. niloticus fingerlings were assessed in response to environmental oxygen, temperature, and exhaustion and activity in a series of experiments. The air‐breathing behavior of H. niloticus fingerlings under optimum water conditions was characterized by swift excursions lasting less than 1 s to the air–water interface to gulp air. The intervals between air‐breaths were highly variable, ranging from 3 to 259 s. Body size only slightly affected f AB , while hypoxia, hyperthermia, and exercise stress significantly increased f AB . Progressive hypoxia from 17.69 to 2.17 kPa caused a ~2.5‐fold increase in f AB . Increasing temperatures to 27 and 32°C, from a baseline temperature of 22°C, significantly increased f AB from 0.4 ± 0.2 to 1.3 ± 0.5 and 1.6 ± 0.4 breaths min −1 , respectively. Lastly, following exhaustive exercise, f AB increased up to 3‐fold. These observations suggest that H. niloticus fingerlings are very reliant on aerial oxygen, and their air‐breathing behavior is sensitive to environmental changes and activity levels.

Investigation of random noise in SYM-H and Dst during intense geomagnetic storms and solar quiet days of SC 23 using the method of potential analysis - Devi R Nair; P R Prince (Journal of Earth System Science, 2023)

Nature-Based Solutions (NBS) in spatial planning for urban flood mitigation: The perspective of flood management experts in Accra - Prince Asare; Funda Atun; Karin Pfeffer (Land Use Policy, 2023)

Mineral prospectivity mapping over the Gomoa Area of Ghana's southern Kibi-Winneba belt using support vector machine and naive bayes - Eric Dominic Forson; Prince Ofori Amponsah (Journal of African Earth Sciences, 2023)

Geospatial modelling of mineral potential zones using data-driven based weighting factor and statistical index techniques - Prince Ofori Amponsah; Eric Dominic Forson (Journal of African Earth Sciences, 2023)

Development of a novel single-tube SYBR Green real-time PCR assay for simultaneous detection of Brucella spp. and Listeria monocytogenes by melt curve analysis - A. Arun Prince Milton; M.C.B. Prasad; Kasanchi M. Momin; G. Bhuvana Priya; Zakir Hussain; Samir Das; Sandeep Ghatak; Arnab Sen (International Dairy Journal, 2023)

Deep learning-based framework for vegetation hazard monitoring near powerlines - Nana Ekow Nkwa Sey; Mark Amo-Boateng; Martin Kyereh Domfeh; Amos T. Kabo-Bah; Prince Antwi-Agyei (Spatial Information Research, 2023)

Zinc and L-carnitine combination with or without methotrexate prevents intestinal toxicity during arthritis treatment via Nrf2/Sirt1/Foxo3 pathways: an In vivo and molecular docking approach - Ramkumar Katturajan; Sabina Evan Prince (Inflammopharmacology, 2023)

Supporting regional co-operation in the South China Sea with an initial assessment of the data-limited skipjack tuna fishery - Jeremy Prince; Xuefeng Wang; Kun Lin; Ani Suryanti; Sallehudin Jamon; Mudjekeewis D. Santos; Francisco SB. Torres; Nicko Amor L. Flores; Vu Viet Ha; Tran Thi Ngoc Anh (Marine Policy, 2023)

Effects of nickel supplementation on nutrient utilization, mineral balance, haematology and antioxidant status of crossbred dairy calves - Shambhvi; Chander Datt; P. Thamizhan; Prince Chauhan; Kuldeep Dudi; Veena Mani (Journal of Trace Elements in Medicine and Biology, 2023)

Investing for a better tomorrow: Values-driven antecedents of investment in socially responsible equity funds by Indian retail investors - Anand Kumar Mishra; Rohit Bansal; Prince Kumar Maurya (Journal of Cleaner Production, 2023)

Interactions of legume phenols-rice protein concentrate towards improving vegan food quality: Development of a protein-phenols enriched fruit smoothie - GopikaJayaprakash; Prince Chawla; Kandi Sridhar; Aarti Bains (Food Research International, 2023)

Advances in therapeutic applications of silver nanoparticles - Ashutosh Kaushal; Isha Khurana; Poonam Yadav; Prince Allawadhi; Anil Kumar Banothu; Dinesh Neeradi; Sunitha Thalugula; Percy Jasmine Barani; Ramavath Redya Naik; Umashanker Navik; Kala Kumar Bharani; Amit Khurana (Chemico-Biological Interactions, 2023)

Probabilistic and deterministic-based approach for liquefaction potential assessment of layered soil - Prince Poddar; Sauhardra Ojha; Mohit Kumar Gupta (Natural Hazards, 2023)

Assessment of phytoplankton diversity, distribution, and environmental variables along the southeast coast of India - P. Sathish Kumar; G. Dharani; J. Santhanakumar; Dilip Kumar Jha; Vikas Pandey; S. Venkatnarayanan; J. Prince Prakash Jebakumar; C. Muthukumar; R. Arthur James (Frontiers in Marine Science, 2023)
Coastal waters are dynamic because of anthropogenic activities that contribute nutrients and contaminants. These changes have the potential to alter patterns of primary production and thus pelagic food webs. Here, we investigated the spatial variation of the phytoplankton community and its response to changing environmental variables at 84 stations along the five coastal districts of Tamil Nadu (TN). During the present study, 85 phytoplankton species were recorded, such as diatoms (64), dinoflagellates (18), silicoflagellates (1), and Cyanophyceae (2). The maximum phytoplankton abundance was recorded on the Thanjavur coast and gradually decreased towards the south coast of Tamil Nadu. Among the phytoplankton community, 50% was dominated by pennate diatoms, attributed to higher NO 3 − concentrations in the coastal waters due to agricultural discharge. Cluster analysis revealed that Ramanathapuram and Tirunelveli formed a closed cluster, whereas Thanjavur and Pudukottai formed a separate closed cluster associated with higher nutrient and metal concentrations, highlighting the difference in physicochemical parameters between the northern and southern districts of the TN coast. Relatively high nutrient concentrations in the coastal waters of northern districts are of greater concern, which could impact the coastal ecosystem. Coastal eutrophication is becoming a widespread phenomenon, causing disruption in the food chain and ecosystem balances and hence requiring regular monitoring and management.

Dioxin emission modeling using feature selection and simplified DFR with residual error fitting for the grate-based MSWI process - Heng Xia; Jian Tang; Loai Aljerf; Canlin Cui; Bingyin Gao; Prince Onyedinma Ukaogo (Waste Management, 2023)

Prevalence of bovine tuberculosis and analysis of risk factors among the dairy farms in and around Guwahati metropolitan city, India - Nur Abdul Kader; Razibuddin Ahmed Hazarika; Mosuri Chendu Bharat Prasad; Srinivas Kandhan; A. Arun Prince Milton; Durlav Prasad Bora; Nagendra Nath Barman; Archana Talukdar; Sarat Sonowal; Sandeep Ghatak; Johanna F. Lindahl; Samir Das (Research in Veterinary Science, 2023)

The longitudinal dependence of SEP events on associated Solar Flare parameters - M.S. Biji; P.R. Prince (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Molecular and isotopic signatures of indigenous and non-indigenous hydrocarbons in Campanian sediments from the Tano Basin, Ghana - Kojo Amoako; Zhong Ningning; Nancy Pearl Osei-Boakye; N'Guessan Francois De Sales Konan; Gordon Foli; Prince Opoku Appau; Ebenezer Apesegah (Applied Geochemistry, 2023)

Concentrating to avoid falling: interaction between peripheral sensory and central attentional demands during a postural stability limit task in sedentary seniors - Marie Julie Vermette; François Prince; Louis Bherer; Julie Messier (GeroScience, 2023)

Socio-cultural beliefs on drought in Talensi Ghana: insights for environmental management, social vulnerability, early warning systems and coping and adaptation - Peter Dok Tindan; Alexander Yao Segbefia; Divine Odame Appiah; Jones Opoku-Ware; Prince Osei-Wusu Adjei (Environment, Development and Sustainability, 2023)

Screening for antimicrobial residues in poultry eggs in Bangladesh using Charm II radio-receptor assay technique following validation - Darmin Chakma; Md. Maruf Billah Prince; Md. Hedayetul Islam; E. M. Tanvir; Md. Mahamodun Nabi; Wim Reybroeck; James Jacob Sasanya; M. Jahurul Islam; Md. Nazrul Islam; Md. Shahabe Uddin Talukder; Chironjit Kumar Shaha; M. A. Mannan; et al. (Food Additives & Contaminants Part B-Surveillance, 2023)

Hazardous impacts of glyphosate on human and environment health: Occurrence and detection in food - Deeksha Rawat; Aarti Bains; Prince Chawla; Ravinder Kaushik; Rahul Yadav; Anil Kumar; Kandi Sridhar; Minaxi Sharma (Chemosphere, 2023)

Field fluorometers for assessing oil dispersion at sea - Charbel Abou-Khalil; Wen Ji; Roger C. Prince; Gina M. Coelho; Tim J. Nedwed; Kenneth Lee; Michel C. Boufadel (Marine Pollution Bulletin, 2023)

Assessment of PCDD/Fs formation and emission characteristics at a municipal solid waste incinerator for one year - Heng Xia; Jian Tang; Loai Aljerf; Tianzheng Wang; Bingyin Gao; Qindong Xu; Qiang Wang; Prince Ukaogo (Science of The Total Environment, 2023)

L-carnitine and Zinc supplementation impedes intestinal damage in methotrexate-treated adjuvant-induced arthritis rats: Reinstating enterocyte proliferation and trace elements - Ramkumar Katturajan; Sabina Evan Prince (Journal of Trace Elements in Medicine and Biology, 2023)

Microbial responses to increased salinity in oiled upper tidal shorelines - Charbel Abou-Khalil; Nathalie Fortin; Jessica Wasserscheid; Roger C. Prince; Charles W. Greer; Kenneth Lee; Michel C. Boufadel (International Biodeterioration & Biodegradation, 2023)

A multi-dimensional assessment of sustainable foods and the influence of stakeholder perceptions during nutrition interventions - Prince Agyemang; Ebenezer Miezah Kwofie; Raphael Aidoo; Derrick Kpakpo Allotey; Michael Ngadi (Food Policy, 2023)

Mitigation pathways towards climate change: Modelling the impact of climatological factors on wheat production in top six regions of China - Abbas Ali Chandio; Devi Prasad Dash; Solomon Prince Nathaniel; Ghulam Raza Sargani; Yuansheng Jiang (Ecological Modelling, 2023)

Enhancing life cycle assessment for circular economy measurement of different case scenarios of modular steel slab - Prince Antwi-Afari; S. Thomas Ng; Ji Chen; Benjamin I. Oluleye; Maxwell F. Antwi-Afari; Benjamin K. Ababio (Building and Environment, 2023)

Global prevalence of setting longlines at dawn highlights bycatch risk for threatened albatross - David Kroodsma; Joanna Turner; Cian Luck; Tim Hochberg; Nathan Miller; Philip Augustyn; Stephanie Prince (Biological Conservation, 2023)

Experimental study of bifacial photovoltaic module with waste polyvinyl chloride flex and acrylonitrile butadiene styrene road side safety sticker as an alternative reflector: optimization using response surface methodology - Hariharasudhan Thangaraj; Prince Winston David; Gurukarthik Babu Balachandran; Pravin Murugesan (Environmental Science and Pollution Research, 2023)

Asymmetric effect of environmental tax on CO2 emissions embodied in domestic final demand in developing economies: A panel NARDL approach - Chika A. Anisiuba; Ishaku Prince Abner; Charles Ogechukwu Ugbam; Sylvester Ebosetale Okoebor; Hillary Chijindu Ezeaku (Environment, Development and Sustainability, 2023)

Sustainability and affordability of Chinese-funded renewable energy project in sub-Saharan Africa: a hybridized solid oxide fuel cell, temperature sensors, and lithium-based solar system approach - Prince Opoku; Huaming Song (Environmental Science and Pollution Research, 2023)

Corrigendum to “Plasma concentrations of per- and polyfluoroalkyl substances are associated with perturbations in lipid and amino acid metabolism” [Chemosphere 324 (2023)138228] - Nicole Prince; Sofina Begum; Lidia Mínguez-Alarcón; Maximilien Génard-Walton; Mengna Huang; Djøra I. Soeteman; Craig Wheelock; Augusto A. Litonjua; Scott T. Weiss; Rachel S. Kelly; Jessica Lasky-Su (Chemosphere, 2023)

Phytochemistry of plants in the genus Vepris: A review and in silico analysis of their ADMET properties - Prince Ojuka; Njogu M. Kimani; Seth Apollo; James Nyariki; Ryan S. Ramos; Cleydson B.R. Santos (South African Journal of Botany, 2023)

Green metal price volatility and environmentally sustainable real estate development nexus: A global perspective from post COVID-19 pandemic - Grace Chinyere Eje; Ishaku Prince Abner; Hillary Chijindu Ezeaku (Journal of Cleaner Production, 2023)

Detrital zircon geochronology of quartzites from the Central Zone of the Limpopo Complex in southern Africa: Implications for different models and the timing of Zimbabwe Craton–Kaapvaal Craton amalgamation - Thembiso O. Basupi; Toshiaki Tsunogae; Kazuki Takahashi; Yusuke Takamura; Prince Mandingaisa; Yukiyasu Tsutsumi (Journal of African Earth Sciences, 2023)

Effects of the breeding season, birth type and sex on growth and reproductive performances of sheep breeds - Soul Washaya; Uaipo Ngorio; Clarice Princes Mudzengi (Tropical Animal Health and Production, 2023)

Structural variation among assembled genomes facilitates development of rapid and low-cost NOR-linked markers and NOR-telomere junction mapping in Arabidopsis - Gargi Prasad Saradadevi; Dalen Fultz; Murali Krishna Ramgopal; Abirami T. Subramanian; Gerin Prince; Vivek Thakur; Gireesha Mohannath (Plant Cell Reports, 2023)

CADNet: an advanced architecture for automatic detection of coronary artery calcification and shadow border in intravascular ultrasound (IVUS) images - Priyanka Arora; Parminder Singh; Akshay Girdhar; Rajesh Vijayvergiya; Prince Chaudhary (Physical and Engineering Sciences in Medicine, 2023)

Frequency ratio-based flood vulnerability modeling over the greater Accra Region of Ghana - Eric Dominic Forson; Prince Ofori Amponsah; Godfred Bright Hagan; Marian Selorm Sapah (Modeling Earth Systems and Environment, 2023)

Correction to: Vegetation attributes drive the taxonomic richness and functional composition of beetles and spiders in mountainous urban green spaces - Frederick Gyasi Damptey; Bernard Fosu Frimpong; Daniel Kwame Debrah; Prince Pascal Agro; Edward Debrah Wiafe (Energy, Ecology and Environment, 2023)

An empirical assessment of the tripartite nexus between environmental pollution, economic growth, and agricultural production in Sub-Saharan African countries - Ernest Baba Ali; Bright Akwasi Gyamfi; Festus Victor Bekun; Ilhan Ozturk; Prince Nketiah (Environmental Science and Pollution Research, 2023)

Overhauling the ecotoxicological impact of synthetic pesticides using plants’ natural products: a focus on Zanthoxylum metabolites - Innocent Uzochukwu Okagu; Emmanuel Sunday Okeke; Wisdom Chinedu Favour Ezeorba; Joseph Chinedum Ndefo; Timothy Prince Chidike Ezeorba (Environmental Science and Pollution Research, 2023)
The reduction in agricultural production due to the negative impact of insects and weeds, as well as the health and economic burden associated with vector-borne diseases, has promoted the wide use of chemicals that control these “enemies.” However, the use of these synthetic chemicals has been recognized to elicit negative impacts on the environment as well as the health and wellbeing of man. In this study, we presented an overview of recent updates on the environmental and health impacts of synthetic pesticides against agro-pest and disease vectors while exhaustive reviewing the potentials of natural plant products from Zanthoxylum species ( Rutaceae ) as sustainable alternatives. This study is expected to spur further research on exploiting these plants and their chemicals as safe and effective pesticide entities to minimize the impact of their chemical and synthetic counterparts on health and the environment. Graphical abstract

Plasma concentrations of per- and polyfluoroalkyl substances are associated with perturbations in lipid and amino acid metabolism - Nicole Prince; Sofina Begum; Lidia Mínguez-Alarcón; Maximilien Génard-Walton; Mengna Huang; Djøra I. Soeteman; Craig Wheelock; Augusto A. Litonjua; Scott T. Weiss; Rachel S. Kelly; Jessica Lasky-Su (Chemosphere, 2023)

Post-fifth assessment report urban climate planning: Lessons from 278 urban climate action plans released from 2015 to 2022 - Prince Dacosta Aboagye; Ayyoob Sharifi (Urban Climate, 2023)

Modeling the principal success factors for attaining systemic circularity in the building construction industry: An international survey of circular economy experts - Benjamin I. Oluleye; Daniel W.M. Chan; Prince Antwi-Afari; Timothy O. Olawumi (Sustainable Production and Consumption, 2023)

Further to quantification of content, can reflectance spectroscopy determine the speciation of cobalt and nickel on a mine waste dump surface? - Vahid Khosravi; Asa Gholizadeh; Prince Chapman Agyeman; Faramarz Doulati Ardejani; Saeed Yousefi; Mohammadmehdi Saberioon (Science of The Total Environment, 2023)

153 Comparison of cortisol concentrations between traditional group therapy and equine assisted psychotherapy for substance use disorder residential treatment patients - M. Friend; E. Farnlacher; K. Holtcamp; M. Nicodemus; R. Swanson; C. Lemley; C. Cavinder; P. Prince (Journal of Equine Veterinary Science, 2023)

Consuming oral cannabidiol prior to a standard alcohol dose has minimal effect on breath alcohol level and subjective effects of alcohol - Hollis C. Karoly; Meggan L. Drennan; Mark A. Prince; Leila Zulic; Gregory Dooley (Psychopharmacology, 2023)

Combination of enrichment factor and positive matrix factorization in the estimation of potentially toxic element source distribution in agricultural soil - Prince Chapman Agyeman; Kingsley John; Ndiye Michael Kebonye; Luboš Borůvka; Radim Vašát (Environmental Geochemistry and Health, 2023)

Effects of nodding broomrape parasitism on growth, physio-biochemical changes and yield loss of Withania somnifera (Linn.) Dunal plant - Kuldeepsingh A. Kalariya; Deepa Shahi; Parmeshwar Lal Saran; Ram Prasnna Meena; Narendra Gajbhiye; Prince Choyal; Satyajit Roy (Vegetos, 2023)

Segmentation of OECD countries on the basis of selected global environmental indicators using k-means non-hierarchical clustering - Pallavi Kudal; Amitabh Patnaik; Sunny Dawar; Raj Kumar Satankar; Prince Dawar (Environmental Science and Pollution Research, 2023)

Modeling geostatistical incomplete spatially correlated survival data with applications to COVID-19 mortality in Ghana - Prince Addo Allotey; Ofer Harel (Spatial Statistics, 2023)

Recovery of agricultural waste biomass: A path for circular bioeconomy - Pardeep Kumar Sadh; Prince Chawla; Suresh Kumar; Anamika Das; Ravinder Kumar; Aarti Bains; Kandi Sridhar; Joginder Singh Duhan; Minaxi Sharma (Science of The Total Environment, 2023)

Seven years of United Nations’ sustainable development goals in Africa: A bibliometric and systematic methodological review - Prince Gyimah; Kingsley Opoku Appiah; Kwadjo Appiagyei (Journal of Cleaner Production, 2023)

On exploring bivariate and trivariate maps as visualization tools for spatial associations in digital soil mapping: A focus on soil properties - Ndiye M. Kebonye; Prince C. Agyeman; Zibanani Seletlo; Peter N. Eze (Precision Agriculture, 2023)

Bioactivity of Zanthoxylum armatum fruit extract against Spodoptera frugiperda and Tuta absoluta - Dnyaneshwar M. Firake; Rituparna Ghosh; Manish Kumar; Arockiasamy Arun Prince Milton; Raj Kumari Sanjukta; Gajanan T. Behere; Sagar Pandit (Journal of Plant Diseases and Protection, 2023)

Experimental and numerical analysis of the under-reamed piled ring foundation - Prince Karandeep Singh Sandhu; Arvind Kumar (Marine Georesources & Geotechnology, 2023)

A baseline study of Fiji’s small-scale lobster fishery using value chain analysis and size at maturity thresholds - Max Tukana; Jeremy Prince; Kerstin B.J. Glaus; Kalisiana Marama; Cherie Whippy-Morris (Marine Policy, 2023)

Prediction of the concentration of cadmium in agricultural soil in the Czech Republic using legacy data, preferential sampling, Sentinel-2, Landsat-8, and ensemble models - Prince Chapman Agyeman; Luboš Borůvka; Ndiye Michael Kebonye; Vahid Khosravi; Kingsley John; Ondrej Drabek; Vaclav Tejnecky (Journal of Environmental Management, 2023)

The photometric observation of the quasi-simultaneous mutual eclipse and occultation between Europa and Ganymede on 22 August 2021 - Chu Wing So; Godfrey Ho Ching Luk; Giann On Ching Chung; Po Kin Leung; Kenneith Ho Keung Hui; Jack Lap Chung Cheung; Ka Wo Chan; Edwin Lok Hei Yuen; Lawrence Wai Kwan Lee; Patrick Kai Ip Lau; Gloria Wing Shan Cheung; Prince Chun Lam Chan; et al. (Icarus, 2023)

Drought stress impact on agronomic, shoot, physiological, canning and nutritional quality traits of navy beans (Phaseolus vulgaris L.) under field conditions in Zimbabwe - Bruce Mutari; Julia Sibiya; Prince M. Matova; Edmore Gasura; Kennedy Simango (Field Crops Research, 2023)

Groundwater prospectivity modeling over the Akatsi Districts in the Volta Region of Ghana using the frequency ratio technique - Prince Ofori Amponsah; Eric Dominic Forson; Prospera Sungpour Sungzie; Yvonne Sena Akosuah Loh (Modeling Earth Systems and Environment, 2023)

Using an innovative bivariate colour scheme to infer spatial links and patterns between prediction and uncertainty: an example based on an explainable soil CN ratio model - Ndiye M. Kebonye; Prince C. Agyeman; James K. M. Biney (Modeling Earth Systems and Environment, 2023)

miRNA dysregulation in traumatic brain injury and epilepsy: a systematic review to identify putative biomarkers for post-traumatic epilepsy - Prince Kumar (Metabolic Brain Disease, 2023)

Compositional mapping, uncertainty assessment, and source apportionment via pollution assessment-based receptor models in urban and peri-urban agricultural soils - Prince Chapman Agyeman; Ndiye Michael Kebonye; Kingsley John; Hamed Haghnazar; Luboš Borůvka; Radim Vašát (Journal of Soils and Sediments, 2023)

Towards Circular Economy and Local Economic Development in Ghana: Insights from the Coconut Waste Value Chain - Benjamin Doe; Prince Dacosta Aboagye; Paa Kofi Osei-Owusu; Theophilus Amoah; Andrews Aidoo; Nana Yaa Amponsah (Circular Economy and Sustainability, 2023)

Novel sensitive isothermal-based diagnostic technique for the detection of African swine fever virus - A. Arun Prince Milton; Samir Das; Sabia Khan; K. M. Momin; C. B. Prasad; H. Kylla; Sandeep Ghatak; Arnab Sen (Archives of Virology, 2023)

A hybrid deep leaning model for prediction and parametric sensitivity analysis of noise annoyance - Shashi Kant Tiwari; Lakshmi Annamalai Kumaraswamidhas; Prince; Mustafa Kamal; Masood ur Rehman (Environmental Science and Pollution Research, 2023)

Public health implications of endocrine disrupting chemicals in drinking water and aquatic food resources in Nigeria: A state-of-the-science review - Oju R. Ibor; Prince Nnadozie; Dinah M. Ogarekpe; Omokhudu Idogho; Jennifer Anyanti; Dennis Aizobu; Chinedu Onyezobi; Azubuike V. Chukwuka; Aina O. Adeogun; Augustine Arukwe (Science of The Total Environment, 2023)

Gully erosion susceptibility mapping using four machine learning methods in Luzinzi watershed, eastern Democratic Republic of Congo - Géant Basimine Chuma; Yannick Mugumaarhahama; Jean Mubalama Mond; Espoir Mukengere Bagula; Adrien Byamungu Ndeko; Prince Baraka Lucungu; Katcho Karume; Gustave Nachigera Mushagalusa; Serge Schmitz (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Blockchain technology adaptation for land administration services: The importance of socio-cultural elements - Prince Donkor Ameyaw; Walter Timo de Vries (Land Use Policy, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs): A current insight into its molecular mechanism eliciting organ toxicities - Nagesh Kishan Panchal; Evan Prince Sabina (Food and Chemical Toxicology, 2023)

Investigation on dioxins emission characteristic during complete maintenance operating period of municipal solid waste incineration - Heng Xia; Jian Tang; Loai Aljerf; Tianzheng Wang; Junfei Qiao; Qindong Xu; Qiang Wang; Prince Ukaogo (Environmental Pollution, 2023)

Potential use of Tinospora cordifolia as a herbal supplement in dairy animals: a review - Rajneesh Rajneesh; A. K. Misra; Shwetambri Jamwal; S. Praveen; Jyotimala Sahu; Prince Chauhan; Ninad Bhatt (Tropical Animal Health and Production, 2023)

Exploring key drivers of forest fires in the Mole National Park of Ghana using geospatial tools - Martin Kyereh Domfeh; Nana Ekow Nkwa Sey; Amprofi Ampah Amproche; Eric Mensah Mortey; Prince Antwi-Agyei; Emmanuel Kwesi Nyantakyi (Spatial Information Research, 2023)

The stock assessment theory of relativity: deconstructing the term “data-limited” fisheries into components and guiding principles to support the science of fisheries management - Jason M. Cope; Natalie A. Dowling; Sybrand A. Hesp; Kristen L. Omori; Pia Bessell-Browne; Leandro Castello; Rowan Chick; Dawn Dougherty; Steven J. Holmes; Richard McGarvey; Daniel Ovando; Josh Nowlis; et al. (Reviews in Fish Biology and Fisheries, 2023)

Adopting Artificial Intelligence for enhancing the implementation of systemic circularity in the construction industry: A critical review - Benjamin I. Oluleye; Daniel W.M. Chan; Prince Antwi-Afari (Sustainable Production and Consumption, 2023)

Optimal zinc level and uncertainty quantification in agricultural soils via visible near-infrared reflectance and soil chemical properties - Prince Chapman Agyeman; Ndiye Michael Kebonye; Vahid Khosravi; John Kingsley; Luboš Borůvka; Radim Vašát; Charles Mario Boateng (Journal of Environmental Management, 2023)

A half century of oil spill dispersant development, deployment and lingering controversy - Roger C. Prince (International Biodeterioration & Biodegradation, 2023)

Prediction of the concentration of antimony in agricultural soil using data fusion, terrain attributes combined with regression kriging - Prince Chapman Agyeman; John Kingsley; Ndiye Michael Kebonye; Vahid Khosravi; Luboš Borůvka; Radim Vašát (Environmental Pollution, 2023)

Transmission of viruses and other pathogenic microorganisms via road dust: Emissions, characterization, health risks, and mitigation measures - Frimpong J. Alex; Gangfeng Tan; Sampson K. Kyei; Prince O. Ansah; Philip K. Agyeman; Jamshid V. Fayzullayevich; Isaac O. Olayode (Atmospheric Pollution Research, 2023)

Objective determination of the winter monsoon onset dates and its interannual variability in Malaysia - Sheeba Nettukandy Chenoli; Jeong Yik Diong; Mohd Fadzil Firdzaus Mohd Nor; Weng Sang Yip; Prince Xavier; Nursalleh K. Chang; Azizan Abu Samah (International Journal of Climatology, 2022)
The northeast/winter monsoon over Malaysia often leads to extreme rainfall events and floods over the windward side of terrain due to the strong northeasterly winds. Comparatively, much less rain falls over the other are sheltered by the mountain ranges. Based on this consideration, the onset of monsoon in the region is best determined operationally using 925 hPa winds. Therefore, we propose the first, simple, single‐variable‐based method to determine the onset dates of winter monsoon is yet reliable and can be closely monitored for operational purposes. The onset date is defined in the third pentad when the average of three pentads of 925 hPa northerly wind speed is greater than 1 m·s −1 , and at least one of three pentads must be greater than 2.5 m·s −1 . The study also investigates the relationship between the interannual variability of onset date and El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). Late‐onset can be expected when La Niña develops in the boreal fall season. However, a similar association between monsoon onset and El Niño condition was not observed. The lead–lag correlation between the IOD and the onset dates shows that the onset is significantly negatively correlated with the IOD. During negative (positive) IOD events, a delay (early) onset is expected. Results also show that the relationship between the onset and IOD is more robust and linear than the ENSO.

Satellite-based estimates of photosynthetically active radiation for tropical ecosystems in Ghana—West Africa - Prince Asilevi Junior; Emmanuel Quansah; Felicia Dogbey (Tropical Ecology, 2022)

Nature green with avarice and greed - Roger C. Prince; Graham N. George; Amy L. Stevens (Plant Physiology Reports, 2022)

New insights into the taxonomy of duiker antelopes (Artiodactyla: Bovidae) from the eastern Democratic Republic of the Congo, with the formal description of a new genus - Eva V. Bärmann; Vera G. Fonseca; Kathrin Langen; Prince Kaleme (Mammalian Biology, 2022)

Trichopus zeylanicus ameliorates ibuprofen inebriated hepatotoxicity and enteropathy: an insight into its modulatory impact on pro/anti-inflammatory cytokines and apoptotic signaling pathways - Nagesh Kishan Panchal; Purushotham Swarnalatha; Sabina Evan Prince (Inflammopharmacology, 2022)

Impact of economic policy uncertainty, energy intensity, technological innovation and R&D on CO2 emissions: evidence from a panel of 18 developed economies - Prince Asare Vitenu-Sackey; Theophilus Acheampong (Environmental Science and Pollution Research, 2022)
This study examines the impact of economic policy uncertainty (EPU) and ecological innovation on carbon (CO 2 ) emissions in a panel of 18 developed countries from 2005 to 2018 using second-generation time-series panel data techniques. We use three robust long-run estimators, namely two-stage least squares (2SLS), panel generalised method of moments (GMM) and generalised least squares (GLS), to resolve heterogeneity, endogeneity and simultaneity in the panels. We further performed causality tests to ascertain the direction of causality between the variables. Our estimations suggest three innovative findings. First, economic growth contributes significantly and positively to CO 2 emissions; however, this happens at an optimal level of growth after which carbon emission reduces, indicating that our sample exhibits an inverted U-shaped environmental Kuznets curve (EKC) relationship. Second, the impact of EPU on CO 2 emissions is diverse: high levels of EPU have a significant influence on CO 2 emissions only in high-polluting countries but not in low-polluting ones. Thirdly, research and development (R&D), foreign direct investment (FDI), urbanisation and renewable energy (RE) usage were also found to have varying effects on CO 2 emissions. These findings highlight the heterogeneous relationship between carbon emissions and economic indicators even in advanced economies, as the pollution haven hypothesis (PHH) holds true in high-pollution countries while the pollution halo effect holds for low-pollution ones. A key policy implication of this work is that the quest to mitigate emissions should not be a one-size-fits-all approach because not every country’s urbanisation rate, FDI inflows, R&D and renewable energy consumption directly affect CO 2 emissions in the face of economic policy uncertainties.

Does bootstrapping the remainder component of seasonal time series improve forecasting using SARIMA model? An application to rainfall data - Prince Mensah Osei (Modeling Earth Systems and Environment, 2022)

Military spending, financial development, and ecological footprint in a developing country: insights from bootstrap causality and Maki cointegration - Perekunah B. Eregha; Xuan Vinh Vo; Solomon Prince Nathaniel (Environmental Science and Pollution Research, 2022)

Standard histological techniques systematically under‐estimate the size fish start spawning - Jeremy Prince; William J. Harford; Brett M. Taylor; Steven J. Lindfield (Fish and Fisheries, 2022)
Beverton & Holt's (1957) functional definition of maturity in fish ( L 50 ), as being the size class in which 50% of individuals begin producing gametes in some proportion to body weight, is widely used in assessment models to estimate spawning stock biomass, and manage the minimum size of capture. Standardized histological techniques for estimating L 50 apply physiological definitions that identify cellular or hormonal markers indicating individuals are capable of producing gametes. Few studies have examined how those phases of gonadal development correlate with reproductive behaviour or reproductive output. We compare histological estimates of L 50 for 10 species of reef fish from Palau, with the size composition of catches, surveys and spawning aggregations, and interpret those comparisons with simulation modelling. Our study shows that the histological L 50 estimates coincide with the size species begin ontogenetically shifting between juvenile and adult habitat, and with the size the smallest individuals join spawning aggregations, but are ~15% smaller than the length at which we infer 50% of individuals begin joining spawning aggregations. This highlights a mismatch between the functional definition of L 50 assumed for assessment and management, and the physiological definitions developed for histological studies, which identify the beginning of a sub‐adult adolescent phase, rather than the end, when functional adulthood starts. This definitional mismatch could be causing stock assessments to systematically over‐estimate the reproductive output of fisheries. By considering fish behaviour, we hope to better align estimates of physiological maturation with the estimation of functional reproductive potential required for assessment and management.

Emerging pollutants: impact on environment, management, and challenges - S. Krishnakumar; D. Satheesh Herbert Singh; Prince S. Godson; Salom Gnana Thanga (Environmental Science and Pollution Research, 2022)

Ecotoxicological and health implications of microplastic-associated biofilms: a recent review and prospect for turning the hazards into benefits - Emmanuel Sunday Okeke; Timothy Prince Chidike Ezeorba; Yao Chen; Guanghua Mao; Weiwei Feng; Xiangyang Wu (Environmental Science and Pollution Research, 2022)

Multi-geochemical background comparison and the identification of the best normalizer for the estimation of PTE contamination in agricultural soil - Prince Chapman Agyeman; Kingsley John; Ndiye Michael Kebonye; Samuel Kudjo Ahado; Luboš Borůvka; Karel Němeček; Radim Vašát (Environmental Geochemistry and Health, 2022)

On anomalously high sub-surface dissolved oxygen in the Indian sector of the Southern Ocean - Prince Prakash; Satya Prakash; M. Ravichandran; N. Anil Kumar; T. V. S. Udaya Bhaskar (Journal of Oceanography, 2022)

Acceleration of flow modeling using a freeware 2D GPU-shallow water equations code - Prince Mahmood; Sajjad Haider; Hamza Farooq Gabriel; Muhammad Shahid; Zain Syed (Arabian Journal of Geosciences, 2022)

Development and operation of immobilized cell plug flow bioreactor (PFR) for treatment of textile industry effluent and evaluation of its working efficiency - Satish Koundal; Khushboo Sharma; Prince Dhammi; Pooja Chadha; Harvinder Singh Saini (Environmental Science and Pollution Research, 2022)

Strongylopus grayii tadpole blastema extract exerts cytotoxic effects on embryonal rhabdomyosarcoma cells - Vincent Harrison; Saif F. Khan; Victoria Damerell; Jenna Bleloch; KN. ArulJothi; Musalula Sinkala; Katie Lennard; Nicola Mulder; Bridget Calder; Jonathan Blackburn; Sharon Prince (In Vitro Cellular & Developmental Biology - Animal, 2022)

A comprehensive review on textile waste valorization techniques and their applications - Prince Kumar Mishra; Ansari Mohammed Dilsad Izrayeel; Bhupender Kumar Mahur; Arihant Ahuja; Vibhore Kumar Rastogi (Environmental Science and Pollution Research, 2022)

Microaerobic conditions enhance laccase production from Rheinheimera sp. in an economical medium - Aarjoo Sharma; Sanjeev Balda; Naveen Gupta; Neena Capalash; Prince Sharma (Archives of Microbiology, 2022)

Characterization of thermo-physiological, hematological, and molecular changes in response to seasonal variations in two tropically adapted native cattle breeds of Bos indicus lineage in hot arid ambience of Thar Desert - Gayatri Gujar; Vijay Kumar Choudhary; Prince Vivek; Monika Sodhi; Monika Choudhary; Manish Tiwari; Nampher Masharing; Manishi Mukesh (International Journal of Biometeorology, 2022)

Role of Antimicrobial Peptides in Treatment and Prevention of Mycobacterium Tuberculosis: A Review - Kanchan Mehta; Prince Sharma; Shama Mujawar; Ashish Vyas (International Journal of Peptide Research and Therapeutics, 2022)

Investigation of Coastal Water Characteristics Along the Southeast Coast of India: A Multivariate Approach - Dilip Kumar Jha; Vikas Pandey; Chandrasekaran Muthukumar; Ponnusamy Sathish Kumar; Srinivas Venkatnarayanan; Jebarathnam Prince Prakash Jebakumar; Gopal Dharani (Frontiers in Marine Science, 2022)

Experimental study on piled ring foundation resting on RDFS cushion overlying soft clay - Prince Karandeep Singh; Arvind Kumar (Marine Georesources & Geotechnology, 2022)

Synthesis and in silico evaluation of novel uridyl sulfamoylbenzoate derivatives as potential anticancer agents targeting M1 subunit of human ribonucleotide reductase (hRRM1) - Prince J. Salvador; Heather B. Jacobs; Lujain Alnouri; Asia Fee; Lynn M. Utley; Madison Mabry; Hannah Krajeck; Christopher Dicksion; Ahmed M. Awad (Medicinal Chemistry Research, 2022)

Coconut oil and fermented palm wine biodiesel production for oil spill cleanup: experimental, numerical, and hybrid metaheuristic modeling approaches - Eric Thompson Brantson; Harrison Osei; Mark Shalom Kwesi Aidoo; Prince Opoku Appau; Fuseini Naziru Issaka; Nannan Liu; Chukwugozie Jekwu Ejeh; Kouamelan Serge Kouamelan (Environmental Science and Pollution Research, 2022)

Multi-metric Ecosystem Health Assessment of Three Inland Water Bodies in South-west, Nigeria, with Varying Levels of Sand Mining Activities and Heavy Metal Pollution - Prince Emeka Ndimele; Fatai Gbolahan Owodeinde; Abdullatif Olufemi Giwa-Ajeniya; Bridget Adekemi Moronkola; Oyindamola Roseline Adaramoye; Lois Oyindamola Ewenla; Hijrah Yetunde Kushoro (Biological Trace Element Research, 2022)

Evolution of l arge‐scale factors influencing extreme rainfall over south western coast of India - Ajil Kottayil; Anu Xavier; Prince Xavier; Prajwal Koovekkallu; Kesavapillai Mohanakumar (International Journal of Climatology, 2022)
The life cycle and the large‐scale factors driving extreme heavy rainfall events over the south west coast of India are studied. The extreme rainfall events are linked to the development of monsoon depressions and the associated large‐scale dynamics. Strengthening of these parameters intensifies the monsoon low‐level circulation over the Arabian Sea and the west coast via steepened meridional pressure gradient. The intensification of the low‐level jet stream speed and its extension in the vertical causes an increase in the humidity flux in the lower and midtroposphere. The consequent ascending motion is from the midtroposphere to the upper troposphere, resulting in the formation of deep convective cloud clusters over the west coast and eastern parts of the Arabian Sea. This results in the incidence of extreme heavy rainfall over the south west coast of India. It is observed that during days of extreme rainfall, the direction of wind in the lower troposphere tends to be almost perpendicular to the Western Ghats favouring a strong orographic lift. The extreme rainfall events over the south west coast do not necessarily occur during the active cycle of monsoon intraseasonal oscillation, but are linked to the north westwards propagating monsoon depressions. We show that the signatures of extreme rainfall can be observed in several meteorological variables developing over different parts of the monsoon region. A synergistic analysis of these variables may help in the accurate and timely prediction of these events.

Genetic parameters of growth traits, trend of production and reproduction traits, and meat quality status of Ghagus, an indigenous chicken of India - Santosh Haunshi; Rajkumar Ullengala; Leslie Leo Prince; Kannaki Ramasamy; Kandeepan Gurunathan; Suresh Devatkal; Rudra Nath Chatterjee (Tropical Animal Health and Production, 2022)

A Looming Chance of Bio Invasion by a Bryozoan Amathia verticillata Among the Sea Fan and Seagrass Population Along Tamil Nadu Coast: A Case Study - J. Prince Prakash Jeba Kumar; G. Nandhagopal; B. Rajan Babu; S. Ragumarn; Dilip Kumar Jha; J. Santhana Kumar; G. Dharani; Vijaya Ravichandran (Proceedings of the Zoological Society, 2022)

Rational design and fabrication of monophasic bioceramic microspheres with enhanced mechanical and biological performances in reconstruction of segmental bone defect - Yu Cong; Zhong Liang; Ni Jianping; Hu Wenyue; Ghamor-Amegavi Edem Prince; Xiangfeng Zhang (Medical & Biological Engineering & Computing, 2022)

Vegetation attributes drive the taxonomic richness and functional composition of beetles and spiders in mountainous urban green spaces - Frederick Gyasi Damptey; Bernard Fosu Frimpong; Daniel Kwame Debrah; Prince Pascal Agro; Edward Debrah Wiafe (Energy, Ecology and Environment, 2022)
Urban green spaces (UGS) enhance the quality of life in urban environments and serve as habitat corridors or refuge for organisms, including beetles and spiders. The attributes of UGS allow them to harbour species that offer essential ecosystem services. However, the ability of UGS to provide services is limited by the extent to which they have been altered anthropogenically. We described the taxonomic richness and functional composition of arthropods in a mountainous urban ecosystem of Ghana by focussing on the activity of both beetles and spiders at the family level. Two main land-use types (woodlands and built-up areas) were identified and characterised based on the presence or absence of certain vegetation attributes. Sixteen plots in each land-use type with sizes 20 × 20 m were demarcated and fitted with four pitfall traps in each plot to sample continuously for eight weeks, the activity density of both beetles and spiders. Samples were sorted into families and functional groups (detritivores, fungivores, herbivores and predators). The taxonomic richness and activity density were both significantly higher in the woodlands than in the built-up areas. Similarly, all functional groups showed a higher affinity to the woodlands than the built-up areas. Habitat attributes defined by plant diversity and structural complexity were the underlying drivers explaining the differences in arthropod communities between the land-use types. Though the built-up areas seem degraded and open, the remaining small vegetation patches still support the activities of some taxa that should merit the protection of such remnant vegetation in urban ecosystems.

Geochemistry and zircon U–Pb ages of the Paleoproterozoic ultramafic rocks of the Mbi Valley, Boali area, Central African Republic - Evine Laure Njiosseu Tanko; Prince Emilien Danguene; Philomene Nga Essomba Tsoungui; Sylvestre Ganno; Jonas Didero Takodjou Wambo; Bertin Guy Takam Tchoupe; Gus Djibril Kouankap Nono; Timoleon Ngnotue; Boniface Kankeu; Jean Biandja; Jean Paul Nzenti (Acta Geochimica, 2022)

Genetic analysis of grain yield and yield-attributing traits in navy bean (Phaseolus vulgaris L.) under drought stress - Bruce Mutari; Julia Sibiya; Edmore Gasura; Prince M. Matova; Kennedy Simango; Aleck Kondwakwenda (Euphytica, 2022)

Quantile estimation of ecological footprint and economic complexity in emerging economies: The moderating role of increasing energy consumption - Solomon Prince Nathaniel; Davidmac Olisa Ekeocha; Nnamdi Nwulu (Environmental Science and Pollution Research, 2022)

Paleoproterozoic gold events in the southern West African Craton: review and synopsis - Quentin Masurel; Aurélien Eglinger; Nicolas Thébaud; Andrew Allibone; Anne-Sylvie André-Mayer; Helen McFarlane; John Miller; Mark Jessell; Laurent Aillères; Olivier Vanderhaeghe; Stefano Salvi; Lenka Baratoux; et al. (Mineralium Deposita, 2022)

Revisiting the EKC hypothesis by assessing the complementarities between fiscal, monetary, and environmental development policies in China - Ayoub Zeraibi; Zahoor Ahmed; Khurram Shehzad; Muntasir Murshed; Solomon Prince Nathaniel; Haider Mahmood (Environmental Science and Pollution Research, 2022)

The relationship between external debt and ecological footprint in SANE countries: insights from Kónya panel causality approach - Darlington Akam; Solomon Prince Nathaniel; Hamid Adebayo Muili; Samuel Nzube Eze (Environmental Science and Pollution Research, 2022)

Mitigating energy production-based carbon dioxide emissions in Argentina: the roles of renewable energy and economic globalization - Muntasir Murshed; Seemran Rashid; Recep Ulucak; Vishal Dagar; Abdul Rehman; Rafael Alvarado; Solomon Prince Nathaniel (Environmental Science and Pollution Research, 2022)

Tobramycin Stress Induced Differential Gene Expression in Acinetobacter baumannii - Shruti Kashyap; Prince Sharma; Neena Capalash (Current Microbiology, 2022)

Surfactants usage in enhanced oil recovery operations coupling harsh reservoir conditions: an experimental review - Prince Opoku Appau; Hui Pu; Solomon Adjei Marfo; Eric Thompson Brantson (Arabian Journal of Geosciences, 2022)

Air pollution perception in ten countries during the COVID-19 pandemic - Baowen Lou; Diego Maria Barbieri; Marco Passavanti; Cang Hui; Akshay Gupta; Inge Hoff; Daniela Antunes Lessa; Gaurav Sikka; Kevin Chang; Kevin Fang; Louisa Lam; Brij Maharaj; et al. (Ambio, 2022)
As largely documented in the literature, the stark restrictions enforced worldwide in 2020 to curb the COVID-19 pandemic also curtailed the production of air pollutants to some extent. This study investigates the perception of the air pollution as assessed by individuals located in ten countries: Australia, Brazil, China, Ghana, India, Iran, Italy, Norway, South Africa and the USA. The perceptions towards air quality were evaluated by employing an online survey administered in May 2020. Participants ( N = 9394) in the ten countries expressed their opinions according to a Likert-scale response. A reduction in pollutant concentration was clearly perceived, albeit to a different extent, by all populations. The survey participants located in India and Italy perceived the largest drop in the air pollution concentration; conversely, the smallest variation was perceived among Chinese and Norwegian respondents. Among all the demographic indicators considered, only gender proved to be statistically significant.

Farmers’ preferences for climate-smart cowpea varieties: implications for crop breeding programmes - Edward Martey; Prince M. Etwire; Desmond Sunday Adogoba; Theophilus Kwabla Tengey (Climate and Development, 2022)

An in-depth human health risk assessment of potentially toxic elements in highly polluted riverine soils, Příbram (Czech Republic) - Ndiye M. Kebonye; Peter N. Eze; Kingsley John; Prince C. Agyeman; Karel Němeček; Luboš Borůvka (Environmental Geochemistry and Health, 2022)

Evaluation of Site Suitability for Artificial Reefs Deployment in Southeast Coast of India Using Geographical Information System as a Management Tool - Dilip Kumar Jha; Vikas Pandey; J. Santhanakumar; P. Sathish Kumar; S. Venkatnarayanan; J. Prince Prakash Jebakumar; G. Dharani; R. Vijaya (Frontiers in Marine Science, 2022)
A planned artificial reef (AR) deployment program as part of a fisheries enhancement might be a useful tool for managers to supplement traditional ways to utilize available space and augment local productivity. Several AR deployment initiatives have been carried out globally, but they are rarely subjected to a rigorous site selection process. We created a site selection procedure in this study that includes systematic stages including exclusion mapping, underwater visual transect, benthic composition, seawater quality, and comparative visual mapping. This research focused on restoring the fishing grounds for artisanal fishermen by deploying AR along the southeast coast of India. The results of each stage in the procedure enabled us to choose suitable locations at a target depth with low wave action, no slope, and a good substrate capable of supporting an AR. Analysis of variance (ANOVA-one way) showed significant ( p < 0.05) spatial variation for depth, slope, seawater current, salinity, chlorophyll-a, benthic density, and diversity. The geographical information system (GIS) based model output showed space allocation for AR deployment. The GIS methodology for site selection was developed to be easily adaptable to the demands of diverse artificial reef programs. The integrated strategy has proven to be a successful regulatory intervention for AR deployment practices in order to facilitate coastal restoration and management.

( −)-Epicatechin and cardiometabolic risk factors: a focus on potential mechanisms of action - Ezequiel J. Hid; Juana I. Mosele; Paula D. Prince; Cesar G. Fraga; Monica Galleano (Pflügers Archiv - European Journal of Physiology, 2022)

Antibiotic residues in environment: antimicrobial resistance development, ecological risks, and bioremediation - Mansi Apreja; Aarjoo Sharma; Sanjeev Balda; Kirti Kataria; Neena Capalash; Prince Sharma (Environmental Science and Pollution Research, 2022)

Impact of climate change adaptation on farm productivity and household welfare - Prince Maxwell Etwire; Isaac Koomson; Edward Martey (Climatic Change, 2022)

Multi-Indicator Harvest Strategies for Data-Limited Fisheries: A Practitioner Guide to Learning and Design - William J. Harford; Ricardo Amoroso; Richard J. Bell; Matias Caillaux; Jason Marc Cope; Dawn Dougherty; Natalie Anne Dowling; Frank Hurd; Serena Lomonico; Josh Nowlis; Dan Ovando; Ana M. Parma; et al. (Frontiers in Marine Science, 2021)
As the world population grows, fisheries practitioners will be under increased pressure to address global challenges in data-limited fisheries management. With a focus on addressing localized and case-specific management needs, we provide a practical guide to the design and development of multi-indicator frameworks for fishery management. In a data-limited context, indicators are observations or estimates of the state of the fishery resource that are typically proxies for variables of interest, rather than quantities such as stock biomass estimated from data-rich stock assessments. Indicator frameworks structure the integration and interpretation of indicators to guide tactical fishery decision-making, often when the application of more formal analytical assessments is not feasible, yet where indicators in combination provide insight into stock status. With a focus on multi-indicator frameworks, we describe a pragmatic approach for their development via a set of organizational steps, considering a wide spectrum of types and severity of information limitations. We highlight where multi-indicator frameworks can be insightful and informative in relation to single indicator approaches but also point to potential pitfalls, with emphasis on critical evaluation and detection of performance flaws during the design phase using methods such as management strategy evaluation.

Quantifying fishing activity targeting subsea pipelines by commercial trap fishers - Todd Bond; Dianne L. McLean; Corey B. Wakefield; Julian C. Partridge; Jane Prince; David White; Dion K. Boddington; Stephen J. Newman (Reviews in Fish Biology and Fisheries, 2021)

Distribution and diversity of alternate hosts of Maruca vitrata Fabricius in three West African countries - Prince Christopher Addae; Y. Anani Bruce; Iliyasu M. Utono; Mumuni Abudulai; Fousseni Traore; Mohammad F. Ishiyaku; Rabiu S. Adamu; Ahmed Seidu; Benoît J. Batieno; Onyekachi Francis Nwankwo; Malick N. Ba; Gloria A. Adazebra; et al. (International Journal of Tropical Insect Science, 2021)
The evolution of resistance to the Bacillus thuringiensis ( Bt ) toxins by insect pests is a major threat to Bt technology. However, the rate of resistance can be slowed with appropriate integrated insect resistance management (IRM) strategies. Surveys were conducted to identify alternate host species for Maruca vitrata (commonly called the legume pod borer or Maruca ) that could serve as refuges for Pod-Borer Resistant (PBR) cowpea in three West African countries (Ghana, Nigeria, and Burkina Faso). Survey sites included 25 in northern Ghana, 44 in northern Nigeria, and 52 in north-central and southwestern Burkina Faso. Alternate hosts of Maruca identified from plant species belonging to the Fabaceae family that showed signs of Maruca damage on cowpea tissues were collected and dissected. Larvae that were found during these dissections were reared to adult moths in the laboratory then identified to species. The alternate host plants including species of Crotolaria , Sesbania , Tephrosia , and Vigna were the most frequently encountered among sites and locations. Flowering and podding of these plants overlapped with flowering and podding of the nearby (~200 m) cowpea crop. Abundance of these wild hosts and overlapping flowering patterns with the cowpea crop in most locations have the potential to sustain ample numbers of Bt susceptible Maruca that will mate with possible resistant Maruca and deter resistance development. Further quantitative studies, however, are required from each location to determine if actual Maruca production from alternate hosts is sufficient for a PBR IRM strategy. If verified, this approach would be compatible with the high dose/refuge IRM strategy that includes alternate hosts and non- Bt crops as refuges.

Foreign direct investments and environmental quality in sub-Saharan Africa: the merits of policy and institutions for environmental sustainability - Emmanuel Duodu; Evans Kwarteng; Eric Fosu Oteng-Abayie; Prince Boakye Frimpong (Environmental Science and Pollution Research, 2021)

Economic complexity versus ecological footprint in the era of globalization: evidence from ASEAN countries - Solomon Prince Nathaniel (Environmental Science and Pollution Research, 2021)

A multi-emission analysis of organic and inorganic pollutants during the combustion of sludge with high and low calorific value coals - Jingyu Huang; Prince Atta Opoku; Li Guang; Li Ke; Eyram Norgbey (Environmental Science and Pollution Research, 2021)

Linking external debt and renewable energy to environmental sustainability in heavily indebted poor countries: new insights from advanced panel estimators - Darlington Akam; Oluwasegun Owolabi; Solomon Prince Nathaniel (Environmental Science and Pollution Research, 2021)

Detection of novel sequence types and zoonotic transmission potentiality among strains of Shiga toxigenic Escherichia coli (STEC) from dairy calves, animal handlers and associated environments - Madesh Angappan; Sandeep Ghatak; Arockiasamy Arun Prince Milton; Asha Kumari Verma; Sophia Inbaraj; Abhishek; Pallab Chaudhuri; Rajesh Kumar Agarwal; Prasad Thomas (Brazilian Journal of Microbiology, 2021)

The nexus between economic growth, energy use, international trade and ecological footprints: the role of environmental regulations in N11 countries - Solomon Prince Nathaniel; Muntasir Murshed; Mohga Bassim (Energy, Ecology and Environment, 2021)

Evaluation of microfiber release from jeans: the impact of different washing conditions - Aravin Prince Periyasamy (Environmental Science and Pollution Research, 2021)
Microplastic particles are a burgeoning population crisis in the marine environment. This research examines the emission of microfibers from three different jeans (garments) during domestic washing. The jeans types, washing temperature, washing duration, spin speed, detergent types, and addition of conditioner are the main factors for this research work. The average length and diameter of the microfibers for the 100% PET jeans (jeans-P) has 7800 ± 4000 μm and 11.9±3.2 μm and for polyester/cotton jeans (jeans-PB) has 4900 ± 2200 μm 17.4±4.8 μm, respectively. The maximum microfiber released was observed in the rigorous washing treatment (90 min, 60°C, 1400 rpm, powder detergent with the presence of conditioner). The surmised number of microfibers discharged from the 1 kg wash load of jeans-P was calculated within the extent of 2300000–4900000 microfibers, and it is varied by the washing treatments.

A relative study on energy and exergy analysis between conventional single slope and novel stepped absorbable plate solar stills - Gurukarthik Babu Balachandran; Prince Winston David; Anandha Balaji Alexander; Muthu Manokar Athikesavan; Padmanaban Velayudha perumal Chellam; Krishna Kumar Sasi Kumar; Vinothkumar Palanichamy; Abd Elnaby Kabeel; Ravishankar Sathyamurthy; Fausto Pedro Garcia Marquez (Environmental Science and Pollution Research, 2021)

A recurring population of the sea hare Bursatella hirsuta (Gastropoda: Aplysiidae) at Rottnest Island, Western Australia - Fred E. Wells; Cindy Bessey; Marthe Monique Gagnon; John K. Keesing; Jane Prince (Molluscan Research, 2021)

Coral annual growth band impregnated microplastics (Porites sp.): a first investigation report - S. Krishnakumar; S. Anbalagan; S. M. Hussain; R. Bharani; Prince Samuel Godson; S. Srinivasalu (Wetlands Ecology and Management, 2021)

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Environmental pollution and energy research and development: an Environmental Kuznets Curve model through quantile simulation approach - Faik Bilgili; Solomon Prince Nathaniel; Sevda Kuşkaya; Yacouba Kassouri (Environmental Science and Pollution Research, 2021)

The impact of social media marketing strategies on promoting sustainability of tourism with fuzzy cognitive mapping: a case of Kalanggaman Island (Philippines) - Kafferine Yamagishi; Lanndon Ocampo; Dharyll Prince Abellana; Reciel Ann Tanaid; Ann Myril Tiu; Maria Esther Medalla; Egberto Selerio; Chrisalyn Go; Rey Cesar Olorvida; Amalia Maupo; Dearielyn Maskariño; Emilyn Tantoo (Environment, Development and Sustainability, 2021)

MR Imaging of Human Brain Mechanics In Vivo: New Measurements to Facilitate the Development of Computational Models of Brain Injury - Philip V. Bayly; Ahmed Alshareef; Andrew K. Knutsen; Kshitiz Upadhyay; Ruth J. Okamoto; Aaron Carass; John A. Butman; Dzung L. Pham; Jerry L. Prince; K. T. Ramesh; Curtis L. Johnson (Annals of Biomedical Engineering, 2021)

Health risk assessment and the application of CF-PMF: a pollution assessment–based receptor model in an urban soil - Prince Chapman Agyeman; Samuel Kudjo Ahado; Kingsley John; Ndiye Michael Kebonye; Radim Vašát; Luboš Borůvka; Martin Kočárek; Karel Němeček (Journal of Soils and Sediments, 2021)

Artificial coastal defence structures – A surrogate of natural rocky structure to enhance coastal biodiversity - J Prince Prakash Jebakumar; G Nandhagopal; S Ragumaran; Vijaya Ravichandran; C M Ramakritinan (Journal of Earth System Science, 2021)

The roles of nuclear energy, renewable energy, and economic growth in the abatement of carbon dioxide emissions in the G7 countries - Solomon Prince Nathaniel; Md. Shabbir Alam; Muntasir Murshed; Haider Mahmood; Paiman Ahmad (Environmental Science and Pollution Research, 2021)

Marine ecoregions and subecoregions within Indo‐West Australian waters: A statistical approach based on species distributions - Hadiyanto Hadiyanto; Renae K. Hovey; Christopher J. Glasby; Jane Prince (Journal of Biogeography, 2021)
Aim The Marine Ecoregions of the World (MEOW) system delineates the oceans into 232 ecoregions. Here, we aimed to evaluate the suitability of this system to represent species distributions within Indo‐West Australian waters, explore alternative ecoregions and new subecoregions and investigate environmental variables that are correlated with species distributions within those waters. Location Indo‐West Australia. Taxon Vertebrates, invertebrates, marine plants. Methods We downloaded occurrence data for 14,513 marine species from the Ocean Biogeographic Information System. We analysed differences in species composition among nine ecoregions within Indo‐West Australian waters using pairwise permutational multivariate analysis of variance to evaluate how well the MEOW system represents species distributions within those waters. We delineated subecoregions within each distinct ecoregion using hierarchical cluster analysis with the unweighted pair‐group method using arithmetic averages. We analysed relationships between environmental variables and species composition using distance‐based linear models. Results Species composition was significantly different among ecoregions, except for three adjacent regions, which were combined into a single large ecoregion. Hence, seven distinct ecoregions were further analysed. Our study identified 13 subecoregions within these ecoregions that each separate into ‘inshore’ and ‘offshore’ zones. Depth explained the most variation in species composition of the combined taxa and sea surface temperature was the most important parameter in explaining the variability in most taxa. Main Conclusion The MEOW system did not represent well the distribution of marine species within Indo‐West Australian waters. Alternatively, we show that those waters encompass seven distinct ecoregions with 13 subecoregions. The main environmental drivers of species distributions could be depth and sea surface temperature. The proposed ecoregions and subecoregions allow us to improve the biogeographic hypotheses for understanding the evolution of marine species and identify representative marine habitats and species composition for the setting of Marine Protected Area networks within Indo‐West Australian waters.

Petrology and geochronology of metamorphic rocks from the Bossangoa-Bossembélé area, Northern Central African Republic—evidence for Palaeoproterozoic high-grade metamorphism in the North Equatorial Fold Belt - Evine Laure Tanko Njiosseu; Prince Emilien Danguene; Timoleon Ngnotue; Sylvestre Ganno; Gus Djibril Kouankap Nono; Christiane Diorlette Ngo Nlend; Boniface Kankeu; Jean Biandja; Jean Paul Nzenti (Arabian Journal of Geosciences, 2021)

Effect of bypass fatty acid and Tinospora cordifolia supplementation on production performance and milk fatty acid profiling in Murrah buffaloes (Bubalus bubalis) - Rajneesh; A. K. Misra; Rajan Sharma; Prince Chauhan (Tropical Animal Health and Production, 2021)

What drives ecological footprint in top ten tourist destinations? Evidence from advanced panel techniques - Solomon Prince Nathaniel; Suborna Barua; Zahoor Ahmed (Environmental Science and Pollution Research, 2021)

Investigation on the performance enhancement of single-slope solar still using green fibre insulation derived from Artocarpus heterophyllus rags reinforced with Azadirachta indica gum - Gurukarthik Babu Balachandran; Prince Winston David; Vignesh Radhakrishnan; Mohamed Nasrulla Akbar Ali; Vishnu Karan Baskaran; Dhanasekaran Virumandi; Muthu Manokar Athikesavan; Ravishankar Sathyamurthy (Environmental Science and Pollution Research, 2021)

Banana fibre: a natural and sustainable bioresource for eco-friendly applications - Sanjeev Balda; Aarjoo Sharma; Neena Capalash; Prince Sharma (Clean Technologies and Environmental Policy, 2021)

The functions and regulation of heat shock proteins; key orchestrators of proteostasis and the heat shock response - Benjamin J. Lang; Martin E. Guerrero; Thomas L. Prince; Yuka Okusha; Cristina Bonorino; Stuart K. Calderwood (Archives of Toxicology, 2021)

Morpho-molecular identification of Heterophyes heterophyes encysted metacercariae and its immunological and histopathological effects on farmed Mugil cephalus in Egypt - Marwa M. Attia; Mamdouh Y. Elgendy; Mohamed Abdelsalam; Azza Hassan; Abdelbary Prince; Nagla M. K. Salaeh; Nehal A. Younis (Aquaculture International, 2021)

The potential effect of phytochemicals and herbal plant remedies for treating drug-induced hepatotoxicity: a review - Manisha Parthasarathy; Sabina Evan Prince (Molecular Biology Reports, 2021)

Environmental degradation in ASEAN: assessing the criticality of natural resources abundance, economic growth and human capital - Solomon Prince Nathaniel (Environmental Science and Pollution Research, 2021)

Trend analysis of global usage of digital soil mapping models in the prediction of potentially toxic elements in soil/sediments: a bibliometric review - Prince Chapman Agyeman; Samuel Kudjo Ahado; Luboš Borůvka; James Kobina Mensah Biney; Vincent Yaw Oppong Sarkodie; Ndiye M. Kebonye; John Kingsley (Environmental Geochemistry and Health, 2021)

Comparison of Cubist models for soil organic carbon prediction via portable XRF measured data - Kingsley John; Ndiye M. Kebonye; Prince C. Agyeman; Samuel K. Ahado (Environmental Monitoring and Assessment, 2021)

Inheritance of growth traits and impact of selection on carcass and egg quality traits in Vanashree, an improved indigenous chicken - Santosh Haunshi; Rajkumar U.; C. Paswan; L. L. L. Prince; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Effect of feeding Azolla pinnata in combination with direct-fed microbial on broiler performance - Shambhvi; Shivani Katoch; Prince Chauhan; Bandu Gangadhar Mane (Tropical Animal Health and Production, 2021)

Pharmacokinetics and hypoglycemic effect of gliclazide loaded in Isabgol husk mucilage microparticles - Vipin Kumar; Bhaskar Mazumder; Prince Prashant Sharma; Yusra Ahmed (Journal of Pharmaceutical Investigation, 2021)

Green method of stemming the tide of invasive marine and freshwater organisms by natural filtration of shipping ballast water - Jebarathnam Prince Prakash Jeba Kumar; Shunmugavel Ragumaran; Ganesan Nandagopal; Vijaya Ravichandran; Ramana Murthy Mallavarapu; Thomas M. Missimer (Environmental Science and Pollution Research, 2021)
Marine and freshwater pollution caused by transport of invasive species in shipping ballast water is a major global problem and will increase in magnitude as shipping of commodities increases in the future. An economical method to preclude biological organisms in the seawater used for ballast is to exclude them at the source port. Integrated natural filtration using onshore wells or seabed gallery systems has been thoroughly investigated for use as pretreatment for seawater desalination systems and has proven to be environmentally acceptable and economic. Thus, the use of this proven filtration technology to another issue, ballast water treatment, is an innovative method of providing marine organism free seawater by non-destructive means in port-based facilities. This method is ecosystem-friendly in that no chemicals or destructive processes are used. Design and construction of well or seabed gallery intake systems for production of ballast seawater are feasible in virtually all global port facilities.

Response to letter to the Editor: The therapeutic strategy of drug re-positioning to induce autophagic cell death in brain malignancy - S. I. Omoruyi; A. Jardine; S. Prince (Apoptosis, 2021)

Gene expression during larval caste determination and differentiation in intermediately eusocial bumblebees, and a comparative analysis with advanced eusocial honeybees - David H. Collins; Anders Wirén; Marjorie Labédan; Michael Smith; David C. Prince; Irina Mohorianu; Tamas Dalmay; Andrew F. G. Bourke (Molecular Ecology, 2021)
The queen‐worker caste system of eusocial insects represents a prime example of developmental polyphenism (environmentally‐induced phenotypic polymorphism) and is intrinsic to the evolution of advanced eusociality. However, the comparative molecular basis of larval caste determination and subsequent differentiation in the eusocial Hymenoptera remains poorly known. To address this issue within bees, we profiled caste‐associated gene expression in female larvae of the intermediately eusocial bumblebee Bombus terrestris . In B . terrestris , female larvae experience a queen‐dependent period during which their caste fate as adults is determined followed by a nutrition‐sensitive period also potentially affecting caste fate but for which the evidence is weaker. We used mRNA‐seq and qRT‐PCR validation to isolate genes differentially expressed between each caste pathway in larvae at developmental stages before and after each of these periods. We show that differences in gene expression between caste pathways are small in totipotent larvae, then peak after the queen‐dependent period. Relatively few novel (i.e., taxonomically‐restricted) genes were differentially expressed between castes, though novel genes were significantly enriched in late‐instar larvae in the worker pathway. We compared sets of caste‐associated genes in B . terrestris with those reported from the advanced eusocial honeybee, Apis mellifera , and found significant but relatively low levels of overlap of gene lists between the two species. These results suggest both the existence of low numbers of shared toolkit genes and substantial divergence in caste‐associated genes between Bombus and the advanced eusocial Apis since their last common eusocial ancestor.

Marine Oil Snow, a Microbial Perspective - Benjamin H. Gregson; Boyd A. McKew; Robert D. Holland; Timothy J. Nedwed; Roger C. Prince; Terry J. McGenity (Frontiers in Marine Science, 2021)
Under certain conditions, dispersed crude oil in the sea combines with organisms, organic matter, and minerals to form marine oil snow (MOS), thereby contributing to the sinking of oil to the seafloor. Marine microbes are the main players in MOS formation, particularly via the production of extracellular polymeric substances. Distinct groups of microbes also consume the majority of the hydrocarbons during descent, leading to enrichment of the less bioavailable hydrocarbons and asphaltenes in the residue. Here we discuss the dynamics of microbial communities in MOS together with their impacts on MOS evolution. We explore the effects of dispersant application on MOS formation, and consider ways in which laboratory experiments investigating MOS formation can be more representative of the situation in the marine environment, which in turn will improve our understanding of the contribution of MOS to the fate of spilled oil.

Investigation of performance enhancement of solar still incorporated with Gallus gallus domesticus cascara as sensible heat storage material - Gurukarthik Babu Balachandran; Prince Winston David; Gokul Rajendran; Mohamed Nasrulla Akbar Ali; Vignesh Radhakrishnan; Ramkumar Balamurugan; MuthuManokar Athikesavan; Ravishankar Sathyamurthy (Environmental Science and Pollution Research, 2021)

Source apportionment, contamination levels, and spatial prediction of potentially toxic elements in selected soils of the Czech Republic - Prince Chapman Agyeman; Samuel Kudjo Ahado; John Kingsley; Ndiye Michael Kebonye; James Kobina Mensah Biney; Luboš Borůvka; Radim Vasat; Martin Kocarek (Environmental Geochemistry and Health, 2021)

Energetic management in wild chimpanzees (Pan troglodytes verus) in Taï National Park, Côte d’Ivoire - Prince D. Valé; Jean-Claude K. Béné; Antoine K. N’Guessan; Catherine Crockford; Tobias Deschner; Inza Koné; Cédric Girard-Buttoz; Roman M. Wittig (Behavioral Ecology and Sociobiology, 2021)
Socioecological theories predict that, in mammals, feeding and mating competitions affect male and female energetic conditions differently but energetic studies investigating both sexes simultaneously are rare. We investigated the effect of socioecological factors on the energetic conditions of male and female western chimpanzees, a long-lived species with high degrees of male-male competition. We used behavioural data collected on one chimpanzee community in the Taï National Park over 12 months, phenological data and urinary c-peptide (UCP) measures, a marker of energy balance. We found a positive effect of food availability on UCP levels in both sexes. Dominance rank also affected chimpanzee UCP levels. High-ranking females had higher UCP levels than low-ranking ones but only in periods when no oestrus females were present in the community. In contrast, high-ranking males had higher UCP levels than low-ranking males in the presence of oestrus females but lower UCP levels in their absence. Our results suggest that oestrus female presence lessened the competitive advantages of high-ranking females in feeding competition and that low-ranking males bore higher energetic costs related to mating competition than high-ranking ones. Yet caution should apply in interpreting these results since the statistical model was only close to significance. High-ranking male and female chimpanzees spent significantly less energy. Furthermore, all chimpanzees significantly spent less time feeding and spent more energy when food availability was high. Finally, our behavioural measure of energy intake and expenditure did not correlate with UCP levels highlighting the value of non-invasive hormonal markers for field studies. Significance statement General socioecological theories hypothesize that the social grouping dynamic and energetics of females are highly influenced by food competition, whereas in males, competition for sexual partners is more influential for these factors. Recent studies in the non-invasive physiological assessment of energy balance in primates have begun to test the implied relationship between chimpanzee socioecology and individual energetic condition, with inconsistent results. However, only a few studies have investigated this relationship concurrently for both sexes. Here, using non-invasive measures of energy balance in wild western chimpanzees, we found that the energetics of both males and females are related to ecological factors, such as food availability. However, female energy balance appears also to be related to increased male mating competition, as this can result in increased aggression directed from males to females, with apparent energetic costs for females.

C-terminal domain of APETALA1 is essential for its functional divergence from CAULIFLOWER in Arabidopsis - Prince Saini; Ram Kishor Yadav (Journal of Plant Biochemistry and Biotechnology, 2020)

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

Sponges in shallow tropical and temperate reefs are important habitats for marine invertebrate biodiversity - Ying-Yueh Chin; Jane Prince; Gary Kendrick; Muhammad Azmi Abdul Wahab (Marine Biology, 2020)

Mystery pufferfish create elaborate circular nests at mesophotic depths in Australia - Todd Bond; Robert J. Mueller; Matthew J. Birt; Jane Prince; Karen Miller; Julian C. Partridge; Dianne L. McLean (Journal of Fish Biology, 2020)
In 2011, the enigma of “mystery circles,” small but complex underwater structures first observed by divers from southern Japan in 1995, was solved when a new species of pufferfish, white‐spotted pufferfish ( Torquigener albomaculosus Matsuura 2014), was identified as the responsible agent. To date these circles have been described only from Japan, where they are formed on a sandy seafloor in water depths less than 30 m. A survey of oil field infrastructure on the North West Shelf of Western Australia in 2018 using a remotely operated vehicle and hybrid autonomous underwater vehicle (HAUV) recorded a high‐resolution video and bathymetric data of 21 circular formations with similar features to those described in Japan. The circles display dimensions and morphology like those described from Japan, but were observed in water depths between 129 and 137 m. The HAUV also recorded high‐resolution photographs which captured a Torquigener sp. fish in the immediate vicinity of the circles. An additional circle and Torquigener sp. were observed in images collected by baited remote underwater stereo‐video in a nearby location in 129 m depth. These circles are the first to be found in Australia. The pufferfish species responsible cannot be identified from images collected . Such a discovery not only generates intrigue and wonder among scientists and the general public but also provides an insight into the reproductive behaviour and evolution of pufferfish globally.

Wet or dry sowing had a larger effect on the soil bacterial community composition than tillage practices in an arid irrigated agro-ecosystem - Laurette Prince; Nele Verhulst; Bram Govaerts; Yendi E. Navarro-Noya; Luc Dendooven (Journal of Soils and Sediments, 2020)

Biodiversity conservation in China–Pakistan Economic Corridor region with strategic environmental assessment - Akhtar Hussain Lashari; Wei Li; Mabroor Hassan; Ghulam Nabi; Prince T Mabey; Mohammad Morshedul Islam; Khalid Hussain Rind; Safdar Ali Ujjan (Environmental Science and Pollution Research, 2020)

Improvising the efficiency of single-sloped solar still using thermally conductive nano-ferric oxide - Gurukarthik Babu Balachandran; Prince Winston David; Rajesh Kannan Mariappan; Abd Elnaby Kabeel; Muthu Manokar Athikesavan; Ravishankar Sathyamurthy (Environmental Science and Pollution Research, 2020)

Enhancement of PV/T-integrated single slope solar desalination still productivity using water film cooling and hybrid composite insulation - Gurukarthik Babu Balachandran; Prince Winston David; Aravind Bhaskar Panayilvedu Vijayakumar; Abd Elnaby Kabeel; Muthu Manokar Athikesavan; Ravishankar Sathyamurthy (Environmental Science and Pollution Research, 2020)

Ameliorative effect of curcumin on altered expression of CACNA1A and GABRD in the pathogenesis of FeCl3-induced epilepsy - Prince Kumar; Deepak Sharma (Molecular Biology Reports, 2020)

Vertical structure and evolution of monsoon circulation as observed by 205-MHz wind profiler radar - Ajil Kottayil; Prince Xavier; K. Satheesan; K. Mohanakumar; V. Rakesh (Meteorology and Atmospheric Physics, 2020)

Correction to: Characterization and genome sequencing of three Aeromonas hydrophila-specific phages, CF8, PS1, and PS2 - Sumeet Rai; Anuj Tyagi; Anu Kalia; B. T. Naveen Kumar; Prince Garg; Niraj K. Singh (Archives of Virology, 2020)

Characterization and genome sequencing of three Aeromonas hydrophila-specific phages, CF8, PS1, and PS2 - Sumeet Rai; Anuj Tyagi; Anu Kalia; B. T. Naveen Kumar; Prince Garg; Niraj K. Singh (Archives of Virology, 2020)

Enhancement of potable water production from an inclined photovoltaic panel absorber solar still by integrating with flat-plate collector - A. Muthu Manokar; M. Vimala; Ravishankar Sathyamurthy; A. E. Kabeel; D. Prince Winston; Ali J. Chamkha (Environment, Development and Sustainability, 2020)

Exploitation of a novel phenothiazine derivative for its anti-cancer activities in malignant glioblastoma - S. I. Omoruyi; O. E. Ekpo; D. M. Semenya; A. Jardine; S. Prince (Apoptosis, 2020)

Analysis on the effect of salinity in underwater wireless optical communication - Sanjay Kumar; Shanthi Prince; Jinka Venkata Aravind; Santosh Kumar G (Marine Georesources & Geotechnology, 2020)

Genetic characterization of cassava (Manihot esculenta Crantz) genotypes using agro-morphological and single nucleotide polymorphism markers - Kumba Y. Karim; Beatrice Ifie; Daniel Dzidzienyo; Eric Y. Danquah; Essie T. Blay; Jim B. A. Whyte; Peter Kulakow; Ismail Rabbi; Elizabeth Parkes; Lucky Omoigui; Prince E. Norman; Peter Iluebbey (Physiology and Molecular Biology of Plants, 2020)
Dearth of information on extent of genetic variability in cassava limits the genetic improvement of cassava genotypes in Sierra Leone. The aim of this study was to assess the genetic diversity and relationships within 102 cassava genotypes using agro-morphological and single nucleotide polymorphism markers. Morphological classification based on qualitative traits categorized the germplasm into five different groups, whereas the quantitative trait set had four groups. The SNP markers classified the germplasm into three main cluster groups. A total of seven principal components (PCs) in the qualitative and four PCs in the quantitative trait sets accounted for 79.03% and 72.30% of the total genetic variation, respectively. Significant and positive correlations were observed between average yield per plant and harvest index (r = 0.76 *** ), number of storage roots per plant and harvest index (r = 0.33*), height at first branching and harvest index (0.26*), number of storage roots per plant and average yield per plant (r = 0.58*), height at first branching and average yield per plant (r = 0.24*), length of leaf lobe and petiole length (r = 0.38*), number of leaf lobe and petiole length (r = 0.31*), width of leaf lobe and length of leaf lobe (r = 0.36*), number of leaf lobe and length of leaf lobe (r = 0.43*), starch content and dry matter content (r = 0.99***), number of leaf lobe and root dry matter (r = 0.30*), number of leaf lobe and starch content (r = 0.28*), and height at first branching and plant height (r = 0.45**). Findings are useful for conservation, management, short term recommendation for release and genetic improvement of the crop.

Decentralized forest governance and community representation outcomes: analysis of the modified taungya system in Ghana - Prince Osei-Wusu Adjei; Frank Kwaku Agyei; Joyce Osei Adjei (Environment, Development and Sustainability, 2020)

Quality of life in patients with liver tumors treated with holmium-166 radioembolization - Caren van Roekel; Maarten L. J. Smits; Jip F. Prince; Rutger C. G. Bruijnen; Maurice A. A. J. van den Bosch; Marnix G. E. H. Lam (Clinical & Experimental Metastasis, 2020)
Holmium-166 radioembolization is a palliative treatment option for patients with unresectable hepatic malignancies. Its influence on quality of life has not been evaluated yet. Since quality of life is very important in the final stages of disease, the aim of this study was to evaluate the effect of holmium-166 radioembolization on quality of life. Patients with hepatic malignancies were treated with holmium-166 radioembolization in the HEPAR I and II studies. The European Organization for Research and Treatment of Cancer QLQ-C30 and LMC21 questionnaires were used to evaluate quality of life at baseline, 1 week, 6 weeks and at 6, 9 and 12 months after treatment. The course of the global health status and symptom and functioning scales were analyzed using a linear mixed model. Quality of life was studied in a total of 53 patients with a compliance of 94%. Role functioning was the most affected functioning scale. Fatigue and pain were the most affected symptom scales. Changes in almost all categories were most notable at 1 week after treatment. A higher WHO performance score at baseline decreased global health status, physical functioning, role functioning and social functioning and it increased symptoms of fatigue, dyspnea and diarrhea. Quality of life in salvage patients with liver metastases treated with holmium-166 radioembolization was not significantly affected over time, although a striking decline was seen during the first week post-treatment. A WHO performance score > 0 at baseline significantly influenced quality of life.

The microbial community in an alkaline saline sediment of a former maar lake bed - Claudia L. Ibarra-Sánchez; Laurette Prince; José L. Aguirre-Noyola; Karla E. Sánchez-Cerda; Yendi E. Navaro-Noya; Marco Luna-Guido; Eloy Conde-Barajas; Luc Dendooven; Elizabeth Selene Gomez-Acata (Journal of Soils and Sediments, 2020)

Exploring methodological approaches to assess climate change vulnerability and adaptation: reflections from using life history approaches - Chandni Singh; Mark Tebboth; Dian Spear; Prince Ansah; Adelina Mensah (Regional Environmental Change, 2019)
People in developing countries face multiple risks, and their response decisions sit at the complex and often opaque interface of climatic stressors, constrained resource access, and changing livelihoods, social structures, and personal aspirations. Many risk management studies use a well-established toolkit of methodologies—household surveys, focus group discussions, and semi-structured interviews. We argue that such methodological conservatism tends to neglect the dynamic and differentiated nature of livelihood decisions. Since different methodologies privilege different portrayals of risk and response, we highlight how plural methodological approaches can capture a broader range of perspectives and problematisations. In this paper, we draw on life history (LH) interviews across four countries (Kenya, Namibia, Ghana, and India) to offer one way of expanding current methodological approaches on vulnerability and adaptation. We argue that LHs offer four key ‘value additions’. First, LHs give insights into the multiple and interacting nature of drivers of response behaviour. Second, they highlight intra-household dynamics to demonstrate how people with differential power shape risk management decisions. Third, LHs support explorations of past decisions, present situations, and future aspirations, thus producing temporally nuanced enquiries. Fourth, they provide a powerful analytical lens to capture the interplay of motivations, aspirations, and values on livelihood choices and adaptation outcomes. By adding value in these four ways, LHs challenge assumptions about how and why people respond to multiple risks and offer a nuanced understanding of adaptation processes.

Effect of pre-existing faults on the distribution of lower crust exhumation under extension: numerical modelling and implications for NW Ghana - Xiaojun Feng; Enyuan Wang; Prince O. Amponsah; Jérôme Ganne; Roland Martin; Mark W. Jessell (Geosciences Journal, 2019)

A Review on the Factors Affecting the Deposition, Retention, and Biodegradation of Oil Stranded on Beaches and Guidelines for Designing Laboratory Experiments - Michel Boufadel; Xiaolong Geng; Chunjiang An; Edward Owens; Zhi Chen; Kenneth Lee; Elliott Taylor; Roger C. Prince (Current Pollution Reports, 2019)

Mapping the spatial distribution and changes of oil palm land cover using an open source cloud-based mapping platform - Nur Shafira Nisa Shaharum; Helmi Zulhaidi Mohd Shafri; Wan Azlina Wan Ab Karim Ghani; Sheila Samsatli; Husni Mobarak Prince; Badronnisa Yusuf; Ahmed Mohamed Hamud (International Journal of Remote Sensing, 2019)

A comparison of machine-learning techniques for the prediction of the auroral electrojet index - Sumesh Gopinath; P R Prince (Journal of Earth System Science, 2019)

Morpho-molecular Divergence of Restorer Lines for Hybrid Rice ( Oryza sativa L.) Development - M.Z. Islam; M.A. Siddique; N. Akter; M.F.R.K. Prince; M.R. Islam; M. Anisuzzaman; M.A.K. Mian (Cereal Research Communications, 2019)

A 3D Computational Head Model Under Dynamic Head Rotation and Head Extension Validated Using Live Human Brain Data, Including the Falx and the Tentorium - Y.-C. Lu; N. P. Daphalapurkar; A. K. Knutsen; J. Glaister; D. L. Pham; J. A. Butman; J. L. Prince; P. V. Bayly; K. T. Ramesh (Annals of Biomedical Engineering, 2019)

Genetic variation of the most abundant forest‐dwelling rodents in Central Africa ( Praomys jacksoni complex): Evidence for Pleistocene refugia in both montane and lowland forests - Daniela Mizerovská; Violaine Nicolas; Terrence C. Demos; Dudu Akaibe; Marc Colyn; Christiane Denys; Prince K. Kaleme; Pionus Katuala; Jan Kennis; Julian C. Kerbis Peterhans; Anne Laudisoit; Alain Didier Missoup; et al. (Journal of Biogeography, 2019)
Aim We investigate the Plio‐Pleistocene evolutionary history of one of the most abundant rodents in Afrotropical forests. Specifically, we ask how their diversification was influenced by climate change, topography and major rivers. Location Tropical Africa: Lower Guinea (including Cameroon volcanic line; CVL ), Congolia, Albertine Rift ( AR ), Kenyan highlands ( KH ). Taxon Murine rodents of the Praomys jacksoni complex. Methods We used 849 genotyped individuals to describe the overall diversity and spatial genetic structure across a majority of their known distribution area. The combination of one mitochondrial and three nuclear markers was used to infer dated phylogenies using Bayesian and maximum likelihood approaches. Genetic structure was further assessed by multispecies coalescent species delimitation. Current and past distributions of particular taxa were predicted using environmental niche modelling. Results The complex is composed of five major genetic clades (proposed species). Two of them are restricted to specific habitat types (either montane forests of AR or wetlands in lowland forests along the Congo River), three others have wide geographic distributions and lower levels of ecological specialization. The earliest divergence is dated to the Plio‐Pleistocene boundary and is in accordance with the separation of AR forests and Guineo‐Congolian forests. Further diversification of the complex is associated with Pleistocene climate changes. Relatively stable refugia of suitable climatic conditions were identified in lowland Congolia (for two species currently distributed only in lowland forests) as well as in montane forests of CVL , AR , KH (playing the role of reservoirs of diversity). Large rivers, especially the Congo River, are important barriers to gene flow for most taxa, but probably were not the primary cause of differentiation. Main conclusions The evolutionary history of the complex was primarily affected by Pleistocene climate changes and diversification in forest refugia. There is little support for ecological parapatric speciation or the riverine barrier hypothesis.

Two-Staged Dielectric Barrier Discharge-Urea Configuration for the Removal of NO of NOx in a Simulated Coal-Combustion Flue Gas - Huang Jingyu; Prince Atta Opoku; Li Junwei; Eyram Norgbey; Emmanuel Hagan Brown (Water, Air, & Soil Pollution, 2019)

Eichhornia crassipes biodiesel as a renewable green fuel for diesel engine applications: performance, combustion, and emission characteristics - Harish Venu; Dhinakaran Venkataraman; Prince Purushothaman; Dhana Raju Vallapudi (Environmental Science and Pollution Research, 2019)

Multiple Imputation for Incomplete Data in Environmental Epidemiology Research - Prince Addo Allotey; Ofer Harel (Current Environmental Health Reports, 2019)

A microfluidic platform for the simultaneous quantification of methanogen populations in anaerobic digestion processes - Prince P. Mathai; Hannah M. Dunn; Kaushik Venkiteshwaran; Daniel H. Zitomer; James S. Maki; Satoshi Ishii; Michael J. Sadowsky (Environmental Microbiology, 2019)
Summary Methanogens are a diverse group of archaea that play a critical role in the global carbon cycle. The lack of appropriate molecular tools to simultaneously quantify numerous methanogenic taxa, however, has largely limited our ability to study these communities in a wide variety of habitats, such as anaerobic digesters (ADs). In this study, 34 probe‐based quantitative PCR (qPCR) assays were designed to target all known methanogenic genera within the archaeal phylum Euryarchaeota . These qPCR assays were adapted to a high‐throughput microfluidic platform, which allowed for the simultaneous detection and absolute quantification of numerous taxa in a single run. The resulting microfluidic qPCR (MFQPCR) platform was successfully used to decipher structure–function relationships among methanogenic communities in four laboratory‐scale digesters exposed to a transient organic overload. Twelve of the 34 genera targeted in the MFQPCR were detected in the ADs, similar to results obtained using high‐throughput sequencing. The MFQPCR platform and conventional qPCR assays also generated similar quantitative results. The MFQPCR tool developed here will help optimize AD technologies for efficient waste treatment and enhanced biogas production and can facilitate studies that will increase our understanding of methanogenic communities in other environments.

Investigations into solar flare effects using wavelet-based local intermittency measure - Sumesh Gopinath; P. R. Prince (Acta Geophysica, 2019)

Contraceptive Sperm Agglutinating Proteins Identified in Staphylococcus warneri, Natural Microflora of an Infertile Woman - Neeraj Chandra Pant; Ravinder Singh; Aditi Chauhan; Vijaya Gupta; Ravimohan S. Mavuduru; Vijay Prabha; Prince Sharma (Indian Journal of Microbiology, 2019)

What to do when you have almost nothing: A simple quantitative prescription for managing extremely data‐poor fisheries - Jeremy Prince; Adrian Hordyk (Fish and Fisheries, 2019)
The cost, complexity and the lack of technical capacity in many countries have made the scientific assessment and sustainable management of data‐poor fisheries a persistent problem. New and innovative approaches are needed to stop the ongoing decline of data‐poor fisheries and loss of coastal biodiversity they are driving. In recent decades, marine protected areas have become the most preferred form of management for study and have been widely implemented as broadly applicable powerful management tools for data‐poor fisheries, but although clearly capable of building biomass within sanctuaries, their effectiveness for sustaining fisheries is proving more difficult to substantiate. This study suggests the new approach needed is actually a return to the established basics of managing size selectivity. Previous studies have established the wisdom of managing size selectivity and fishing pressure to catch fish above the size or age of maturity, but their prescriptions are difficult to implement without age studies, or the capacity for controlling catches and fishing pressure. This study develops an easily implementable rule of thumb based simply on multiples of size of maturity and quantifies its benefit where controlling fishing pressure is not yet possible. Our study provides a timely reminder that even if used alone, size selectivity, the oldest form of management, still produces pretty good sustainable yields. We suggest our rule of thumb can be used to prevent data‐poor fisheries declining while capacity for more complex forms of assessment and management are developed.

SRAPs and EST-SSRs provide useful molecular diversity for targeting drought and salinity tolerance in Indian mustard - Prince Saini; Disha Kamboj; R. C. Yadav; Neelam R. Yadav (Molecular Biology Reports, 2019)

Interrelationship between late gestational ewe factor and early life lamb factors in semi-arid tropical region - Kalyan De; C. P. Swarnkar; L. L. L. Prince; S. F. Ali (Tropical Animal Health and Production, 2019)

Nonextensive and distance-based entropy analysis on the influence of sunspot variability in magnetospheric dynamics - Sumesh Gopinath; P. R. Prince (Acta Geodaetica et Geophysica, 2018)

Foundation species patch configuration mediates salt marsh biodiversity, stability and multifunctionality - Sinéad M. Crotty; Sean J. Sharp; Ada C. Bersoza; Kimberly D. Prince; Katheryne Cronk; Emma E. Johnson; Christine Angelini (Ecology Letters, 2018)
Foundation species enhance biodiversity and multifunctionality across many systems; however, whether foundation species patch configuration mediates their ecological effects is unknown. In a 6‐month field experiment, we test which attributes of foundation species patch configuration – i.e. patch size, total patch area, perimeter, area‐perimeter ratio, or connectivity – control biodiversity, stability and multifunctionality by adding a standardised density of mussel foundation species in patches of 1, 5, 10, 30, 60, 90 or 180 individuals to a southeastern US salt marsh. Over 67% of response variables increased with clustering of mussels, responses that were driven by increases in area–perimeter ratio (33%), decreases in perimeter (29%), or increases in patch size (5%), suggesting sensitivity to external stressors and/or dependence on foundation species‐derived niche availability and segregation. Thus, mussel configuration – by controlling the relative distribution of multidimensional patch interior and edge niche space – critically modulates this foundation species’ effects on ecosystem structure, stability and function.

Spatial Prediction of Nitrate Concentration Using GIS and ANFIS Modelling in Groundwater - Nalini Jebastina; G. Prince Arulraj (Bulletin of Environmental Contamination and Toxicology, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Impact of various lipophilic substituents on ruthenium(II), rhodium(III) and iridium(III) salicylaldimine-based complexes: synthesis, in vitro cytotoxicity studies and DNA interactions - Irwin Cassells; Tameryn Stringer; Alan T. Hutton; Sharon Prince; Gregory S. Smith (JBIC Journal of Biological Inorganic Chemistry, 2018)

Diosmin Prevents Isoproterenol-Induced Heart Mitochondrial Oxidative Stress in Rats - S. Sharmila Queenthy; P. Stanely Mainzen Prince; Babu John (Cardiovascular Toxicology, 2018)

The role of monsoon low‐level jet in modulating heavy rainfall events - Anu Xavier; Ajil Kottayil; K. Mohanakumar; Prince K. Xavier (International Journal of Climatology, 2018)
Monsoon low‐level jet (MLLJ) is an important component of Asian summer monsoon circulation, which is responsible for large‐scale distribution and variability of rainfall over the Indian subcontinent. The evolution of MLLJ characteristics prior to heavy rainfall days and its changes which lead to instances of heavy rainfall over the south‐western coast of India are studied. The European Centre for Medium Range Weather Forecasts (ECMWF) re‐analysis data and India Meteorological Department (IMD) rainfall data during 1979–2007 were used for this study. It is found that the MLLJ core speed, westerly wind depth, zonal water vapour flux, horizontal wind shear and cyclonic vorticity show a steady increase towards the day of heavy rainfall and gradually decrease thereafter. The intensification of these parameters not only brings in abundant moisture but also triggers convection, thereby resulting in the formation of heavy rainfall during monsoon season. The large‐scale advection of moisture brought about by strengthening of MLLJ is shown to be a prerequisite for heavy rainfall over the Indian subcontinent. An interesting result of this study is that heavy rainfall days may have some predictability by continuous monitoring of the progression of MLLJ.

Aquatic Invasive Species in the Great Lakes Region: An Overview - Luis E. Escobar; Sophie Mallez; Michael McCartney; Christine Lee; Daniel P. Zielinski; Ratna Ghosal; Przemyslaw G. Bajer; Carli Wagner; Becca Nash; Megan Tomamichel; Paul Venturelli; Prince P. Mathai; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

Loss of Kirrel family members alters glomerular structure and synapse numbers in the accessory olfactory bulb - Alexandra C. Brignall; Reesha Raja; Alina Phen; Janet E. A. Prince; Emilie Dumontier; Jean-François Cloutier (Brain Structure and Function, 2018)

Characterization of a virulent ranavirus isolated from marine ornamental fish in India - P. Sivasankar; K. Riji John; M. Rosalind George; P. Mageshkumar; M. Mohamed Manzoor; M. J. Prince Jeyaseelan (VirusDisease, 2017)

Bio-prospecting Bacterial Diversity of Hot Springs in Northern Himalayan Region of India for Laccases - Vijaya Gupta; Naveen Gupta; Neena Capalash; Prince Sharma (Indian Journal of Microbiology, 2017)

Detection of corn oil in adulterated olive and soybean oil by carbon stable isotope analysis - Jingyu Huang; Eyram Norgbey; Philip N. Nkrumah; Prince A. Opoku; Theresa O. Apreku (Journal of Consumer Protection and Food Safety, 2017)

A comparative genomic and transcriptomic analysis at the level of isolated root hair cells reveals new conserved root hair regulatory elements - Zhenzhen Qiao; Lise Pingault; Prince Zogli; Micaela Langevin; Niccole Rech; Andrew Farmer; Marc Libault (Plant Molecular Biology, 2017)

Establishing the link between market orientation and agricultural commercialization: Empirical evidence from Northern Ghana - Edward Martey; Prince M. Etwire; Alexander Nimo Wiredu; Benjamin D. K. Ahiabor (Food Security, 2017)

Development of Eudragit RS 100 Microparticles Loaded with Ropinirole: Optimization and In Vitro Evaluation Studies - Prince Muhammad Kashif; Asadullah Madni; Muhammad Ashfaq; Mubashar Rehman; Muhammad Ahmad Mahmood; Muhammad Imran Khan; Nayab Tahir (AAPS PharmSciTech, 2017)

ALOS PALSAR and Hyperion Data Fusion for Land Use Land Cover Feature Extraction - Vinay Kumar; Prince Agrawal; Shefali Agrawal (Journal of the Indian Society of Remote Sensing, 2017)

Heavy metal accumulation in organs of Oreochromis niloticus (Linnaeus, 1758) from industrial effluent-polluted aquatic ecosystem in Lagos, Nigeria - Prince Emeka Ndimele; Musa O. Pedro; Julius Ibukun Agboola; Kanayo Stephen Chukwuka; Alice O. Ekwu (Environmental Monitoring and Assessment, 2017)

Genetic appraisal of serological response post vaccination against enterotoxaemia (ET) in Malpura and Avikalin sheep - G. R. Gowane; Najif Akram; L. L. L. Prince; Ved Prakash; Arun Kumar (Tropical Animal Health and Production, 2017)

In vitro cytotoxicity assessment of a West Virginia chemical spill mixture involving 4-methylcyclohexanemethanol and propylene glycol phenyl ether - Alice A. Han; Emily B. Fabyanic; Julie V. Miller; Maren S. Prediger; Nicole Prince; Julia A. Mouch; Jonathan Boyd (Environmental Monitoring and Assessment, 2017)

Appraisal of nutrient distribution in the surface water and bed sediments of a small mountainous river - Prince George; Sabu Joseph (Environmental Monitoring and Assessment, 2017)

Subcellular distribution and chemical forms of Co2+ in three barley genotypes under different Co2+ levels - Jonas Lwalaba Wa Lwalaba; Gerald Zvobgo; Mulembo Mwamba; Imrul Mosaddek Ahmed; Robert Prince Mundende Mukobo; Guoping Zhang (Acta Physiologiae Plantarum, 2017)

Bio-Prospecting Laccases in the Bacterial Diversity of Activated Sludge From Pulp and Paper Industry - Vijaya Gupta; Neena Capalash; Naveen Gupta; Prince Sharma (Indian Journal of Microbiology, 2017)

Effects of a 1-year randomised controlled trial of resistance training on blood lipid profile and chylomicron concentration in older men - Anthony P. James; Joanna Whiteford; Timothy R. Ackland; Satvinder S. Dhaliwal; Jenni J. Woodhouse; Richard L. Prince; Xingqiong Meng; Deborah A. Kerr (European Journal of Applied Physiology, 2016)

Phylogeography of the heavily poached A frican common pangolin (Pholidota, Manis tricuspis ) reveals six cryptic lineages as traceable signatures of Pleistocene diversification - Philippe Gaubert; Flobert Njiokou; Gabriel Ngua; Komlan Afiademanyo; Sylvain Dufour; Jean Malekani; Sery Gonedelé Bi; Christelle Tougard; Ayodeji Olayemi; Emmanuel Danquah; Chabi A. M. S. Djagoun; Prince Kaleme; et al. (Molecular Ecology, 2016)
Knowledge on faunal diversification in African rainforests remains scarce. We used phylogeography to assess (i) the role of Pleistocene climatic oscillations in the diversification of the African common pangolin ( M anis tricuspis ) and (ii) the utility of our multilocus approach for taxonomic delineation and trade tracing of this heavily poached species. We sequenced 101 individuals for two mitochondrial DNA (mt DNA ), two nuclear DNA and one Y‐borne gene fragments (totalizing 2602 bp). We used a time‐calibrated, Bayesian inference phylogenetic framework and conducted character‐based, genetic and phylogenetic delineation of species hypotheses within African common pangolins. We identified six geographic lineages partitioned into western Africa, Ghana, the Dahomey Gap, western central Africa, Gabon and central Africa, all diverging during the Middle to Late Pleistocene. Mt DNA (cytochrome b + control region) was the sole locus to provide diagnostic characters for each of the six lineages. Tree‐based Bayesian delimitation methods using single‐ and multilocus approaches gave high support for ‘species’ level recognition of the six African common pangolin lineages. Although the diversification of African common pangolins occurred during Pleistocene cyclical glaciations, causative correlation with traditional rainforest refugia and riverine barriers in Africa was not straightforward. We conclude on the existence of six cryptic lineages within African common pangolins, which might be of major relevance for future conservation strategies. The high discriminative power of the mt DNA markers used in this study should allow an efficient molecular tracing of the regional origin of African common pangolin seizures.

Is Tridacna maxima (Bivalvia: Tridacnidae) at Ningaloo Reef, Western Australia? - Michael S. Johnson; Jane Prince; Anne Brearley; Natalie L. Rosser; Robert Black (Molluscan Research, 2016)

Genome-wide identification of the expansin gene family in tobacco (Nicotiana tabacum) - Anming Ding; Prince Marowa; Yingzhen Kong (Molecular Genetics and Genomics, 2016)

Decline in Additive Genetic Variance for Live Weight and Greasy Fleece Weight in Bharat Merino Sheep - G. R. Gowane; L. L. L. Prince; Ved Prakash; R. C. Sharma; Arun Kumar (Agricultural Research, 2016)

Bifurcation analysis of a two-compartment hippocampal pyramidal cell model - Laura A. Atherton; Luke Y. Prince; Krasimira Tsaneva-Atanasova (Journal of Computational Neuroscience, 2016)

Sub-seasonal behaviour of Asian summer monsoon under a changing climate: assessments using CMIP5 models - K. P. Sooraj; Pascal Terray; Prince Xavier (Climate Dynamics, 2016)

Expansins: roles in plant growth and potential applications in crop improvement - Prince Marowa; Anming Ding; Yingzhen Kong (Plant Cell Reports, 2016)

Investigating the impact of passive external lower limb compression on central and peripheral hemodynamics during exercise - Jennifer Book; Chekema N. Prince; Rodrigo Villar; Richard L. Hughson; Sean D. Peterson (European Journal of Applied Physiology, 2016)

Colin A. Wraight, 1945–2014 - Govindjee; Roger C. Prince; Donald R. Ort (Photosynthesis Research, 2016)

Desiccation as a mitigation tool to manage biofouling risks: trials on temperate taxa to elucidate factors influencing mortality rates - Grant A. Hopkins; Madeleine Prince; Patrick L. Cahill; Lauren M. Fletcher; Javier Atalah (Biofouling, 2016)

Pretreatment of garden biomass using Fenton’s reagent: influence of Fe2+ and H2O2 concentrations on lignocellulose degradation - Vivek P Bhange; SPM Prince William; Abhinav Sharma; Jagdish Gabhane; Atul N Vaidya; Satish R Wate (Journal of Environmental Health Science and Engineering, 2015)
Garden biomass (GB) is defined as low density and heterogeneous waste fraction of garden rubbish like grass clippings, pruning, flowers, branches, weeds; roots. GB is generally different from other types of biomass. GB is mostly generated through maintenance of green areas. GB can be processed for bio energy production as it contains considerably good amount of cellulose and hemicellulose. However, pretreatment is necessary to delignify and facilitate disruption of cellulosic moiety. The aim of the present investigation was to pretreat GB using Fenton’s reagent and to study the influence of Fe 2+ and H 2 O 2 concentrations on degradation of lignin and cellulose. The data were statistically analyzed using ANOVA and numerical point prediction tool of MINITAB RELEASE 14 to optimize different process variables such as temperature, concentration of Fe 2+ and H 2 O 2 . The results of the present investigation showed that Fenton’s reagent was effective on GB, however, concentration of Fe 2+ and H 2 O 2 play crucial role in determining the efficiency of pretreatment. An increase in H 2 O 2 concentration in Fenton’s reagent significantly increased the rate of cellulose and lignin degradation in contrast to increasing concentration of Fe 2+ ion which led to a decrease in lignocellulosic degradation.

Optimization and evaluation of CBSOL LE red wool dye adsorption from aqueous solution onto commercial activated carbon - P. Kaur; A. P. Singh; A. K. Prince; J. P. Kushwaha (International Journal of Environmental Science and Technology, 2015)

Biodiversity, environmental health and human well-being: analysis of linkages and pathways - Prince Osei-Wusu Adjei; Frank Kwaku Agyei (Environment, Development and Sustainability, 2015)

Effect of FecB status on the allometric measurements and reproductive performance of Garole × Malpura ewes under hot semi-arid environment - Veerasamy Sejian; Vijai Prakash Maurya; Lawrence Leslie Leo Prince; Davendra Kumar; Syed Mohammad Krusheed Naqvi (Tropical Animal Health and Production, 2015)

Segmentation of the Cerebellar Peduncles Using a Random Forest Classifier and a Multi-object Geometric Deformable Model: Application to Spinocerebellar Ataxia Type 6 - Chuyang Ye; Zhen Yang; Sarah H. Ying; Jerry L. Prince (Neuroinformatics, 2015)

Transfer behaviour and durability of cementitious mortars containing polycarbonate plastic wastes - Kinda Hannawi; William Prince-Agbodjan (European Journal of Environmental and Civil Engineering, 2015)

Seed coat micromorphology of Gordonia sensu lato (including Polyspora and Laplacea; Theaceae) - L. A. A. H. Gunathilake; Jeffrey S. Prince; Barbara A. Whitlock (Brittonia, 2015)

Characterization of Kota Sandstone Under Different Strain Rates in Uniaxial Loading - Md. Shams Alam; Tanusree Chakraborty; Vasant Matsagar; K. Seshagiri Rao; Prince Sharma; Manjit Singh (Geotechnical and Geological Engineering, 2015)

Species identification of mixed algal bloom in the Northern Arabian Sea using remote sensing techniques - R. Dwivedi; M. Rafeeq; B. R. Smitha; K. B. Padmakumar; Lathika Cicily Thomas; V. N. Sanjeevan; Prince Prakash; Mini Raman (Environmental Monitoring and Assessment, 2015)

Pretreatment of garden biomass by alkali-assisted ultrasonication: effects on enzymatic hydrolysis and ultrastructural changes - Jagdish Gabhane; SPM Prince William; Atul Narayan Vaidya; Duraisamy Anand; Satish Wate (Journal of Environmental Health Science and Engineering, 2014)
The present investigation aims at studying the effectiveness of alkali-assisted ultrasonication on pretreatment of garden biomass (GB). Dry and powdered GB suspended in 1% NaOH was ultrasonicated for 15, 30 and 60 minutes at a frequency of 25 KHZ. The mode of action and effectiveness of alkali-assisted ultrasonication on GB was established through microscopic, scanning electron microscopic and X-ray diffraction studies. A perusal of results showed that alkali-assisted ultrasonication led to fibrillation of GB which ultimately facilitated enzymatic hydrolysis. The results also indicated that alkali-assisted ultrasonication is an efficient means of pretreatment of GB at moderate (45-50°C) working temperature and low (1%) concentration of alkali. The yield of reducing sugar after enzymatic hydrolysis increased almost six times as compared to control due to alkali-assisted ultrasonication.

Evaluation of the effect of closed areas on a unique and shallow water coral reef fish assemblage reveals complex responses - G. Shedrawi; E. S. Harvey; D. L. McLean; J. Prince; L. M. Bellchambers; S. J. Newman (Coral Reefs, 2014)

Lactonase-expressing Lactobacillus plantarum NC8 attenuates the virulence factors of multiple drug resistant Pseudomonas aeruginosa in co-culturing environment - Sudha Joshi; Amanjot Kaur; Prince Sharma; Kusum Harjai; Neena Capalash (World Journal of Microbiology and Biotechnology, 2014)

A protocol for assessing the effectiveness of oil spill dispersants in stimulating the biodegradation of oil - Roger C. Prince; Josh D. Butler (Environmental Science and Pollution Research, 2014)

Genetic Analysis of Reproductive and Fitness Traits of Malpura Sheep in Semi-arid Tropics of India - G. R. Gowane; L. L. L. Prince; C. Paswan; S. S. Misra; R. C. Sharma; S. M. K. Naqvi (Agricultural Research, 2014)

Repeat region of Brugia malayi sheath protein (Shp-1) carries Dominant B epitopes recognized in filarial endemic population - Jeya Jawaharlal; Jayaprakasam Madhumathi; Rajaiah Prince; Perumal Kaliraj (Acta Parasitologica, 2014)
Transmission of lymphatic filariasis is mediated through microfilariae (L1 stage of the parasite) which is encased in an eggshell called sheath. The sheath protein Shp-1 stabilizes the structure due to the unique repeat region with Met-Pro-Pro-Gln-Gly sequences. Microfilarial proteins could be used as transmission blocking vaccines. Since the repeat region of Shp-1 was predicted to carry putative B epitopes, this region was used to analyze its reactivity with clinical samples towards construction of peptide vaccine. In silico analysis of Shp-1 showed the presence of B epitopes in the region 49–107. The polypeptide epitopic region Shp-149–107 was cloned and expressed in Escherichia coli. Antibody reactivity of the Shp-149–107 construct was evaluated in filarial endemic population by ELISA. Putatively immune endemic normals (EN) showed significantly high reactivity (P

Groundwater quality assessment using WQI and GIS techniques, Dindigul district, Tamil Nadu, India - N. S. Magesh; S. Krishnakumar; N. Chandrasekar; John Prince Soundranayagam (Arabian Journal of Geosciences, 2013)

Photoelectron spectroscopy and circular dichroism of a chiral metal–organic complex - D. Catone; S. Turchini; M. Stener; P. Decleva; G. Contini; T. Prosperi; V. Feyer; K. C. Prince; N. Zema (Rendiconti Lincei. Scienze Fisiche e Naturali, 2013)

Isolation and Identification of Environmental Mycobacteria in the Waters of a Hemodialysis Center - Flávio Garcia Sartori; Luís Fernando Leandro; Lilian Bueno Montanari; Maria Gorete Mendes de Souza; Regina Helena Pires; Daisy Nakamura Sato; Clarice Queico Fujimura Leite; Karina de Andrade Prince; Carlos Henrique Gomes Martins (Current Microbiology, 2013)

System for Integrated Neuroimaging Analysis and Processing of Structure - Bennett A. Landman; John A. Bogovic; Aaron Carass; Min Chen; Snehashis Roy; Navid Shiee; Zhen Yang; Bhaskar Kishore; Dzung Pham; Pierre-Louis Bazin; Susan M. Resnick; Jerry L. Prince (Neuroinformatics, 2013)

Principal Component Analysis of Cerebellar Shape on MRI Separates SCA Types 2 and 6 into Two Archetypal Modes of Degeneration - Brian C. Jung; Soo I. Choi; Annie X. Du; Jennifer L. Cuzzocreo; Zhuo Z. Geng; Howard S. Ying; Susan L. Perlman; Arthur W. Toga; Jerry L. Prince; Sarah H. Ying (The Cerebellum, 2012)

Spatiotemporal variation of macroinvertebrates in relation to canopy cover and other environmental factors in Eriora River, Niger Delta, Nigeria - Francis O. Arimoro; Grace E. Obi-Iyeke; Prince J. O. Obukeni (Environmental Monitoring and Assessment, 2012)

Binning algorithm for high-resolution IRS-P4 OCM chlorophyll image - Prince Prakash; T. Srinivasa Kumar; S. H. Rahman; Shailesh Nayak (International Journal of Remote Sensing, 2012)

N-acyl homoserine lactone mediated interspecies interactions between A. baumannii and P. aeruginosa - Nidhi Bhargava; Prince Sharma; Neena Capalash (Biofouling, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Impact of Pleistocene aridity oscillations on the population history of a widespread, vagile Australian mammal, Macropus fuliginosus - Linda E. Neaves; Kyall R. Zenger; Robert I. T. Prince; Mark D. B. Eldridge (Journal of Biogeography, 2012)
Aim Climatic fluctuations during the Pleistocene have shaped the population structure of many extant taxa. However, few studies have examined widespread species inhabiting the Australian continent, where periods of increased aridity characterized the Pleistocene. Here we investigate the phylogeography and population history of a widespread and vagile southern Australian marsupial, the western grey kangaroo ( Macropus fuliginosus ). Location Southern Australia. Methods We examined the variation of the mitochondrial DNA (mtDNA) control region from 511 individuals of M. fuliginosus sampled throughout their transcontinental distribution. Maximum likelihood and Bayesian analyses were used to investigate the phylogeography and coalescence analyses were then used to test hypothesized biogeographical scenarios. Results The combined results of the phylogeographical and coalescence analyses revealed a complex evolutionary history. Macropus fuliginosus originated in the south‐west of the continent, with north‐western and south‐western populations subsequently diverging as a result of vicariance events during the mid‐Pleistocene. Subsequent arid phases affected these populations differently. In the north‐west, the expansion and contraction of the arid zone resulted in repeated vicariance events and multiple divergent north‐western mtDNA subclades. In contrast, the south‐western population was less impacted by climatic oscillations but gave rise to a major transcontinental eastward expansion. Main conclusions Macropus fuliginosus exhibits the genetic signature of divergence due to unidentified barriers in south‐western Western Australia, while previously identified barriers across southern Australia appear to have had little impact despite evidence of a broad‐scale range expansion prior to the Last Glacial Maximum (LGM). This pattern of localized expansion and contraction is comparable to unglaciated regions in both the Northern and Southern Hemispheres. Furthermore, this study indicates that despite the potential similarities between Northern Hemisphere glaciation and the activation of dune systems in the Australian arid zone, both of which rendered large areas inhospitable, the biotic responses and resultant phylogeographical signatures are dissimilar. Whereas a limited number of major geographically concordant refugia are observed in glaciated areas, the Southern Hemisphere arid zone appears to be associated with multiple species‐specific idiosyncratic refugia.

Hydrogeochemical study of shallow carbonate aquifers, Rameswaram Island, India - S. Krishna Kumar; N. Chandrasekar; P. Seralathan; Prince S. Godson; N. S Magesh (Environmental Monitoring and Assessment, 2012)

Characterization of MspNI (G/GWCC) and MspNII (R/GATCY), novel thermostable Type II restriction endonucleases from Meiothermus sp., isoschizomers of AvaII and BstYI - Richa Gupta; Shuang-Yong Xu; Prince Sharma; Neena Capalash (Molecular Biology Reports, 2012)

MRI Shows a Region-Specific Pattern of Atrophy in Spinocerebellar Ataxia Type 2 - Brian C. Jung; Soo I. Choi; Annie X. Du; Jennifer L. Cuzzocreo; Howard S. Ying; Bennett A. Landman; Susan L. Perlman; Robert W. Baloh; David S. Zee; Arthur W. Toga; Jerry L. Prince; Sarah H. Ying (The Cerebellum, 2012)

Immunopathogenesis of Staphylococcus aureus pulmonary infection - Dane Parker; Alice Prince (Seminars in Immunopathology, 2012)

Estimating demographic parameters for a critically endangered marine species with frequent reproductive omission: hawksbill turtles nesting at Varanus Island, Western Australia - Robert I. T. Prince; Milani Chaloupka (Marine Biology, 2012)

Lead Levels in Breast Milk, Blood Plasma and Intelligence Quotient: A Health Hazard for Women and Infants - C. Prince Jebadass Isaac; A. Sivakumar; C. Rebecca Prem Kumar (Bulletin of Environmental Contamination and Toxicology, 2012)

The effects of modulating eNOS activity and coupling in ischemia/reperfusion (I/R) - Kerry-Anne A. Perkins; Sailesh Pershad; Qian Chen; Sloane McGraw; Jovan S. Adams; Christopher Zambrano; Samuel Krass; Jeffrey Emrich; Brandon Bell; Michael Iyamu; Catherine Prince; Helen Kay; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Laccase from prokaryotes: a new source for an old enzyme - Gursharan Singh; Aditya Bhalla; Paramjit Kaur; Neena Capalash; Prince Sharma (Reviews in Environmental Science and Bio/Technology, 2011)

Promotion of Growth in Mungbean (Phaseolus aureus Roxb.) by Selenium is Associated with Stimulation of Carbohydrate Metabolism - Jahid Ali Malik; Sanjeev Kumar; Prince Thakur; Suchi Sharma; Navneet Kaur; RamanPreet Kaur; D. Pathania; Kalpna Bhandhari; Neeru Kaushal; Kamaljit Singh; Alok Srivastava; Harsh Nayyar (Biological Trace Element Research, 2011)

Phenolic acid content in potato peel determines natural infection of common scab caused by Streptomyces spp. - Prince K. Singhai; Birinchi K. Sarma; Jai S. Srivastava (World Journal of Microbiology and Biotechnology, 2011)

Proline induces heat tolerance in chickpea (Cicer arietinum L.) plants by protecting vital enzymes of carbon and antioxidative metabolism - Neeru Kaushal; Kriti Gupta; Kalpna Bhandhari; Sanjeev Kumar; Prince Thakur; Harsh Nayyar (Physiology and Molecular Biology of Plants, 2011)

Growth and metabolic responses of contrasting chickpea (Cicer arietinum L.) genotypes to chilling stress at reproductive phase - Sanjeev Kumar; Jahid Malik; Prince Thakur; Suchi Kaistha; Kamal Dev Sharma; H. D. Upadhyaya; J. D. Berger; Harsh Nayyar (Acta Physiologiae Plantarum, 2011)

Preventive Effects of Vanillic Acid on Lipids, Bax, Bcl-2 and Myocardial Infarct Size on Isoproterenol-Induced Myocardial Infarcted Rats: A Biochemical and In Vitro Study - P. Stanely Mainzen Prince; K. Dhanasekar; S. Rajakumar (Cardiovascular Toxicology, 2011)

Depositional environment and faunal assemblages of the reef-associated beachrock at Rameswaram and Keelakkarai Group of Islands, Gulf of Mannar, India - S. Krishna Kumar; N. Chandrasekar; P. Seralathan; Prince S. Godson (Frontiers of Earth Science, 2011)

Genetic analysis for growth traits of prolific Garole × Malpura (GM) sheep - Gopal R. Gowane; Ashish Chopra; L. L. L. Prince; A. K. Mishra; A. L. Arora (Tropical Animal Health and Production, 2011)

An analysis of land use pattern in the industrial development city using high resolution satellite imagery - John Prince Soundranayagam; P. Sivasubramanian; N. Chandrasekar; K. S. P. Durairaj (Journal of Geographical Sciences, 2011)

Crucial epitopes of Wuchereria bancrofti abundant larval transcript recognized in natural infection - J. Madhumathi; D. Pradiba; P. R. Prince; P. J. Jeyaprita; D. N. Rao; P. Kaliraj (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Ocean scale hypoxia‐based habitat compression of Atlantic istiophorid billfishes - ERIC D. PRINCE; JIANGANG LUO; C. PHILLIP GOODYEAR; JOHN P. HOOLIHAN; DERKE SNODGRASS; ERIC S. ORBESEN; JOSEPH E. SERAFY; MAURICIO ORTIZ; MICHAEL J. SCHIRRIPA (Fisheries Oceanography, 2010)
Oxygen minimum zones (OMZs) below near‐surface optimums in the eastern tropical seas are among the largest contiguous areas of naturally occurring hypoxia in the world oceans, and are predicted to expand and shoal with global warming. In the eastern tropical Pacific (ETP), the surface mixed layer is defined by a shallow thermocline above a barrier of cold hypoxic water, where dissolved oxygen levels are ≤3.5 mL L −1 . This thermocline (∼25–50 m) constitutes a lower hypoxic habitat boundary for high oxygen demand tropical pelagic billfish and tunas (i.e., habitat compression). To evaluate similar oceanographic conditions found in the eastern tropical Atlantic (ETA), we compared vertical habitat use of 32 sailfish ( Istiophorus platypterus ) and 47 blue marlin ( Makaira nigricans ) monitored with pop‐up satellite archival tags in the ETA and western North Atlantic (WNA). Both species spent significantly greater proportions of their time in near‐surface waters when inside the ETA than when in the WNA. We contend that the near‐surface density of billfish and tunas increases as a consequence of the ETA OMZ, therefore increasing their vulnerability to overexploitation by surface gears. Because the ETA OMZ encompasses nearly all Atlantic equatorial waters, the potential impacts of overexploitation are a concern. Considering the obvious differences in catchability inside and outside the compression zones, it seems essential to standardize these catch rates separately to minimize inaccuracies in stock assessments for these species. This is especially true in light of global warming, which will likely exacerbate future compression impacts.

Protective Effects of Rutin on Mitochondrial Damage in Isoproterenol-Induced Cardiotoxic Rats: An In Vivo and In Vitro Study - V. R. Punithavathi; K. Shanmugapriya; P. Stanely Mainzen Prince (Cardiovascular Toxicology, 2010)

Estimates of (co)variance components and genetic parameters for growth traits of Avikalin sheep - Leslie Leo L. Prince; Gopal R. Gowane; Ashish Chopra; Amrit L. Arora (Tropical Animal Health and Production, 2010)

Estimates of genetic parameters for faecal egg count of Haemonchus contortus infection and relationship with growth traits in Avikalin sheep - Leslie Leo L. Prince; G. R. Gowane; C. P. Swarnkar; D. Singh; A. L. Arora (Tropical Animal Health and Production, 2010)

Erratum to: The Java Image Science Toolkit (JIST) for Rapid Prototyping and Publishing of Neuroimaging Software - Blake C. Lucas; John A. Bogovic; Aaron Carass; Pierre-Louis Bazin; Jerry L. Prince; Dzung L. Pham; Bennett A. Landman (Neuroinformatics, 2010)

The Java Image Science Toolkit (JIST) for Rapid Prototyping and Publishing of Neuroimaging Software - Blake C. Lucas; John A. Bogovic; Aaron Carass; Pierre-Louis Bazin; Jerry L. Prince; Dzung L. Pham; Bennett A. Landman (Neuroinformatics, 2010)

Synergistic application of oceanographic variables from multi-satellite sensors for forecasting potential fishing zones: methodology and validation results - H. U. Solanki; Prince Prakash; R. M. Dwivedi; Shailesh Nayak; Arvind Kulkarni; V. S. Somvamshi (International Journal of Remote Sensing, 2010)

Importance of the Straits of Florida spawning ground to Atlantic sailfish ( Istiophorus platypterus ) and blue marlin ( Makaira nigricans ) - DAVID E. RICHARDSON; ROBERT K. COWEN; ERIC D. PRINCE; Su SPONAUGLE (Fisheries Oceanography, 2009)
Much of the uncertainty in managing highly migratory pelagic species results from the scarcity of fisheries‐independent data relevant to determining long‐term trends in abundance, migratory movements, and the relative importance of different spawning grounds. To address these issues, we used an ichthyoplankton‐based method to quantify the overall level of spawning of sailfish ( Istiophorus platypterus ) and blue marlin ( Makaira nigricans ) in the Straits of Florida (SF). We estimated that during the 2 years (2003–2004) of the study, 4.60 × 10 11 sailfish eggs and 4.49 × 10 11 blue marlin eggs were produced on an annual basis in this region. These egg production values, when combined with estimates of annual fecundity for each species and the most recent stock assessment estimate of total biomass, indicate that about 2.1% of Western Atlantic sailfish spawning and 1.6% of Atlantic‐wide blue marlin spawning occurs in the SF. Additionally, pop‐up satellite tags deployed on sailfish at the start of the spawning season revealed their short residency times in the SF, suggesting that a large (≈13%) transient portion of the sailfish population is responsible for the SF egg production. Overall, this study provides a critically needed fisheries‐independent method of quantifying spatial and temporal trends in the abundance of highly migratory species. The application of this methodology in the SF indicated that above‐average levels of sailfish and blue marlin spawning occur in this area and, possibly more importantly, that the SF is a migratory bottleneck for these species.

Strategies and issues in the detection of pathway enrichment in genome-wide association studies - Mun-Gwan Hong; Yudi Pawitan; Patrik K. E. Magnusson; Jonathan A. Prince (Human Genetics, 2009)

Landscape discontinuities influence gene flow and genetic structure in a large, vagile Australian mammal, Macropus fuliginosus - LINDA E. NEAVES; KYALL R. ZENGER; ROBERT I. T. PRINCE; MARK D. B. ELDRIDGE; DESMOND W. COOPER (Molecular Ecology, 2009)
Large vagile mammals typically exhibit little genetic structuring across their range, particularly when their habitat is essentially continuous. We investigated the population genetic structure of a large vagile Australian macropodid, Macropus fuliginosus, which is continuously distributed across most of southern Australia, using nine highly polymorphic nuclear microsatellite loci. Five distinct genetic units were identified across the range, four on the mainland and one on Kangaroo Island. In addition to the predicted historic Nullarbor Plain Barrier, two unexpected mainland barriers to gene flow were identified. Both were associated with landscape discontinuities (Swan River, Flinders Ranges), which appear within the dispersal capabilities of M. fuliginosus. Typical of large vagile mammals, M. fuliginosus displays high genetic diversity (with the exception of an insular population) and weak genetic structuring (within genetic units). However, the expansion of M. fuliginosus from southwestern Australia during the Pleistocene has resulted in significantly reduced genetic diversity in eastern populations. No significant sex‐biased dispersal was detected, although differences in habitat, densities and climatic conditions between the eastern and western regions of the range appear to influence dispersal with the effects of isolation by distance only evident in the west. These results suggest that the biogeography of southern Australia is more complex than previously thought and reveal that seemingly minor landscape features can significantly impact genetic structuring in large vagile mammals.

Characterization of a modified nitrogenase Fe protein from Klebsiella pneumoniae in which the 4Fe4S cluster has been replaced by a 4Fe4Se cluster - Patrick Clark Hallenbeck; Graham N. George; Roger C. Prince; Roger N. F. Thorneley (JBIC Journal of Biological Inorganic Chemistry, 2009)

Hisslers observed during daytime in a low latitude ground station - Krishna Kumar Singh; Ravindra Pratap Patel; Balraj Kumar; Mohamad Altaf; Prince Ahmad Ganai; Abhay Kumar Singh; Ram Pal Singh; Lalmani (Acta Geophysica, 2009)

Appraisal of immunomodulatory potential of Spirulina fusiformis: an in vivo and in vitro study - Mahaboobkhan Rasool; Evan Prince Sabina (Journal of Natural Medicines, 2009)

Axon Guidance Events in the Wiring of the Mammalian Olfactory System - Jin Hyung Cho; Janet E. A. Prince; Jean-François Cloutier (Molecular Neurobiology, 2009)

Chalk dustfall during classroom teaching: particle size distribution and morphological characteristics - Deepanjan Majumdar; S. P. M. Prince William (Environmental Monitoring and Assessment, 2009)

Comparison of Neutralizing Antibody Assays for Receptor Binding and Enzyme Activity of the Enzyme Replacement Therapeutic Naglazyme® (Galsulfase) - Joleen T. White; Lisa Argento Martell; William S. Prince; Ryan Boyer; Lucy Crockett; Christopher Cox; Andrea Van Tuyl; Allora Aguilera; Erik Foehr (The AAPS Journal, 2008)

A differential series of pepper (Capsicum annuum) lines delineates fourteen physiological races of Phytophthora capsici - Bonnie R. Glosier; Ebenezer A. Ogundiwin; Gurmel S. Sidhu; David R. Sischo; James P. Prince (Euphytica, 2008)

Effects of harmful algal blooms on competitors: Allelopathic mechanisms of the red tide dinoflagellate Karenia brevis - Emily K. Prince; Tracey L. Myers; Julia Kubanek (Limnology and Oceanography, 2008)
Because competitive interactions may have led to adaptations enabling bloom‐forming phytoplankton to dominate pelagic communities, we explored the allelopathic effects of one red tide dinoflagellate, Karenia brevis , on competing phytoplankton species. Exposure to waterborne compounds from natural 9;A. brevis blooms resulted in growth inhibition or death for four of five co‐occurring species tested, whereas compounds exuded by 9A. brevis cultures suppressed three of these same competitors (the diatoms Asterionellopsis glacialis and Skeletonema costatum and the dinoflagellate Prorocentrum minimum ) plus one additional species (the dinoflagellate Akashiwo cf. sanguinea ) that was unaffected by bloom exudates. 9A. brevis exudates lowered photosynthetic efficiency and damaged cell membranes of competing phytoplankton, but had no effect on competitor esterase activity, nor did they limit competitor access to iron. Overall, during blooms, 9A. brevis exudes potent allelopathic compounds, competitors vary in their susceptibility to 9A. brevis allelopathy, and 9A. brevis may achieve nearly monospecific blooms by lowering the photosynthetic efficiency of competitor species and increasing competitor membrane permeability, eventually resulting in competitor growth suppression or death.

Natural resistance to Alfalfa mosaic virus in different lupin species - R. A. C. Jones; R. M. Pearce; R. T. Prince; B. A. Coutts (Australasian Plant Pathology, 2008)

Hexavalent uranium supports growth of Anaeromyxobacter dehalogenans and Geobacter spp. with lower than predicted biomass yields - Robert A. Sanford; Qingzhong Wu; Youlboong Sung; Sara H. Thomas; Benjamin K. Amos; Emily K. Prince; Frank E. Löffler (Environmental Microbiology, 2007)
Summary The stimulation of bacteria capable of reducing soluble U(VI) to sparingly soluble U(IV) is a promising approach for containing U(VI) plumes. Anaeromyxobacter dehalogenans is capable of mediating this activity; however, its ability to couple U(VI) reduction to growth has not been established. Monitoring the increase in 16S rRNA gene copy numbers using quantitative real‐time PCR (qPCR) in cultures provided with U(VI) as an electron acceptor demonstrated growth, and 7.7–8.6 × 10 6 cells were produced per μmole of U(VI) reduced. This biomass yield was lower than predicted based on the theoretical free energy changes associated with U(VI)‐to‐U(IV) reduction. Lower than predicted growth yields with U(VI) as electron acceptor were also determined in cultures of Geobacter lovleyi and Geobacter sulfurreducens suggesting that U(VI) reduction is inefficient or imposes an additional cost to growing cells. These findings have implications for U(VI) bioremediation because Anaeromyxobacter spp. and Geobacter spp. contribute to radionuclide immobilization in contaminated subsurface environments.

Anaerobic biodegradation of natural gas condensate can be stimulated by the addition of gasoline - Roger C. Prince; Joseph M. Suflita (Biodegradation, 2007)

Desertification in the Sahel: a reinterpretation of a reinterpretation - STEPHEN D. PRINCE; KONRAD J. WESSELS; COMPTON J. TUCKER; SHARON E. NICHOLSON (Global Change Biology, 2007)
In semiarid regions the ratio of annual net primary production to precipitation, rain‐use efficiency (RUE), has been used as an index of desertification. In a recent publication ( Hein & de Ridder, 2006 ) it was proposed that an incorrect understanding of the relationship between RUE and rainfall has led to a misinterpretation of the satellite record of desertification in the African Sahel. Here, we examine this suggestion and show that, contrary to Hein and de Ridder's statement, satellite studies of Sahelian RUE have reported increases, decreases, and constant values since 1981. Furthermore, we find that data do not support their proposal that RUE increases with rainfall, even in nondegraded areas. Hence we reject their corollary, that constant RUE is prima facie evidence of desertification. The fundamental difficulty with the use of RUE for detection of desertification remains, that is the difficulty of estimation of the RUE for nondegraded land at a regional scale.

Review - Bill Streever; Harold H. Prince; Scudder D. Mackey (Wetlands, 2007)

Circle hooks, ‘J’ hooks and drop‐back time: a hook performance study of the south Florida recreational live‐bait fishery for sailfish, Istiophorus platypterus - E. D. PRINCE; D. SNODGRASS; E. S. ORBESEN; J. P. HOOLIHAN; J. E. SERAFY; J. E. SCHRATWIESER (Fisheries Management and Ecology, 2007)
This study evaluates the performance of two types of non‐offset circle hooks (traditional and non‐traditional) and a similar‐sized ‘J’ hook commonly used in the south Florida recreational live‐bait fishery for Atlantic sailfish, Istiophorus platypterus (Shaw). A total of 766 sailfish were caught off south Florida (Jupiter to Key West, FL, USA) to assess hook performance and drop‐back time, which is the interval between the fish's initial strike and exertion of pressure by the fisher to engage the hook. Four drop‐back intervals were examined (0–5, 6–10, 11–15 and >15 s), and hook performance was assessed in terms of proportions of successful catch, undesirable hook locations, bleeding events and undesirable release condition associated with physical hook damage and trauma. In terms of hook performance, the traditionally‐shaped circle hook had the greatest conservation benefit for survival after release. In addition, this was the only hook type tested that performed well during each drop‐back interval for all performance metrics. Conversely, ‘J’ hooks resulted in higher proportions of undesirable hook locations (as much as twofold), bleeding and fish released in undesirable condition, particularly during long drop‐back intervals. Non‐traditional circle hooks had performance results intermediate to the other hook types, but also had the worst performance relative to undesirable release condition during the first two drop‐back intervals. Choice of hook type and drop‐back interval can significantly change hook wounding, and different models of non‐offset circle hooks should not be assumed to perform equivalently.

Use of pyrosequencing to identify point mutations in domain V of 23S rRNA genes of linezolid-resistant Staphylococcus aureus and Staphylococcus epidermidis - W. Zhu; F. C. Tenover; J. Limor; D. Lonsway; D. Prince; W. M. Dunne; J. B. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Annual migrations, diving behavior, and thermal biology of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre Boustany; Heidi Dewar; Michael J. W. Stokesbury; Kevin C. Weng; Shana Beemer; Andrew C. Seitz; Charles J. Farwell; Eric D. Prince; Barbara A. Block (Marine Biology, 2007)

Rutin improves the antioxidant status in streptozotocin-induced diabetic rat tissues - N Kamalakkannan; P Stanely Mainzen Prince (Molecular and Cellular Biochemistry, 2006)

The genetic structure of Australasian green turtles ( Chelonia mydas ): exploring the geographical scale of genetic exchange - KIKI E. M. DETHMERS; DAMIEN BRODERICK; CRAIG MORITZ; NANCY N. FITZSIMMONS; COLIN J. LIMPUS; SHANE LAVERY; SCOTT WHITING; MICK GUINEA; ROBERT I. T. PRINCE; ROD KENNETT (Molecular Ecology, 2006)
Ecological and genetic studies of marine turtles generally support the hypothesis of natal homing, but leave open the question of the geographical scale of genetic exchange and the capacity of turtles to shift breeding sites. Here we combine analyses of mitochondrial DNA (mtDNA) variation and recapture data to assess the geographical scale of individual breeding populations and the distribution of such populations through Australasia. We conducted multiscale assessments of mtDNA variation among 714 samples from 27 green turtle rookeries and of adult female dispersal among nesting sites in eastern Australia. Many of these rookeries are on shelves that were flooded by rising sea levels less than 10 000 years ( c . 450 generations) ago. Analyses of sequence variation among the mtDNA control region revealed 25 haplotypes, and their frequency distributions indicated 17 genetically distinct breeding stocks (Management Units) consisting either of individual rookeries or groups of rookeries in general that are separated by more than 500 km. The population structure inferred from mtDNA was consistent with the scale of movements observed in long‐term mark–recapture studies of east Australian rookeries. Phylogenetic analysis of the haplotypes revealed five clades with significant partitioning of sequence diversity (Φ = 68.4) between Pacific Ocean and Southeast Asian/Indian Ocean rookeries. Isolation by distance was indicated for rookeries separated by up to 2000 km but explained only 12% of the genetic structure. The emerging general picture is one of dynamic population structure influenced by the capacity of females to relocate among proximal breeding sites, although this may be conditional on large population sizes as existed historically across this region.

Hypoxia‐based habitat compression of tropical pelagic fishes - ERIC D. PRINCE; C. PHILLIP GOODYEAR (Fisheries Oceanography, 2006)
Large areas of cold hypoxic water occur as distinct strata in the eastern tropical Pacific (ETP) and Atlantic oceans as a result of high productivity initiated by intense nutrient upwelling. We show that this stratum restricts the depth distribution of tropical pelagic marlins, sailfish, and tunas by compressing the acceptable physical habitat into a narrow surface layer. This layer extends downward to a variable boundary defined by a shallow thermocline, often at 25 m, above a barrier of cold hypoxic water. The depth distributions of marlin and sailfish monitored with electronic tags and average dissolved oxygen (DO) and temperature profiles show that this cold hypoxic environment constitutes a lower habitat boundary in the ETP, but not in the western North Atlantic (WNA), where DO is not limiting. Eastern Pacific and eastern Atlantic sailfish are larger than those in WNA, where the hypoxic zone is much deeper or absent. Larger sizes may reflect enhanced foraging opportunities afforded by the closer proximity of predator and prey in compressed habitat, as well as by the higher productivity. The shallow band of acceptable habitat restricts these fishes to a very narrow surface layer and makes them more vulnerable to over‐exploitation by surface gears. Predictably, the long‐term landings of tropical pelagic tunas from areas of habitat compression have been far greater than in surrounding areas. Many tropical pelagic species in the Atlantic Ocean are currently either fully exploited or overfished and their future status could be quite sensitive to increased fishing pressures, particularly in areas of habitat compression.

The Effect of Vegetation Productivity on Millet Prices in the Informal Markets of Mali, Burkina Faso and Niger - Molly E. Brown; Jorge E. Pinzon; Stephen D. Prince (Climatic Change, 2006)

Production of Cellulase-Free Xylanase from Bacillus megaterium by Solid State Fermentation for Biobleaching of Pulp - Indu Sindhu; Sanjay Chhibber; Neena Capalash; Prince Sharma (Current Microbiology, 2006)

Antitumour activity of crocetin in accordance to tumor incidence, antioxidant status, drug metabolizing enzymes and histopathological studies - Venkatraman Magesh; Jayapal Prince Vijaya Singh; Karupaya Selvendiran; Ganapathy Ekambaram; Dhanapal Sakthisekaran (Molecular and Cellular Biochemistry, 2006)

Vertical habitat utilization by large pelagic animals: a quantitative framework and numerical method for use with pop‐up satellite tag data - JIANGANG LUO; ERIC D. PRINCE; C. PHILLIP GOODYEAR; BRIAN E. LUCKHURST; JOSEPH E. SERAFY (Fisheries Oceanography, 2006)
A quantitative framework and numerical methodology were developed to characterize vertical habitat utilization by large pelagic animals and to estimate the probability of their capture by certain types of fishing gear. Described are the steps involved to build ‘vertical habitat envelopes’ from data recovered from an electronically tagged blue marlin ( Makaira nigricans ) as well as from a longline fishing gear experiment employing temperature–depth recording devices. The resulting vertical habitat envelopes, which integrate depth and temperature preferences of tagged fish, are conducive for comparative studies of animal behavior and for calculation (and visualization) of degrees of overlap – be it among individuals, species or fishing gear. Results of a computer simulation evaluation indicated our numerical procedure to be reliable for estimating vertical habitat use from data summaries. The approach appears to have utility for examining pelagic longline fishing impacts on both target and non‐target species and could point to ways of reducing bycatch via modification of fishing strategy or gear configuration.

Agrobacterium-mediated transformation of seedling-derived maize callus - Vladimir Sidorov; Larry Gilbertson; Prince Addae; David Duncan (Plant Cell Reports, 2006)

Fitness consequences for copepods feeding on a red tide dinoflagellate: deciphering the effects of nutritional value, toxicity, and feeding behavior - Emily K. Prince; Liliana Lettieri; Katherine J. McCurdy; Julia Kubanek (Oecologia, 2006)

Towards compendia of negative genetic association studies: an example for Alzheimer disease - Mia E-L. Blomqvist; Chandra Reynolds; Hagit Katzov; Lars Feuk; Niels Andreasen; Nenad Bogdanovic; Kaj Blennow; Anthony J. Brookes; Jonathan A. Prince (Human Genetics, 2006)

A test for ectopic exchange catalyzed by Cre recombinase in maize - Thomas S. Ream; Jonathan Strobel; Brandon Roller; Donald L. Auger; Akio Kato; Cynthia Halbrook; Eric M. Peters; James Theuri; Matthew J. Bauer; Prince Addae; Waly Dioh; Jeffrey M. Staub; et al. (Theoretical and Applied Genetics, 2005)

Chemopreventive effect of piperine on mitochondrial TCA cycle and phase-I and glutathione-metabolizing enzymes in benzo(a)pyrene induced lung carcinogenesis in Swiss albino mice - K. Selvendiran; C. Thirunavukkarasu; J. Prince Vijeya Singh; R. Padmavathi; D. Sakthisekaran (Molecular and Cellular Biochemistry, 2005)

Development of sequence characterized amplified region (SCAR) primers for the detection of Phyto.5.2, a major QTL for resistance to Phytophthora capsici Leon. in pepper - E. A. Quirin; E. A. Ogundiwin; J. P. Prince; M. Mazourek; M. O. Briggs; T. S. Chlanda; K-T Kim; M. Falise; B-C Kang; M. M. Jahn (Theoretical and Applied Genetics, 2005)

UNOLS Establishes SCOAR to Promote Research Aircraft Facilities for U.S. Ocean Sciences - John Bane; Robert Bluth; Charles Flagg; Carl Friehe; Haflidi Jonsson; Kendall Melville; Mike Prince; Daniel Riemer (Oceanography, 2004)

Characterization of BflI – A Thermostable, Co++-Requiring Isoschizomer of BsiYI from Anoxybacillus Flavithermus - David R. D'Souza; Richard D. Morgan; Vijay Parashar; Neena Capalash; Prince Sharma (World Journal of Microbiology and Biotechnology, 2004)

Balance control during an arm raising movement in bipedal stance: which biomechanical factor is controlled? - Myriam Ferry; Luc Martin; Nicolas Termoz; Julie Côté; Francois Prince (Biological Cybernetics, 2004)

Copper and dyes enhance laccase production in γ-proteobacterium JB - Kanam Malhotra; Prince Sharma; Neena Capalash (Biotechnology Letters, 2004)

The effects of light and thallus scour from Ecklonia radiata canopy on an associated foliose algal assemblage: the importance of photoacclimation - Benjamin Toohey; Gary A. Kendrick; Thomas Wernberg; Julia C. Phillips; Sairah Malkin; Jane Prince (Marine Biology, 2004)

Variants of CYP46A1 may interact with age and APOE to influence CSF A42 levels in Alzheimer?s disease - Lars Feuk; Boo Johansson; Nenad Bogdanovic; Annica Johansson; Niels Andreasen; Boris Lenhard; Anthony J. Brookes; Nancy L. Pedersen; Kaj Blennow; Jonathan A. Prince; Henrik Zetterberg; Hagit Katzov (Human Genetics, 2004)

Remotely Sensed Interannual Variations and Trends in Terrestrial Net Primary Productivity 1981?2000 - Mingkui Cao; Stephen D. Prince; Jennifer Small; Scott J. Goetz (Ecosystems, 2004)

Common variants of ACE contribute to variable age-at-onset of Alzheimer’s disease - Patrick G. Kehoe; Hagit Katzov; Niels Andreasen; Maragaret Gatz; Gordon K. Wilcock; Nigel J. Cairns; Juni Palmgren; Ulf de Faire; Anthony J. Brookes; Nancy L. Pedersen; Kaj Blennow; Jonathan A. Prince (Human Genetics, 2004)

Design and analysis of multiple choice feeding preference data - Jeffrey S. Prince; W. G. LeBlanc; S. Maci (Oecologia, 2004)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Thioredoxinh overexpressed in barley seeds enhances selenite resistance and uptake during germination and early seedling development - Yong-Bum Kim; Carlos Garbisu; Ingrid J. Pickering; Roger C. Prince; Graham N. George; Myeong-Je Cho; Joshua H. Wong; Bob B. Buchanan (Planta, 2003)

The Insulator Effect of the 5′HS4 Region from the β-globin Chicken Locus on the Rabbit WAP Gene Promoter Activity in Transgenic Mice - Sylvie Rival-Gervier; Thais Pantano; Céline Viglietta; Caroline Maeder; Sonia Prince; Joe Attal; Geneviève Jolivet; Louis-Marie Houdebine (Transgenic Research, 2003)

The barefoot ecologist goes fishing - Jeremy D Prince (Fish and Fisheries, 2003)
Haliotid (abalone) fisheries are comprised of small‐scale ( 2 ) stocks and serve as a model for many such fisheries. Extremely valuable to local fishing communities in aggregate, these micro‐stocks are myriad and complex to study, monitor, assess and manage. Micro‐stocks need assessment and management at local scales to prevent small components from suffering the tragedy of commons. This paper asks how can we ever hope to address the research and management needs of so many small resources? Community‐based and territorial rights‐based systems may help in sustaining these resources, but servicing the technical needs of many small communities of stakeholders raises problems. A new generation of ‘barefoot ecologists’ is envisaged to perform this task.

Characterization of 2,3-butanediol-forming and valine-sensitive α-acetolactate synthase of Enterobacter cloacae - Anju Kaushal; Sunil Pabbi; Prince Sharma (World Journal of Microbiology and Biotechnology, 2003)

Laccase from a non-melanogenic, alkalotolerant γ-proteobacterium JB isolated from industrial wastewater drained soil - Jasleen Bains; Neena Capalash; Prince Sharma (Biotechnology Letters, 2003)

Membrane-anchored cytochrome c as an electron carrier in photosynthesis and respiration: past, present and future of an unexpected discovery - Fevzi Daldal; Meenal Deshmukh; Roger C. Prince (Photosynthesis Research, 2003)

Response of terrestrial carbon uptake to climate interannual variability in China - MINGKUI CAO; STEPHEN D. PRINCE; KERANG LI; BO TAO; JENNIFER SMALL; XUEMEI SHAO (Global Change Biology, 2003)
The interest in national terrestrial ecosystem carbon budgets has been increasing because the Kyoto Protocol has included some terrestrial carbon sinks in a legally binding framework for controlling greenhouse gases emissions. Accurate quantification of the terrestrial carbon sink must account the interannual variations associated with climate variability and change. This study used a process‐based biogeochemical model and a remote sensing‐based production efficiency model to estimate the variations in net primary production (NPP), soil heterotrophic respiration (HR), and net ecosystem production (NEP) caused by climate variability and atmospheric CO 2 increases in China during the period 1981–2000. The results show that China's terrestrial NPP varied between 2.86 and 3.37 Gt C yr −1 with a growth rate of 0.32% year −1 and HR varied between 2.89 and 3.21 Gt C yr −1 with a growth rate of 0.40% year −1 in the period 1981–1998. Whereas the increases in HR were related mainly to warming, the increases in NPP were attributed to increases in precipitation and atmospheric CO 2 . Net ecosystem production (NEP) varied between −0.32 and 0.25 Gt C yr −1 with a mean value of 0.07 Gt C yr −1 , leading to carbon accumulation of 0.79 Gt in vegetation and 0.43 Gt in soils during the period. To the interannual variations in NEP changes in NPP contributed more than HR in arid northern China but less in moist southern China. NEP had no a statistically significant trend, but the mean annual NEP for the 1990s was lower than for the 1980s as the increases in NEP in southern China were offset by the decreases in northern China. These estimates indicate that China's terrestrial ecosystems were taking up carbon but the capacity was undermined by the ongoing climate change. The estimated NEP related to climate variation and atmospheric CO 2 increases may account for from 40 to 80% to the total terrestrial carbon sink in China.

Terrestrial net primary production estimates for 0.5° grid cells from field observations—a contribution to global biogeochemical modeling - Daolan Zheng; Stephen Prince; Robb Wright (Global Change Biology, 2003)
Net Primary Production (NPP) is an important component of the carbon cycle and, among the pools and fluxes that make up the cycle, it is one of the steps that are most accessible to field measurement. While easier than some other steps to measure, direct measurement of NPP is tedious and not practical for large areas and so models are generally used to study the carbon cycle at a global scale. Nevertheless these models require field measurements of NPP for parameterization, calibration and validation. Most NPP data are for relatively small field plots that cannot represent the 0.5° × 0.5° grid cells that are commonly used in global scale models. Furthermore, technical difficulties generally restrict NPP measurements to aboveground parts and sometimes do not even include all components of aboveground NPP. Thus direct inter‐comparison between field data obtained in different studies or comparison of these results with coarse resolution model outputs can be misleading. We summarize and present a series of methods that were used by original authors to estimate NPP and how and what we have done to prepare a consistent data set of NPP for 0.5 °grid cells for a range of biomes from these studies. The methods used for estimation of NPP include: (i) aggregation of fine‐scale (plot or stand‐level) vegetation inventory data to larger grid cells, (ii) mapping of grid cells and area weighting of field NPP observations in each mapped class, (iii) direct correlation of extensive data sets of ground measurements with remotely sensed spectral vegetation indices, (iv) local modeling of NPP using key independent variables, for which maps are available at the scale of the grid cell, and (v) regression analysis to link productivity with controlling environmental variables. For a few grid cells whose NPP were obtained for multiple years, temporal analysis was conducted. The grid cells are grouped to the biome level and are compared with existing compilations of field NPP and the results of the Miami potential NPP model. Mean NPP was similar to the well‐known compilation of Whittaker and Likens, except for temperate evergreen needle‐leaved forest, woodland, and shrubland. The grid cell datasets are a contribution to the International Geosphere‐Biosphere Programme (IGBP) Data and Information System (DIS) Global Primary Production Data Initiative (GPPDI). The full dataset currently contains 3654 cells (including replicate measurements) developed from 15 studies representing NPP in croplands, sparse vegetation, shrub lands, grasslands, and forests worldwide. An edited subset consists of 2335 cells in which outliers were removed and all replicate measurements were averaged for each unique geographical location. Most of the data incorporated into GPPDI were wholly or partly developed by participants in the GPPDI, in addition to the present authors. These studies are gathered together here to provide a consistent account of the grid cell component of GPPDI and an analysis of the entire data set. The datasets have been deposited in an IGBP‐DIS GPPDI database ( http://daacl.esd.ornl.gov/npq/GPPDI/Combined_GPPDI_des.html ).

Avian communities in forested riparian wetlands of southern Michigan, USA - Rainy L. Inman; Harold H. Prince; Daniel B. Hayes (Wetlands, 2002)

On the determinants of census area: implications for mammalian macroecological patterns - Mary Ellen Prince; Marina Silva (Global Ecology and Biogeography, 2002)
The aim of this study was to examine the effects of various biological factors such as body mass, trophic level, climate and geography on census area in terrestrial mammals. We also examine the effects of census area on the population density–body mass relationship. The geographic areas covered in this study include most major terrestrial biomes including taïga, desert, savanna, grassland, tropical dry forest, temperate dry forest, tropical rain forest and temperate rain forest. An extensive literature search was conducted and we compiled data on census area and body mass from 377 mammalian populations and 59 communities. Statistical analyses include linear regression, Kruskal–Wallis analysis of variance, LOWESS, and multiple regression. Overall, the regression between log census area (A) and log body mass (M) yielded a slope of 0.710, which did not differ significantly from 0.75, but it was significantly different from 1.0. The analyses also showed that the log A–log M relationship is constrained within a well‐defined space in a similar fashion to the home range–body mass relationship. When mammals were separated into trophic groups, regression lines differed significantly in their intercepts, but not in slopes. At the community level, the census area was particularly affected by the population with the largest body mass within the community. Both the number of species and number of taxa encompassed by the community were found to be correlated positively with log A ( r = 0.26, P = 0.0464 and r = 0.27, P = 0.0398, respectively). Sampling of mammalian species is not usually random. Not only is census area significantly associated with the technique used to sample a given species, but it is also influenced by biological factors that have been shown previously to influence population density. Striking similarities were found between the census area–body mass relationship and the home range–body mass relationship, suggesting that investigators may sample mammalian populations over areas that actually reflect the use of space of their focal species.

Herpes simplex type 1 infects and establishes latency in the brain and trigeminal ganglia during primary infection of the lip in cotton rats and mice - G. Lewandowski; M. N. Zimmerman; L. L. Denk; D. D. Porter; G. A. Prince (Archives of Virology, 2002)

The fauna of thrombolitic microbialites, Lake Clifton, Western Australia - Y. Konishi; J. Prince; B. Knott (Hydrobiologia, 2001)

Mulberry-Silkworm Food Chain – A Templet to Assess Heavy Metal Mobility in Terrestrial Ecosystems - SPM. Prince; P. Senthilkumar; V. Subburam (Environmental Monitoring and Assessment, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Pharmacokinetics and safety of escalating single and repeat oral doses of GW420867X, a novel non-nucleoside reverse transcriptase inhibitor - K.H.P. Moore; L.M. Cass; N. Dallow; T.C. Hardman; A. Jones; M. Boyce; W.T. Prince (European Journal of Clinical Pharmacology, 2001)

Apolipoprotein-E dependent role for the FAS receptor in early onset Alzheimer's disease: finding of a positive association for a polymorphism in the TNFRSF6 gene - Lars Feuk; Jonathan Prince; Gerome Breen; Tesfai Emahazion; Andrew Carothers; David St Clair; Anthony Brookes (Human Genetics, 2000)

X-ray absorption spectroscopy of selenium-containing amino acids - I. J. Pickering; Graham N. George; Verena Van Fleet-Stalder; Thomas G. Chasteen; Roger C. Prince (JBIC Journal of Biological Inorganic Chemistry, 1999)

Geographical variation in morphometry of black-browed and grey-headed albatrosses from four sites - S. M. Waugh; P. A. Prince; H. Weimerskirch (Polar Biology, 1999)

Cell fusion corrects the 4-nitroquinoline 1-oxide sensitivity of Werner syndrome fibroblast cell lines - P.R. Prince; C.E. Ogburn; M.J. Moser; M.J. Emond; G.M. Martin; R.J. Monnat Jr (Human Genetics, 1999)

Enhanced biodecolorization of synthetic textile dye effluent by Phanerochaete chrysosporium under improved culture conditions - Dapinder K. Bakshi; K.G. Gupta; Prince Sharma (World Journal of Microbiology and Biotechnology, 1999)

Cell fusion corrects the 4-nitroquinoline 1-oxide sensitivity of Werner syndrome fibroblast cell lines - P.R. Prince; C.E. Ogburn; M.J. Moser; M.J. Emond; G.M. Martin; R.J. Monnat Jr (Human Genetics, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Biophysical stratification of the Amazon basin - Stephen D. Prince; MarC. K. Steininger (Global Change Biology, 1999)
In field measurement programmes, stratified sampling can optimize sampling efficiency, but stratification is often undertaken subjectively, and is frequently based on a priori classification schemes such as those used for vegetation maps. In order to avoid the problems associated with a priori subjective schemes, we explore here an objective procedure, Regression Tree Analysis (RTA). RTA has previously been used in local‐scale studies, but here we apply it to a very large study domain, namely the entire humid tropical zone of South America. The aim of the study was to develop an optimal sampling design in preparation for the Large Scale Biosphere‐Atmosphere Experiment in Amazonia (LBA). Co‐registered spatially continuous fields of rainfall, temperature, photosynthetically active radiation (PAR), the normalized difference index (NDVI), an index of surface moisture, and other independent variables were used to predict three dependent variables, annual net radiation (Rn), latent heat (LE) and net primary production (NPP). Rather than simply dividing the study area based on differing levels of the three dependent variables, empirical models were developed using RTA to indicate how the relationships between these and possible forcing variables vary across the study area. For each variable long‐term seasonal indices such as annual average, monthly minimum and amplitude were used to exclude effects of temporal phase differences between the hemispheres. The resulting hierarchical models revealed variations in the interdependence of the forcing variables throughout the study area and therefore provided a basis for a stratified sampling and identifying the most important variables to be collected in LBA for the Amazon basin as a whole as well as optimizing the sampling scheme for scaling up findings from the field scale to larger areas.

Survey of Grauer's Gorillas (Gorilla gorilla graueri) and Eastern Chimpanzees (Pan troglodytes schweinfurthi) in the Kahuzi-Biega National Park Lowland Sector and Adjacent Forest in Eastern Democratic Republic of Congo - Jefferson S. Hall; Lee J. T. White; Bila-Isia Inogwabini; Ilambu Omari; Hilary Simons Morland; Elizabeth A. Williamson; Kristin Saltonstall; Peter Walsh; Claude Sikubwabo; Dumbo Bonny; Kaleme Prince Kiswele; Amy Vedder; et al. (International Journal of Primatology, 1998)

Evidence from rain‐use efficiencies does not indicate extensive Sahelian desertification - S. D. Prince; E. Brown De Colstoun; L. L. Kravitz (Global Change Biology, 1998)
Desertification is regarded as one of the major global environmental problems of the 20th century and the African Sahel is often quoted as the most seriously affected region. Previous attempts to map the occurrence and severity of desertification in the Sahel have been unsatisfactory, mainly because of the lack of any readily measured, objective indicators. We explore here the properties of the ratio of net primary production (NPP) to precipitation – the rain‐use efficiency (RUE) – calculated from remotely sensed vegetation indices and rain gauge data. Negative deviations from the normal range of RUE values are shown to be an indicator of desertification. Observations of NPP of the entire Sahel were possible using satellite platforms for the period 1982–90, including the 1984 drought. The results suggest that NPP was remarkably resilient, a fact that was reflected in only little variation in the RUE during the period of study. Thus, in much of the region, NPP seems to be in step with rainfall, recovering rapidly following drought and not supporting the fears of widespread, subcontinental scale desertification taking place in the 9‐year period that is studied. In fact the results show a small but systematic increase in RUE for the Sahel as a whole from 1982 to 1990, although some areas contained within the region did have persistently low values.

Crystallographic studies of mutant reaction centres from Rhodobacter sphaeroides - Paul K. Fyfe; Katherine E. McAuley-Hecht; Justin P. Ridge; Steve M. Prince; Günter Fritzsch; Neil W. Isaacs; Richard J. Cogdell; Michael R. Jones (Photosynthesis Research, 1998)

A peroxisome proliferator-activated receptor-alpha (PPARα) cDNA cloned from guinea-pig liver encodes a protein with similar properties to the mouse PPARα: implications for species differences in responses to peroxisome proliferators - Jonathan D. Tugwood; Peter R. Holden; Neil H. James; Rebecca A. Prince; Ruth A. Roberts (Archives of Toxicology, 1998)

Calcitriol enhancement of TPA-induced tumorigenic transformation is mediated through vitamin D receptor-dependent and -independent pathways - Pi-Ling Chang; Tan-Feng Lee; Kate Garretson; Charles W. Prince (Clinical & Experimental Metastasis, 1997)

Elemental composition of a tusk of a dugong, Dugong dugon , from Exmouth, Western Australia - J. S. Edmonds; Y. Shibata; R. I. T. Prince; A. R. Preen; M. Morita (Marine Biology, 1997)

The ability of selected bacterial isolates to utilise components of synthetic metal-working fluids as sole sources of carbon and nitrogen for growth - K.L.M. Buers; E.L. Prince; C.J. Knowles (Biotechnology Letters, 1997)

Diet and feeding ecology of the diving petrels Pelecanoides georgicus and P. urinatrix at South Georgia - K. Reid; J. P. Croxall; T. M. Edwards; H. J. Hill; P. A. Prince (Polar Biology, 1997)

Experimental linkage issues of petroleum site bioremediation - J. W. Blackburn; E. J. Harner; W. K. Robbins; R. C. Prince; J. R. Clark; R. M. Atlas; J. B. Wilkinson (Biodegradation, 1994)

The cytochromes of a marine Beggiatoa - Roger C. Prince; Karen E. Stokley; Copper E. Haith; Holger W. Jannasch (Archives of Microbiology, 1988)

Preliminary studies on the development of a swine vesicular disease vaccine - G. N. Mowat; M. J. Prince; R. E. Spier; R. F. Staple (Archives of Virology, 1974)

Enhancement of immunizing potency of a foot-and-mouth disease vaccine for cattle by treatment of the antigen with formaldehyde - G. N. Mowat; R. C. Masters; M. J. Prince (Archives of Virology, 1973)

Some effects of irrigation and pertilization on the yield and quality of Kennebec potatoes - A. B. Prince; P. T. Blood (American Journal of Potato Research, 1962)

Sectional notes - H. G. Zuckerman; C. H. Metzger; W. B. Ward; John S. Gardner; Hussey Frank W.; E. V. Hardenburg; H. O. Werner; Robert Schmidt; E. M. Gillig; E. B. Tussing; Geo E. Prince; Brooks D. Drain; et al. (American Journal of Potato Research, 1936)

Sectional notes - C. H. Metzger; H. L. Cochran; C. L. Fitch; Julian C. Miller; Frank W. Hussey; Lionel Harris; Robert Schmidt; E. R. Jackman; J. B. R. Dickey; Geo E. Prince; Brooks D. Drain (American Journal of Potato Research, 1936)

Sectional notes - J. H. Heckman; H. G. Zuckerman; C. H. Metzger; B. A. Brown; E. R. Bennett; W. B. Ward; C. L. Fitch; O. H. Elmer; Jhon S. Gardner; Julan C. Miller; Frank W. Hussey; E. L. Newdick; et al. (American Journal of Potato Research, 1935)

Sectional notes - William G. Amstein; C. H. Metzger; W. B. Ward; C. L. Fitch; H. G. Zuckerman; Frank W. Hussey; E. L. Newdick; Ralph W. Donaldson; J. J. Bird; Lionel Harris; H. O. Werner; Wm. H. Martin; et al. (American Journal of Potato Research, 1935)